Multiscale insights into the phase-dependent sintering of Fe2O3 and Fe3O4 under chemical looping conditions - Guanshan Liu; Yang Lei; Yayong Zhang; Huijun Ge; Tao Zhang; Rui Tan; Mudi Wu; Shiwei Ma; Mingwu Tan; Tao Song (Fuel, 2027)

Salt perception programming for salt reduction in meat products: Integrating salt-release kinetics, oral processing, multisensory perception, and meat product formulation - Xiaohai Ma; Qiuye Wang; You Ge; Qian Li; Duoting He; Shuang Bai; Yuan Liu (Trends in Food Science & Technology, 2026)

Piperazine derivatives monomer-based TFC nanofiltration membranes with enhanced mineral/organic selectivity for efficient surface water purification - Xuewu Zhu; Xiaowen Zhang; Xiangfeng Jia; Yixuan Li; Wenxin Yan; Feiyue Ge; Feilong Zhang; Xinwei Kang; Yongshan Ma; Daliang Xu (Desalination, 2026)

Enhanced carbon capture and storage in the green microalga Chlamydomonas by heterologous expression of an engineered carbonic anhydrase - Yunlong Ge; Wanyi Zhang; Shuo Lin; Xinyu Mao; Keqing Liu; Wei Ma; Songlin Ma; Yanbo Liu; Zhanyou Chi; Fantao Kong (Bioresource Technology, 2026)

Mechanism study of METTL3 regulating Wnt/β-Catenin signalling in Pg.LPS-stimulated hSCAPs odontogenic differentiation - Xiang Ge; Yongna Zhu; Yongting Ji; Lina Jiang; Xiu Ying; Min Wang; Chengxi Li; Caiyun Ma; Qingling Yang (Molecular Biology Reports, 2026)

Transcriptomic insights into ferroptosis and potential therapeutic targets in central Post-Stroke pain following thalamic hemorrhage - Yinggang Xiao; Ju Gao; Xiaojin Wei; Yang Zhang; Yali Ge; Cunjin Wang; Tianfeng Huang; Longfei Ma (Molecular Biology Reports, 2026)

Untargeted serum lipidomics reveals lipid metabolic disturbances and identifies candidate lipid biomarkers in acute diquat poisoning - Xinxin Huang; Xunan Kan; Lei Xiao; Chuanguang Han; Ge Li; Quan Xia; Qianli Zou; Qinhai Ma; Shuai Song (Toxicology and Applied Pharmacology, 2026)

Elevated contaminations and risks of novel organophosphate esters and their transformation products in paddy soils - Zixiao Zhao; Meng Gao; Mohan Ma; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; Hongwen Sun (Journal of Environmental Sciences, 2026)

Sea cucumber viscera-derived antifreeze peptides: identification, ice recrystallization inhibition activity, and ice-binding mechanism - Richeng Yu; Yang Zhao; Linnan Wang; Peng Ge; Zhupeng Zhang; Yuejuan Jia; Qianyun Ma; Wenxiu Wang; Jianfeng Sun (Food Research International, 2026)

Modified β-glucans promote saponin and fucosylated chondroitin sulfate biosynthesis in sea cucumber Apostichopus japonicus in association with activation of the TLR-MAPK signaling pathway - Zezheng Qi; Zeyu Zhang; Wenyue Dai; Hongmei Ma; Junpeng Ge; Yutong Yu; Mengling Cheng; Wenjian Zhao; Shihui Pan; Min Gu; Nan Bai (Fish & Shellfish Immunology, 2026)

Holocene environmental changes recorded by magnetic parameters of sediments in the Yangtze River Delta and implications for prehistoric cultural development - Guiye Zhang; Longsheng Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu (Estuarine, Coastal and Shelf Science, 2026)

Rapid phase separation assisted hydrogel evaporator for solar desalination and water environmental purification - Jianbo Zhang; Jinming Yu; Tongyu Zhang; Zhenjie Ma; Yutian Wang; Bo Ge; Hui Zhao; Tonghui Zhang; Guina Ren; Zhaozhu Zhang (Desalination, 2026)

Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

Scaling-risk early warning in industrial cooling-water systems: A chemically regularized machine-learning framework using routine water-quality data - Jixuan Guo; Weiyi Yang; Shihan Wu; Xinyue Wei; Ruochun Wang; Ruoxin Ma; Xinyu Wu; Min-ge Tian; Hao Xu (Journal of Water Process Engineering, 2026)

Synergistic H₂O₂-granular activated carbon pretreatment mitigates nanofiltration membrane fouling during secondary effluent treatment: Performance and mechanisms - Qinghao He; Bing Xu; Xiangfeng Jia; Yixuan Li; Yongshan Ma; Guangchao Li; Xinwei Kang; Feiyue Ge; Daliang Xu; Xuewu Zhu (Journal of Water Process Engineering, 2026)

Experimental design and adsorption mechanism research of risedronate nanofunctionalized hydroxyapatite for efficient removal of Co2+ and Pb2+ - Jianzhe Ma; Juying Li; Mingxing Shi; Yuting Chu; Yueqing Zhang; Feng Ge; Mingzhu Xia; Fengyun Wang; Deyang Kong (Journal of Environmental Chemical Engineering, 2026)

Optimizing the drainage segment ratio of stacked prefabricated vertical drain (S-PVD) vacuum preloading method to improve vacuum pressure transmission efficiency - Huayang Lei; Jiankai Li; Shuangxi Feng; Changyuan Ma; Yunyang Ge (Geotextiles and Geomembranes, 2026)

Purification reshapes systemic exposure and immunomodulation-mediated antiviral responses of licorice triterpenoids - Zhongyuan Li; Miaomiao Liu; Ge Qu; Guige Hou; Jipeng Wang; Yukui Ma; Qinghua Cui (Food Research International, 2026)

Short-term nitric oxide gaseous treatment of post-rigor pork: Multidimensional impacts on meat quality, protein oxidation and proteolysis, and microstructure - Jiaye Zhu; Yongmao Ye; Liangyu Zhang; Haoyang Ma; Xinnuo Zhou; Yu Qi; Qingfeng Ge; Mangang Wu; Hai Yu; Rui Liu (Food Chemistry, 2026)

A systematic review of emerging pretreatments, drying technologies, and artificial intelligence applied in processing blueberry - Qiao-Yi Ma; Yan Ge; Magdalena Zielinska; Jia-Xuan Shu; Shan-Yu Wang; Xiaojun Huang; Zi-Liang Liu (Food Control, 2026)

Unravelling nonlinear effects of urban morphology on rooftop PV adoption using explainable machine learning - Chenshuo Ma; Yifu Ge; Qiancheng Wang; Shengao Yi (Energy and Buildings, 2026)

3D solid-liquid heterogeneous anode/electrolyte interlayer for Zn anode: The trade-off between spatial regulation and ion transport kinetics - Haifeng Bian; Yilun Ren; Shunshun Jia; Qing Zhou; Ge Xue; Qimeng Wang; Haoran Wang; Jian Gu; Yujie Ma; Xiangkang Meng (Chemical Engineering Journal, 2026)

Proteomics-guided multivalent capture and integrated amplification enable profiling of tumor-derived extracellular vesicles in gastric cancer - Ke Ge; Yongan Ren; Pengcheng Wang; Guangzhong Ma; Bo Yao; Changku Jia; Yuanyu Wang; Kai Ye (Chemical Engineering Journal, 2026)

pH-responsive microcapsules co-delivering radioprotectant and probiotics for synergistic mitigation of radiation-induced enteritis - Caifang Gao; Jiaxuan Ma; Luke Ge; Yongle Zhao; Ru Feng; Pengqi Zhu; Jinghua Sun; Ruiping Zhang (Chemical Engineering Journal, 2026)

Advances in chitosan materials for supercapacitor applications: A review - Bingchun Ma; Qihang Zhou; Qingming Zhang; Guojiao Chen; Wen Ge; Shukang Deng; Peizhi Yang (Carbohydrate Polymers, 2026)

Microplastic pollution in an anthropogenically modified river: sediment occurrence, associated microbiota, and environmental correlates - Kai Zhang; Ge Ma; Qingyi Wang; Chengshi Ding; Xinlu Shen; Chaoyue Zhao; Siwei Gao; Chenyang Shen; Hui Gao; Rui Xin; Fengxia Yang (Environmental Monitoring and Assessment, 2026)

‘From growth monitoring to berry quality prediction: Advances and challenges in UAV remote sensing for precision viticulture - Jinyu Yang; Mengyuan Wei; Qifan Chen; Tingting Ma; Qian Ge; Yue Yan; Jiming Li; Baofeng Su; Yulin Fang; Xiangyu Sun (Computers and Electronics in Agriculture, 2026)

Boundary-aware data augmentation for solid waste hydrothermal carbonization: An uncertainty-guided SMOTE framework - Zherui Ma; Xiangqian Wang; Zhirong Li; Jiandong Jia; Ruikun Wang; Lichao Ge (Journal of Environmental Management, 2026)

A multifunctional hybrid delivery system of sodium alginate-based nanoparticles-hydrogel beads “double fence” effect for pea peptide - Guocong Ma; Mingwu Qiao; Dan Hai; Yan Ma; Ge Bai; Peijun Zhao; Xianqing Huang; Xinyu Sun; Lianjun Song (Food Chemistry, 2026)

Heterologous expression and functional characterization of Bacillus subtilis natto MenA in Escherichia coli and its role in Vitamin K2 Biosynthesis - Said Nawab; Chuanchao Wu; Zhangbing Ge; Wei Tao; Yuqi Li; Yuexin Ma; Yaqing Zhao; Jie Song; Yi-Feng Jiang; Yan Liu (Food Bioscience, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

Photo-crosslinking strategy to lock π-π-assembled ion channels in polymer membranes for enhanced monovalent anion selectivity - Yachun Ma; Simian Fei; Jie Fang; Qiuhua Li; Lin Zhang; Huchuan Wang; Liang Ge; Chuanrun Li (Desalination, 2026)

Cyclic behaviour of plate-monopile and bucket-monopile hybrid foundation in sand - Yukun Ma; Sanchari Mondal; Ge Cui; Muhammad Aleem; Subhamoy Bhattacharya; Liang Cui (Computers and Geotechnics, 2026)

Efficient direct electroreduction defluorination of PFOA driven by SO-MIL-88B(Cu) adaptive electrocatalyst - Hailong Wang; Ruijie Ge; Chenjian Ye; Jianzhong Zhu; Liang Chen; Binglu Teng; Zhenghao Xu; Jianbo Ma (Chemical Engineering Journal, 2026)

Electronic structure modulation in Co-doped NiFe-LDH for efficient ethylene glycol oxidation in simulated seawater - Jiaming Ding; Tao Li; Yi Ma; Huan Ge; Ning Jian; Jialing Tang; Jing Yu; Jordi Arbiol; Haiting Wang; Luming Li; Andreu Cabot; Junshan Li (Chemical Engineering Journal, 2026)

Interplay of quorum-sensing signals (homoserine lactone/penicillic acid) and nitrate in regulating microbial processes: As(III) immobilization, CH4 and N2O emission in constructed wetlands - Dongxue Fu; Huiwen Ma; Jing Zhang; Honghui Wang; Yixin Wu; Liyun Ge; Chunzhen Fan; Shuqing Wu; Shuyun Zhang; Hui Gao; Zheng Chen (Bioresource Technology, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

A Sea Surface Salinity error correction model integrating physical models and complex environmental influences - Yanling Han; Wenbin Zhao; Qinqin Sun; Ge Song; Ping Ma; Yun Zhang; Chuanxiang Hua; Shouqi Cao (International Journal of Remote Sensing, 2026)

A Wind Data Quality Control Algorithm Utilizing Deep Learning-Based Association Test Rules - Ruidi Ma; Song Gao; Fan Jiang; Bo Yu; Haoqiang Tian; Yanchen Song; Yong Ge; Dianjun Ren; Chenxu Wang (Journal of Marine Science and Engineering, 2026)
Harnessing the powerful learning and modeling capabilities of artificial intelligence, this study introduces a deep learning-driven wind data quality control algorithm that employs correlation verification rules. By constructing a Dual-Track Information Fusion Network (DTF-Net), it captures local temporal variations in wind speed via the temporal track and uncovers physical coupling relationships among temperature, pressure, wind direction, and other variables through the global track. Integrating dynamic three-standard-deviation spike detection with 3δ-RMSE spatial validation based on deep learning predictions, the algorithm enables multi-dimensional collaborative anomaly detection in the absence of neighboring stations. Experimental findings demonstrate that the proposed method achieves Mean Absolute Errors (MAE) of 0.217, 0.398, and 0.462 for 1 h, 12 h, and 24 h wind speed forecasts, respectively, representing a 3.8–61.3% reduction compared to general-purpose models like AutoFormer, ITransformer, and FiLM. The anomaly detection rate for quality control ranges from 0.33% to 9.20%, effectively identifying data aberrations during buoy maintenance, equipment failures, and abrupt changes in short-term weather patterns. This study leverages the powerful learning and modeling capabilities of artificial intelligence to establish a novel and easily understandable intelligent quality-control paradigm for sparse ocean observation networks, providing direct practical value for improving the quality of marine meteorological data assimilation.

PEDV nucleocapsid (N) protein induces liquid-liquid phase separation (LLPS) to selectively aggregate the viral genome - Jinyi Ge; Jingjing Yuan; Liang Zheng; Matthew Kay; Zhijun Wu; Xiaojuan Zhao; Xiaojuan Xu; Wenlong Xia; Jingjing Zhu; Jinzhu Ma; Zhibao Chen; Hua Zhang (Veterinary Microbiology, 2026)

Erratum to “Untargeted serum lipidomics reveals lipid metabolic disturbances and identifies candidate lipid biomarkers in acute diquat poisoning” [Toxicology and Applied Pharmacology 516 (2026) 117995] - Xinxin Huang; Xunan Kan; Lei Xiao; Chuanguang Han; Ge Li; Quan Xia; Qianli Zou; Qinhai Ma; Shuai Song (Toxicology and Applied Pharmacology, 2026)

High-pressure crystal structure database - Zhenyu Wang; Qingchang Wang; Honglin Li; Junwen Duan; Heng Ge; Xiaoshan Luo; Pengyue Gao; Wei Zhang; Jian Lv; Yanchao Wang; Yanming Ma (Science Bulletin, 2026)

Quantifying facility-scale CO2 emissions using spaceborne hyperspectral imageries - Ge Han; Huayi Wang; Zhipeng Pei; Huiqin Mao; Jiaying Ying; Siwei Li; Xin Ma; Boming Liu; Feiyue Mao; Wei Gong (Remote Sensing of Environment, 2026)

A stochastic multi-physics framework integrating thermo-electrochemical-microbial dynamics for lifecycle corrosion prediction and risk quantification of subsea pipelines - Yungen He; Ge Song; Shuang Ma; Yajing Liu; Yanhui Hu; Rongsheng Lin; Jiangen Tao (Ocean Engineering, 2026)

Preliminary insights into the release behavior of dissolved organic matter from aged microplastics in seawater: Effects of aging types - Xi Li; Qimeng Yang; Huimin Ma; Ruru Ge; Xinwei Zhou; Peng Ren (Marine Environmental Research, 2026)

Agricultural anthropogenic attribution of nitrate in karst river basin: Insights from nitrate dual isotopes and Bayesian mixing model - Xinyi He; Jie Zeng; Qixin Wu; Qian Zhang; Zhong-Jun Wang; Jie Ren; Qing Ma; Jie Zhang; Xin Ge (Journal of Environmental Management, 2026)

Mineralogical fingerprints reveal the source-to-sink dynamics of the Yellow River and local sources in Laizhou Bay, Bohai Sea - Menglin Zhuo; Xiaoyuan Gu; Jianwei Sun; Qingtong Wang; Hengjian Li; Haigen Wang; Yuhai Chen; Chunhui Ma; Xiangwei Ge; Fengbin Zhu; Yadong Xu; Shixiong Yang (Estuarine, Coastal and Shelf Science, 2026)

Temperature-dependent KMnO4 oxidative decrosslinking for enhanced permeance and scaling resistance of polyamide nanofiltration membranes - Ning Ma; Ruirui Jiang; Jielin Shi; Xinwei Kang; Jinyu Li; Feiyue Ge; Feilong Zhang; Feiyong Chen; Daliang Xu; Xuewu Zhu (Desalination, 2026)

Reactant-adsorption induced flexible hydrogen-bond networks on Co–O–Fe electronic bridges for enhanced electro-oxidation of methanol to formate - Haiqing Gong; Ruixiang Ge; Congcong Jian; Ruochen Zhang; Shuo Lu; Min Ma; Jian Tian (Chemical Engineering Journal, 2026)

Metal-phenolic microcapsules-reinforced hydrogel-based in situ tumor vaccine for postoperative adjuvant therapy - Xin Tan; Renwang Sheng; Yanling Liang; Yinghua Tao; Weikun Li; Nuoya Chen; Diyi Feng; Xinyang Pan; Shuangshuang Ma; Fangzhou Liu; Ling Liu; Liqin Ge (Chemical Engineering Journal, 2026)

Unraveling the critical role of ClO• in the degradation of emerging organic contaminants by far-UVC/chlorine: Radical contribution assessment and influence of water matrix - Ping Li; Ge Zeng; Wenjun Zhang; Qiuling Lu; Haonan Lu; Kai Wang; Jun Ma; Yan Zhang; Tao Yang (Chemical Engineering Journal, 2026)

Differences between human and rat 5α-Reductase 1 inhibition by phenolic disinfectants: Comparative kinetics and binding modes for neurosteroid synthesis - Xinyu Han; Wanyu Li; Yinghao Huang; Lisha Wang; Tianchi Zhao; Xishi Chen; Hao Lin; Yiyan Wang; Ren-shan Ge; Jianfeng Ma (Chemico-Biological Interactions, 2026)

Corrigendum to “Interplay of quorum-sensing signals (homoserine lactone/penicillic acid) and nitrate in regulating microbial processes: As(III) immobilization, CH4 and N2O emission in constructed wetlands” [Biores. Technol. 455 (2026) 134788] - Dongxue Fu; Wenhui Ma; Jing Zhang; Honghui Wang; Yixin Wu; Liyun Ge; Chunzhen Fan; Shuqing Wu; Shuyun Zhang; Hui Gao; Zheng Chen (Bioresource Technology, 2026)

Intensive management shifts litter decomposition from mycorrhizal to root-dominated pathway in a subtropical bamboo plantation - Wenhao Jin; Jiahe Wang; Jiangfei Ge; Xingcong Ma; Qifeng Wu; Shuai Shao; Chenfei Liang; Liyuan Peng; Xiaomin Ma; Yuchuan Fan; Yongfu Li; Junhui Chen; et al. (Applied Soil Ecology, 2026)

Synergistic Interactions Between Warming and Elevated Atmospheric CO 2 Increase Soil Organic Carbon Sequestration - Ruiqi Yao; Yike Zhang; Wolfgang Wanek; Zhongkui Luo; Haoran Fu; Scott X. Chang; Cesar Terrer; Mingkai Jiang; Tida Ge; Guopeng Liang; Yuanhe Yang; Yiqi Luo; et al. (Global Change Biology, 2026)
Warming and elevated CO 2 (eCO 2 ) are two potentially opposing climate‐carbon (C) feedback mechanisms that modulate the magnitude of the land C sink, with warming decreasing and eCO 2 increasing C sequestration. However, their net effect on soil organic C (SOC)—the largest terrestrial C stock—remains uncertain. Here, we quantify how warming, eCO 2 , and their interactions influence SOC by using 5558 paired observations from 1392 global studies across ecosystem types. Our study shows that warming reduces SOC by 8.0%, primarily by suppressing aboveground C inputs (−1.0%) and decreasing microbial C use efficiency (−9.9%). Concurrent warming and eCO 2 increase SOC by 7.6%—a synergistic effect larger than eCO 2 alone (+4.8%), primarily contributed by croplands. This outcome may result from increases in plant C inputs and soil nitrogen availability under eCO 2 , which facilitate microbial C assimilation and necromass formation (+3.9%). These processes promote the accumulation of mineral‐associated C (+9.9%) and offset the negative effects of warming. The combined effect of warming and eCO 2 is projected to increase SOC by 27.4 Pg C by 2100. Our findings highlight that synergistic interaction between warming and eCO 2 increases SOC sequestration and enhances SOC stability under future climate change.

Quercetin exerts radioprotective effects against radiation-induced intestinal injury with involvement of the PI3K-AKT/Caspase-3 axis - Qing Guo; Zhibing Tang; Zhenyu Hou; Ge Yan; Jiaxuan Wang; Man Zhang; Ruige Ma; Juan Wang; Qiong Feng; Zhen Wang; Chunlei Wang; Lin Zhao (Molecular and Cellular Biochemistry, 2026)

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Brain-wide mapping and region-specific cellular characterization of Trhr1 reporter-labeled cells in mice using VISoR imaging - Mingrui Zhang; Su Ma; Hanbo Guo; Yuehan Ji; Hong Ni; Rongjing Ge; Yuanyuan Wang; Yong Jiang; Lianjun Li; Yuyang Zhu; Qian Wang; Lingxiao Guo; et al. (Brain Structure and Function, 2026)

Liquid-liquid phase separation-driven enzyme catalysis for efficient biosynthesis of isoprenoid natural products - Han Wang; Bing-Bing Ma; Fei Cao; Ji-Jin Xie; Bei-Bei Wang; Shao-Yong Zhang; Ji-Dong Wang; Zha-Jun Zhan; Yu-Mei Ge; Xu-Ming Mao (Science China Life Sciences, 2026)

Unveiling the distance-to-shore gradient of construction land: shore spectrum analysis for sustainable management of Poyang Lake - Teng Ma; Wei Yan; Jiaheng Wang; Junfeng Ge; Hui Zou; Xuejun Duan (Environment, Development and Sustainability, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Substantial terrestrial export of dissolved organic carbon in China - Qian Yu; Han Li; Xiaodong Ge; Mingrui Ma; Wenxin Zhao; Jinya Yang; Jan Mulder; Lei Zhang; Yu Zhao; Lei Duan (Science Bulletin, 2026)

Pear PbrPRKs regulate pollen tube growth via modulation of apical actin and reactive oxygen species homeostasis - Lan Xu; Yuzhen Qian; Yusheng Xu; Haoran Wu; Juan Ma; Jitao Ge; Yuqian Wang; Kaijing Zhang; Yihu Sui; Xueping Zhang; Jingjing Qian; Shuangshuang Jia; et al. (Plant Science, 2026)

Climate impacts and sustainable implications of large-scale desert solar farms across regions - Yuhan Zhou; Junfeng Liu; Huihuang Wu; Jianmin Ma; Wendong Ge; Boyang Wu; Xinyang Liu; Shu Tao (Journal of Cleaner Production, 2026)

Experimental and numerical study on the effects of preheat temperature and steam dilution rate on the laminar burning velocity of CH4/O2/H2O - Shun Meng; Chunyu Zhang; Xinbin Ge; Shun Bian; Yang Hua; Changfa Tao; Yejian Qian; Peiyong Ma; Chunmei Wang (Fuel, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Microfluidic-based magnetic microspheres for targeted delivery of curcumin nanoparticles in gastroesophageal reflux disease therapy - Haoyao Jiang; Zhonglin Fang; Han Lin; Di Xu; Wanqian Xu; Mengqi Han; Luoran Shang; Ye Zhao; Teng Ma; Di Ge (Chemical Engineering Journal, 2026)

Iron-based nanozymes: From mechanisms to functional applications - Jia-Ming Wang; Kai-Zheng Feng; Pu-Ge Yu; Haoan Wu; Ming Ma; Yu Zhang (Chemical Engineering Journal, 2026)

A chitosan-based multifunctional hydrogel patch improves cardiac health and function by repairing the post-myocardial infarction microenvironment - Qingpeng Wang; Dangwei Li; Zijing Wu; Shuai Ma; Ge Tan; Li Zhang; Hongbing Deng; Jinping Liu (Carbohydrate Polymers, 2026)

Reduce-order dynamic modeling of X-braced girder considering flexible joints for analytical vibration characteristic investigation - Mei Liu; Huaqiang Ge; Lishan Ma; De Li; Zunbing Sheng (Advances in Space Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Precise perception of surface tackiness enabled by a soft single-sensing-element tactile sensor - Ying Yang; Mingwei Gu; Jia-Sen Xie; Xingyu Ma; Yan-Na Lu; Lin Zheng; Jinhui Gu; Junshuai Chen; Yunjie Lu; Denys Makarov; Jin Ge (Science Bulletin, 2026)

Monitoring algal blooms in eutrophic inland lakes using OLCI: Overcoming cloud and sun-glint effects on low-quality imagery - Bingqian Han; Shaojing Wang; Long Fei; Kaishan Song; Ge Liu; Yue Ma; Shidi Shao; Yang Li; Yujin Zhou; Jipeng Zhang (Journal of Hazardous Materials, 2026)

Early-life and lifelong exposure to environmentally relevant enrofloxacin reorganizes a proteobacteria-centered gut-lipid-resistome steady state in marine medaka - Ziyi Guo; Zheyu Wang; Yaxin Liu; Meiru Wang; Hongyue Ma; Ziwei Wang; Siyuan Zhang; Yidan Chang; Hezi Ge; Chenglu Li; Hui Yang; Hui Miao; et al. (Journal of Hazardous Materials, 2026)

Cellulose-guided interfacial engineering of Cu-MOF nanozyme on nylon/spandex fabric for synergistic UV shielding, O3 decomposition and ROS scavenging - Xiaomeng Li; Yaning Ma; Ruimeng Li; Yan Ge; Jiapeng Tang (Journal of Environmental Chemical Engineering, 2026)

White peroxidase-mimicking Mn-MOF enabled smartphone-assisted colorimetric sensor for on-site visual detection of perfluorooctane sulfonate in water samples - Shao-Hua Wen; Jun Zhan; Hao Wu; Yule Ji; Qingpeng Zhao; Ziqi Yuan; Junping Ma; Sha Yu; Yuanzhen Zhou; Man Ge (Journal of Environmental Chemical Engineering, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Polygonatum kingianum polysaccharides delay aging through UPRmt-mediated regulation of mitochondrial function and intestinal homeostasis - Jing-Juan Yang; Sheng-Lan Zhao; Ya-Ge Ma; Jian-Guo Jiang; Xi Zhang (Food Bioscience, 2026)

Wide-narrow row planting optimizes source-sink dynamics to sustain high yield and achieve water conservation in drip-irrigated winter wheat - Jingjing Lu; Tao Jiang; Songhao Ge; Xiangmei Chang; Lili Su; Wenxiu Xu; Jianghua Tang; Jipeng Zhai; Zihan Ma (Field Crops Research, 2026)

Study on the electrocatalytic reduction mechanism of PFOA degradation at gradient sulfur-doped copper sites - Hailong Wang; Ruijie Ge; Chenjian Ye; Jianzhong Zhu; Jue Liu; Liang Chen; Mengjun Xu; Jianbo Ma (Environmental Research, 2026)

From selection to design: Reshaping aptamer discovery with artificial intelligence - Xin Yang; Shijian Ding; Meishen Ren; Huarui Zhang; Xiaohui Tao; Ning Zhang; Yihao Zhang; Hewen Jiange; Yufei Pan; Shanshan Yao; Luyao Wang; Yuan Ma; et al. (Chemical Engineering Journal, 2026)

Recycling spent lithium-ion batteries as high-performance catalysts for peracetic acid activation toward rapid degradation of organic pollutants - Ge Li; Yujie Cheng; Yufei Wu; Yuhao Tian; Bowen Yang; Haoran Chen; Guosen Zhang; Zhengqian Liu; Yuhong Cui; Jun Ma; Pengchao Xie (Chemical Engineering Journal, 2026)

Multiscale magnetic-dielectric coupling in nano-micro-macro Fe/Fe3O4@C aerogels via confinement strategy for broadband electromagnetic wave absorption - Xianlin Zhan; Mengqiu Huang; Bicheng Li; Ge Ma; Wenbin You; Yun Tang; Lei Wang; Renchao Che (Chemical Engineering Journal, 2026)

Pollen-based reconstruction of Anthropocene environmental changes in East Taihu Lake (Eastern China): Impacts of reclamation, agricultural expansion, and urbanization over the past century - Yucui Sun; Zekun Li; Yawen Ge; Mengdi Zhang; Chenlu Ma; Xiangdong Yang; Qinghui Zhang (CATENA, 2026)

A Method for Calculating the Shortest Time Path for the Evacuation and Transfer of People at Risk of Flooding - Wei Ge; Heqiang Sun; Yutie Jiao; Laihong Jing; Yadong Zhang; Meimei Wu; Te Wang; Hua Zhang; Jianyou Wang; Yupan Qin; Fuheng Ma; Pieter van Gelder (Water Resources Management, 2026)

Reducing wheat grain Cd via harnessing indigenous microbiota in weakly alkaline soil - Chenghao Ge; Yixuan Wang; Wenyan Ma; Hong-Bo Li; Jingxia Guo; Hafiz Adeel Ahmad; Yan Gao; Dongmei Zhou (Plant and Soil, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

PG-DyMamba: a physics-guided dynamic graph Mamba network for significant wave height prediction - Fan Jiang; Yinzhu Zang; Ruidi Ma; Bo Yu; Hui Li; Song Gao; Yong Ge; Dianjun Ren (Frontiers in Marine Science, 2026)
Accurate prediction of Significant Wave Height (SWH) is vital for marine engineering safety, yet balancing computational efficiency with physical consistency in long-sequence modeling remains a challenge for data-driven approaches. To address this, we propose the Physics-Guided Dynamic Graph Mamba Network (PG-DyMamba). By integrating oceanographic priors such as windwave relations, our Physics-Aware Graph Learner adaptively captures time-varying multivariate dependencies. Concurrently, the Mamba architecture processes long historical sequences with linear complexity. To ensure physical plausibility, the model employs a composite loss function based on energy conservation and fluid smoothness, effectively constraining predictions to adhere to fundamental physical laws. Empirical evaluations on Australia, NDBC, and North Sea datasets confirm that PG-DyMamba outperforms state-of-the-art baselines. Notably, the model achieves a 19.2% MSE reduction in 48-step prediction horizon on the Australia dataset, demonstrating its robustness for operational marine applications.

Hydrophobic high-frequency vibration collaborative strategy for reducing resistance and soil adhesion of tillage tools in lime concretion black soil - Kuan Qin; Ding Zhang; Biao Ma; Weidong Gao; Chengmao Cao; Xu Zhu; Junjie Lu; Wei Wang; Jun Ge; Qichun Feng; Huaizhi Liu; Siliang Liu; et al. (Soil and Tillage Research, 2026)

Electroacupuncture mitigates cognitive impairment caused by anesthesia and surgery in aged rats by inhibiting the p38 MAPK signaling pathway - Bin Cheng; Qian He; Dan Ge; Shuyan Ma; Yuyu Luo; Jiao Wang (Neurotoxicology and Teratology, 2026)

Investigation and optimization of end-face sealing by analyzing fluid leakage paths in energy recovery device for SWRO desalination system - Bianxiong Ma; Yiyang Ge; Gangtao Liang (Desalination, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

3D Geometry Scanning and Structural Integrity Assessment to Advance Meniscus Allograft Transplantation - Shuchun Sun; Ge Pan; Jichao Zhao; William Michael Pullen; Jian Chen; Haiyang Ma; William C. Bridges; Dustin Mueller; Hai Yao; Shangping Wang (Annals of Biomedical Engineering, 2026)
Purpose Meniscal allograft transplantation can restore joint biomechanics and alleviate symptoms, but its clinical use is limited by the scarcity of size-matched, structurally intact grafts. Current two-dimensional sizing and subjective inspection in tissue banks fail to capture complex three-dimensional geometry and subtle surface defects, highlighting the need for an accurate, reliable, and practical solution for routine donor tissue evaluation. Methods We developed an integrated system combining optical 3D scanning with curvature-based analysis for 3D geometry capture and surface defect detection in meniscus allografts. System performance was validated in terms of scanner accuracy and tissue bank workflow feasibility. Results The system completes each scan within 2 versus ~ 60 min for micro-computed tomography (μCT). It demonstrated μCT-comparable accuracy (mean volume difference: 6.9%; surface deviation: 8.3%). Scanning through phosphate buffer saline (PBS)-immersed transparent bags yielded equivalent accuracy to scanning in air (mean volume difference: 7.2%; surface deviation: 12.5%). The workflow demonstrated high intra- and inter-operator reproducibility. Viability testing revealed PBS-preserved tissues maintained > 94% viability for 20 min, whereas air-exposed tissues dropped below 70% within 10 min. For defect assessment, curvature metrics reliably identified surface wear, longitudinal, and radial defects, with size measurements for wear and longitudinal tears showing equivalence (± 10% margin) to stereomicroscopy. Conclusion This portable system enables accurate and rapid 3D scanning under tissue banking conditions and quantitative surface defect detection. It supports improved graft shape matching and surface defect screening, offering a practical and scalable solution for tissue banks and clinical settings, potentially extendable to other fibrocartilaginous and osteochondral tissues.

Microbial Community Traits and Necromass Dynamics Shape Soil Carbon Accumulation - Wankun Pan; Sheng Tang; Wolfgang Wanek; Zhongkui Luo; Ji Chen; Yuanhe Yang; Tida Ge; Karina A. Marsden; Guopeng Liang; David R. Chadwick; Xinping Chen; Andrew S. Gregory; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) sequestration is vital for food security and climate mitigation. However, its long‐term response to fertilisation remains unclear. Using the 180‐year Broadbalk Experiment (the world's longest‐running fertilisation trial; Rothamsted, UK), combined with 14 C labelling and metagenomics, we identified fundamentally distinct mechanisms of SOC accumulation: a microbially mediated dual pathway under organic fertilisation versus a resource‐limited pathway under inorganic fertilisation. Sustained organic inputs matched inorganic fertilisers in maintaining crop yields while increasing total SOC by 160% (relative to a no‐fertilisation control), far exceeding the 26% gain under inorganic fertilisation. Mechanistically, the continuous supply of labile organic matter provided an energetic surplus, allowing copiotrophic microbial communities with high carbon use efficiency to reduce investment in energy‐intensive enzyme synthesis. This metabolic efficiency facilitated a dual‐pathway expansion, elevating dynamic particulate organic carbon (POC) from 1.4 to 7.5 g kg −1 , while microbial assimilation and necromass accumulation concurrently increased mineral‐associated organic carbon (MAOC) from 6.8 to 21.5 g kg −1 . Conversely, inorganic fertilisation induced an oligotrophic ‘mining’ strategy, in which microorganisms upregulated the degradation of complex organic matter under carbon‐limited conditions, restricting sustained SOC accumulation primarily to the MAOC pool. A global meta‐analysis of field experiments (0–120 years) corroborated these temporal trajectories across diverse soil types, showing that SOC under organic fertilisation increases in a time‐dependent manner, reaching a 77% gain after 80 years (three‐fold greater than under inorganic inputs). Overall, organic fertilisation enhances total SOC via POC and MAOC accumulation, whereas inorganic fertilisation mainly increases MAOC. Long‐term SOC persistence depends not only on carbon inputs, but also on microbial community traits and necromass dynamics, suggesting that aligning nutrient inputs with these biological mechanisms is critical for sustainable carbon sequestration.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Improved U-Net with enhanced spatiotemporal features for Chlorophyll-A concentration prediction in the Zhoushan fishery - Yanling Han; Yizhuo Cai; Ping Ma; Ge Song; Jing Wang; Yun Zhang; Shuhu Yang; Zhonghua Hong (Remote Sensing Applications: Society and Environment, 2026)

Numerical prediction on cavitation characteristics of a marine propeller in oblique flow without and with hull wake effects - Yu Sun; Shengyao Ge; Rui Wu; Wenyu Chen; Han Han; Depeng Ma; Huan Ping (Ocean Engineering, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Development of high-efficient CuFeZnAl-based hydrotalcite catalyst for glycerol hydrogenolysis to 1,2-propanediol - Yuanyuan Ge; Yifan Ma; Zhikuan Lin; Zhihang Lai; Haijun Guo; Bo Chen; Hairong Zhang; Lian Xiong; Xinde Chen; Zhili Li (Journal of Environmental Chemical Engineering, 2026)

The role of co-ion transport in selectrodialysis for mono/divalent cation separation - Xixi Ma; Qian Chen; Lanlan Zhang; Shanshan Liu; Zixuan Wu; Rui Li; Zhiguo Dong; Weiwei Li; Jinfeng He; Chuanrun Li; Liang Ge; Haiyang Yan (Desalination, 2026)

Plasma-induced microcracked stretchable strain sensor array for multifunctional wireless sensing in smart tires - Xiaopeng Du; Xiaona Wang; Shaojie Yuan; Da Chen; Hongen Qu; Xiaoqian Hou; Bing Yao; Chuang Su; Xingyu Ma; Yuhao Cai; Tong Zhang; Ge Song; et al. (Chemical Engineering Journal, 2026)

4-hydroxybenzoic acid-assisted formic acid preserves lignin structure during efficient hemicellulose removal in bamboo biorefinery - Weidong Li; Hanwen Ge; Sen Ma; Lei Liu; Lin Luo; Zihao Qin; Aiyong He; Chao Wang; Xianhai Zeng (Chemical Engineering Journal, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Enabling all-weather interfacial solar evaporation: A latent heat-regulated evaporator with Janus phase change microcapsules - Hailiang Ma; Xinwei Chen; Tiantian Yang; Yuhang Zhang; Linnan Zhang; Fanian Shi; Ge Xu; Jiangtao Fan; Fuxin Liang (Chemical Engineering Journal, 2026)

Molecular identification and genetic diversity of Echinococcus granulosus sensu stricto in livestock from Qinghai lake on the Qinghai-Tibetan plateau - Jun He; Guoyan Zhou; Fan Zhang; Hongrun Ge; Ao Chen; Ru Meng; Zhihong Guo; Yijuan Ma; Yong Fu (Veterinary Research Communications, 2026)

Tenuigenin exerts neuroprotective effects by activating the Nrf2/HO-1 pathway to perform antioxidant activity and inhibit neuronal ferroptosis, preventing epilepsy in immature mice - Qinyun Zhang; Lili Huang; Linling Zhou; Wenfeng Fang; Jie Xu; Siyuan Ma; Chun Ge; Lili Sun; Chen Bu; Weijiang Wu (Molecular & Cellular Toxicology, 2026)

Analysis of the sources of rare earth elements in deep groundwater of the Huainan Coalfield based on the ACPS-MLR model - Jiawen Chen; Tao Jiang; Qingsong Ge; Tianqi Ma; Jiyang Zhao; Liugen Zheng; Xianjie Fu; Shaoneng Du (Environmental Geochemistry and Health, 2026)

Preliminary validation of Tianmu-1 multi-GNSS reflections for snow water equivalent retrieval using a MBF-SWENet model - Yongchao Zhu; Xinyu Ma; Maorong Ge; Xiaohong Zhang; Kefei Zhang; Kegen Yu; Xiaochuan Qu (GPS Solutions, 2026)

LINC01996 suppresses non-small cell lung cancer proliferation and metastasis by orchestrating the miR-12115/CNRIP1/Ras signaling axis - Yi Zhang; Xiaojing Li; Shanshan Liu; Qian Xue; Peize Meng; Xiaolu Ge; Qingnan Zhao; Haitao Ma (Clinical & Experimental Metastasis, 2026)

Tracking the fate of organophosphate esters: from occurrence to risk in the lower Yangtze River water - Yi Zhou; Wenxuan Ma; Wanyu Li; Ge Yin; Jiajun Chang; Yao Xiao; Zhiliang Zhu; Rui Wang; Yanling Qiu (Environmental Science and Pollution Research, 2026)

Recent advances of pretreatments and drying technologies in processing small berries: A comprehensive review - Yan Ge; Qiao-Yi Ma; Shan-Yu Wang; Arun S. Mujumdar; Xiaojun Huang; Hong-Wei Xiao; Zi-Liang Liu; Shaoping Nie (Trends in Food Science & Technology, 2026)

Synergistic Dust Suppression in Fully Mechanized Mining Faces: Integrating Negative Pressure Induction with Supersonic Atomization - Zhuo Jiang; Deji Jing; Heng Ma; Shaocheng Ge; Shuaishuai Ren (Process Safety and Environmental Protection, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

“Alternaria radicina xylanase is required for the occurrence of carrot black rot disease” [Plant Sci. 359 (2025) 112582] - Yingying Wang; Zhimin Wang; Shuo Liu; Jianxin Deng; Ge Wang; Fangfang Ma; Zhilong Bao (Plant Science, 2026)

Enhanced flotation of graphite using Micro-Nano bubbles from the black mass of spent lithium-ion batteries - Xiaoxue Ma; Hao Zhang; Haifeng Wang; Zhuyan Ge; Guangwen Zhang; Ruoxi Zhao; Juan Hao; Shuai Wang; Weining Xie; Yaqun He (Minerals Engineering, 2026)

RNA interference with the selenoprotein M gene inhibits the growth promoting effect by selenium supplementation to silkworm Bombyx mori - Run-Hui Ma; Wen-Jie Ge; Fei Hu; Ting-Ting Hong; Kiran Thakur; Shun-Ming Tang; Zhao-Jun. Wei (Journal of Asia-Pacific Entomology, 2026)

Development of high internal phase emulsion utilizing guar gum and soy lecithin as co-emulsifiers and its impact on the quality of chiffon cake as a fat substitute - Ge Shi; Jiahui Li; Yuqi Ma; Tian Xia; Chaomin Yin; Zhenshun Li (Food Hydrocolloids, 2026)

Bacterial cellulose/tea polyphenol films from tea waste via anaerobic synthesis: A sustainable material for active food preservation - Ge Gao; Haolong Zheng; Shaofang Niu; Yi Wang; Xueqing Zhao; Yucheng Shi; Liyuan Sun; Mingchang Li; Guoqiang Li; Ting Ma (Food Packaging and Shelf Life, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

Engineered M2-sEV encapsulated Se-mRh nanoparticles with Fe2+ chelating capability inhibit ferroptosis for Alzheimer's disease treatment - Chaonan Jing; Kezhen Ge; Dehong Yu; Minghao Chao; Yiming Yin; Junjie Li; Yufan Liu; Guangyu Ma; Rongze Tang; Silin Du; Yingcai Xu; Jiangbo Wang; et al. (Chemical Engineering Journal, 2026)

Chondrocyte-targeting hydrogel loaded with puerarin limits osteoarthritis development by maintaining mitochondrial function - Yunpeng Wan; Kai Shen; Jishi Jiang; Dan li; Mingming Ma; Chengmin Liang; Jie Cao; Bin Liu; Yu Ge; Lei Li; Yaguang Wang; Haiyang Yu (Chemical Engineering Journal, 2026)

Enhanced Remediation of Thiamethoxam Contaminated Soil by Biochar-Immobilized Enterobacter Cloacae TMX-6: Physicochemical Property Regulation and Microbial Response - Yaoyao Cao; Hui Zhang; Jian Chen; Jing Ge; Hongjie Sheng; Qun Wan; Liya Ma; Fayun Feng; Kang Lv; Xiangyang Yu (Water, Air, & Soil Pollution, 2026)

Enhanced abiotic removal of soil monoaromatic hydrocarbons by biochar addition - Huaiyu Ge; Bing Hong; Hao Zhang; Tianyu Hu; Jian Kang; Yinuo Wang; Jingyi Wang; Xiaoya Zheng; Hua Fang; Shutan Ma; Juan Zhao; Ting Wu (Journal of Soils and Sediments, 2026)

Disruption of sphingolipid metabolism triggers lung vascular inflammation and aging-like changes under hypoxia through VDAC1-mediated mitochondrial DNA release - Jin Xu; YiLing Ge; Bin Zhang; SiYuan He; QingLin Cao; PeiJie Li; YingRui Bu; YunGang Bai; Lin Zhang; GuoDong Tan; Jin Ma; ManJiang Xie (Apoptosis, 2026)

Similarity evaluation of seismic datasets by an adversarial validation framework based on deep learning - Shu-na Chen; Zhe-ge Liu; Shu-ying Ma; Jing-Bo Zhai; Ya-juan Xue (Applied Geophysics, 2026)

Screening of quorum Sensing-Dependent strong promoters in Pseudomonas bijieensis 2P24 for metabolic optimization and Recombinant protein production - Jie Li; Hongguang Ma; Na Tai; Yue Fan; Mengxue Nie; Xuanying Tao; Zhilin Wang; Jinxin Wang; Xiangpeng Deng; Cheng Shen; Xuanxuan Chen; Jin Wang; et al. (World Journal of Microbiology and Biotechnology, 2026)

A novel approach to fat reduction: integrating traditional Chinese medicine with a dissolving MNs - Chengzhe Wang; Feifei Liu; Jieqian Ge; Shuang Zhao; Xiaotian Ma; Shuang Yi; Zixiang Ma; Yan Zhao; Jian Zhuang (Drug Delivery and Translational Research, 2026)

Atmospheric wet deposition of silicon in coastal urban area, Southeast China: Variations, determinants, sources, and potential environmental effects - Kunxiang Wang; Jie Zeng; Xiaomin Yang; Qixin Wu; Qing Ma; Shijun Mao; Zixuan Liu; Jingwen Chen; Zhong-Jun Wang; Xin Ge (Urban Climate, 2026)

Insufficient oxidation capacity in the photooxidation of aromatic VOCs results in underestimation of SOA yield - Tianzeng Chen; Jun Liu; Biwu Chu; Yanli Ge; Peng Zhang; Qingxin Ma; Hong He (Science Bulletin, 2026)

Towards sustainable desertification control: A manufacturing method for porosity-controlled upright reed sand fences - Manyu Jin; Yijiang Zheng; Yun Ge; Baojian Ma; Jiangyu Zhang; Rui An; Jianjun Cheng (Journal of Environmental Management, 2026)

Efficient arc-assisted electrothermal regeneration and modification of activated carbon - Xin Nie; Xihao Wang; Xiaojun Ma; Dong Pan; Shiyuan Zheng; Guojia Ge (Journal of Environmental Chemical Engineering, 2026)

Increasing carbon mitigation through enhanced oil recovery - YanJun Lu; QianBo Fan; JinXuan Han; ManPing Yang; JianGuo Ma; DaXin Zhou; HongJian Zhu; Yu Qi; HaoRan Ge (International Journal of Greenhouse Gas Control, 2026)

Multi-species and life-stage patterns of cyanobacterial VOC emissions: Abiotic stress responses and photochemical impacts - Bing Hong; Yinuo Wang; Mengdi Liu; Hao Zhang; Hua Fang; Shutan Ma; Zhijian Fan; Tianyu Hu; Huaiyu Ge; Jian Kang; Jingyi Wang; Xiaoya Zheng; et al. (Environmental Research, 2026)

U-shaped association between outdoor artificial light at night exposure and metabolic syndrome in Chinese youth: Findings from a nationally representative study - Wen-xin Ge; Zhao-huan Gui; Zhi-Yong Zou; Li-qing Yao; Wen-wen Bao; Le-bing Wang; Li-xin Hu; Zheng-ge Jin; Wan-xin Wu; Jun Ma; Ying-Hua Ma; Ya-jun Chen (Environmental Pollution, 2026)

Tailoring hydrophilic channels size in multiblock poly(aryl alkyl) membranes for anion exchange membrane water electrolysis - Xuejiao Dong; Weiwei Luan; Yixiang Ma; Minglong He; Bin Wu; Jibin Miao; Ru Xia; Jiasheng Qian; Guangzu Wang; Qianqian Ge (Desalination, 2026)

Zn2+-DTPMPA chelated cellulose nanocrystal hybrid: synergistic flame-retardant, antibacterial and mechanical reinforcement mechanisms for PA66 composites - Gang Long; Xue Ma; HouYong Yu; Meijin Jin; Xuefei Chen; Xiaohua Wang; Zengwen Yao; Dengteng Ge; Cheng Zeng; Shengjian Wang; Haojie Zang; Yi Jiang (Carbohydrate Polymers, 2026)

Distinct roles of nitrogen and phosphorus availability in preventing soil organic carbon loss in alfalfa-converted cropland - Xu-Long Zhang; Ge Li; Xiao-Peng Shi; Yang-Yang Zhao; Hai-Long Ma; Wen-Feng Cong; Fusuo Zhang; Feng-Min Li (Agriculture, Ecosystems & Environment, 2026)

Hygroscopicity and Cloud Condensation Nucleation Activity of Bromine Salts - Jiali Zhong; Ting Lei; Chao Peng; Wenjun Gu; Nan Ma; Zhe Wang; Maofa Ge; Weigang Wang (Aerosol Science and Engineering, 2026)

3-Methyladenine administration alleviates cognitive and memory dysfunction in attention-deficit/hyperactivity disorder by modulating autophagy - Ge-Ge Lv; Yu-Dong Shan; Jing-Jing Shao; Cao-Yuan Ma; Zhi-Fang Yu; Ji-Zhen Liu; Li-Min Zhang; Wei Zhang (Psychopharmacology, 2026)

Heavy metal pollution in the Jiaodong peninsula: Spatial patterns, elemental mobility, and source-derived ecological impacts - Yang Liu; Xiaoyuan Gu; Jianwei Sun; Haigen Wang; Qingtong Wang; Binghui Feng; Yuhai Chen; Chunhui Ma; Xiangwei Ge; Fengbin Zhu; Shixiong Yang (Marine Pollution Bulletin, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

Comprehensive assessment and policy implications of pesticide packaging waste management in China - Wenjie Shangguan; Can Wang; Qiliang Huang; Zongjie Ren; Hongyi Liu; Chunli Xu; Ge Chen; Dukang Ma; Yongwang Guo; Lidong Cao (Waste Management, 2026)

Millennial rice cultivation shapes depth‑dependent organic carbon mineralization and microbial life strategies in saline paddy soils - Chaoyun Ying; Zhi Ma; Yue Li; Xuechi Rong; Ze Zhang; Guanjun Li; Shuang Wang; Tida Ge; Zhenke Zhu (Soil and Tillage Research, 2026)

Rapid starch degradation characterized by the related gene expression and key enzymes resulted in an optimum comprehensive quality of sugar, acid, and firmness in postharvest apples - Lingyu Qiu; Niu Ye; Yang Zhao; Mengke Cao; Miaomiao Ge; Xiaolin Ren; Yan Tang; Huiling Ma (Postharvest Biology and Technology, 2026)

Retraction notice to “Application of Brachypodium genotypes to the analysis of type II resistance to Fusarium head blight (FHB)” [Plant Sci. 272 (2018) 255–266] - Peisen Su; Xiuxiu Guo; Yanhui Fan; Liang Wang; Guanghui Yu; Wenyang Ge; Lanfei Zhao; Xin Ma; Jiajie Wu; Anfei Li; Hongwei Wang; Lingrang Kong (Plant Science, 2026)

Compact-pol to quad-pol SAR reconstruction via a joint mathematical-physical-constrained multimodal correlation-preserving latent diffusion framework - Zihuan Guo; Hong Zhang; Ji Ge; Xiao-Ming Li; Peifeng Ma; Haoxuan Duan; Lu Xu; Chao Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Aspirin Attenuates the Pathogenesis of Amyotrophic Lateral Sclerosis by Inhibiting the Activities of Microglia in a NF-κB-dependent Complement System-deactivating Mechanism - Tong-Qi Ge; Xiao-Yuan Ma; Pei-Pei Guan; Pu Wang (Molecular Neurobiology, 2026)

MF-GCN: Multimodal Information Fusion Using Incremental Graph Convolutional Network for Ship Behavior Anomaly Detection - Ruixin Ma; Jinhao Zhang; Weizhi Nie; Naiming Ge; Hao Wen; Aoxiang Liu (Journal of Marine Science and Engineering, 2026)
Ship behavior anomaly detection is critical for intelligent perception and early warning in complex inland waterways, where single-source sensing (e.g., AIS-only or vision-only) is often fragile under occlusion, illumination variation, and signal noise. This study proposes MF-GCN, a multimodal (heterogeneous) information fusion framework based on an Incremental Graph Convolutional Network (IGCN) to detect and warn anomalous ship behaviors by jointly modeling AIS, video imagery, LiDAR point clouds, and water level signals. We first extract modality-specific features and enforce temporal–spatial consistency via timestamp and geo-referencing alignment, then construct an evolving graph in which nodes represent multimodal features and edges encode temporal dependency and semantic similarity. MF-GCN integrates a Semantic Clustering-based GCN (S-GCN) to inject historical semantic context and an Attentive Fusion-based GCN (A-GCN) to learn dynamic cross-modal correlations using multi-head attention. Experiments on our constructed real-world datasets demonstrate that MF-GCN achieves accuracies of 93.8%, 93.8%, and 93.3% with F1-scores of 93.6%, 93.6%, and 93.3% for ship deviation warning, bridge-crossing warning, and inter-ship collision warning, respectively, consistently outperforming representative baselines. These results verify the effectiveness of the proposed method for robust multimodal anomaly detection and early warning in inland-waterway scenarios.

Advancing the state of the art of cyclic direct simple shear Testing: Histories, current status, challenges and future trends - Xin Kang; Zi-Rui Ma; Louis Ge (Soil Dynamics and Earthquake Engineering, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

First global XCO2 observations from spaceborne lidar: methodology and initial result - Ge Han; Hongyuan Zhang; Yiyang Huang; Weibiao Chen; Huiqin Mao; Xingying Zhang; Xin Ma; Siwei Li; Haowei Zhang; Jiqiao Liu; Feiyue Mao; Wei Gong (Remote Sensing of Environment, 2025)

Intensification of Weddell Sea deep water in the southern Scotia Sea since ∼0.4 Ma: Mechanistic links to the mid-Brunhes transition - Qiang Zhao; Hongli Wang; Yanpeng Zheng; Kai Liu; Xishuang Li; Chenguang Liu; Yanliang Pei; Qingfeng Hua; Long Ma; Yonghua Wu; Shulan Ge; Fei Cao; et al. (Quaternary Science Reviews, 2025)

Rainfall process-related dissolved organic carbon wet deposition at the southern foot of Qinling Mountain: Implications for atmospheric carbon budget at the boundary area between north and south China - Jie Zeng; Guilin Han; Qixin Wu; Lihong Fu; Qing Ma; Jie Zhang; Xinyi He; Xin Ge (Journal of Hydrology, 2025)

Analysis of the time-varying characteristics of the relationships and influence degrees among dam economic life influencing factors - Heqiang Sun; Wei Ge; Fuheng Ma; Zongkun Li; Yadong Zhang; Menglu Xia; Jianyou Wang; Pieter van Gelder (Journal of Cleaner Production, 2025)

Enhanced humic acid removal via floc-based dynamic membrane for high-salinity water treatment - Jingqiu Sun; Haotong Ge; Yao Xu; Yixuan Ma; Sujie Shan; Songqi Liu; Dapeng Li (Journal of Environmental Chemical Engineering, 2025)

Inconsistent capacity of potential HONO sources to enhance secondary pollutants: Evidence from WRF-Chem modeling - Jingwei Zhang; Haiyan Ran; Yu Qu; Chaofan Lian; Weigang Wang; Yusheng Zhang; Feixue Zheng; Xiaolong Fan; Dawei Lu; Chao Yan; Kaspar R. Daellenbach; Zhiqiang Ma; et al. (Journal of Environmental Sciences, 2025)

A comprehensive story of pea peptides and pea polyphenols: Research status, existing problems, and development trends - Xinyu Sun; Guocong Ma; Dan Hai; Ge Bai; Qi Guo; Tianlin Wang; Xianqing Huang; Lianjun Song (Food Chemistry, 2025)

Effect of electron beam irradiation on physicochemical and protein properties of scallop adductor muscles during cold storage - Zhupeng Zhang; Peng Ge; Chaoqi Han; Fan Zhang; Wenxiu Wang; Ran Suo; Qianyun Ma; Zhenzhen Wang; Jianfeng Sun (Food Chemistry, 2025)

Electrospun Baijiu Prolamin based functional nanofiber: Potential in sustainable food preservation - Runkang Qiu; Ge Wang; Peihua Ma; Huanxiang Luo; Bei Fan; Litao Tong; Lili Wang; Yang Zheng; Liya Liu; Fengzhong Wang (Food Packaging and Shelf Life, 2025)

Tracing copper pollution migration mechanisms in mine tailings pond and surrounding soils using Isotopes: A case study of the Shuimuchong tailings pond, Tongling, China - Mengxi Ren; Qikai Cai; Wenming Pei; Xu Gao; Junchao Ma; Ying Lu; Feng Ge; Xin Liu; Mingzhu Zhang; Keke Xu (Environmental Pollution, 2025)

Synthetic phenolic antioxidants in paddy soils from central China: Contamination characteristics and risk prioritization analysis - Mohan Ma; Meng Gao; Zixiao Zhao; Siyuan Li; Yimeng Si; Liman Wei; Yiting Ge; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; et al. (Environmental Pollution, 2025)

Enhancing vitrification of viable temporomandibular joint discs using DP6 solution - Dustin Mueller; Isabelle McDaniel; Marshall Wilson; Ge Pan; Haiyang Ma; Shangping Wang; Hai Yao (Cryobiology, 2025)

Radiofrequency electromagnetic heating enhanced vitrification of viable large cartilage tissues - Haiyang Ma; Josh Wewerk; Ge Pan; A.J. Riffe; Peng Chen; Yaqian Sun; John M. Alford; Kristi Helke; Girish Srinivas; Hai Yao; David P. Eisenberg; Shangping Wang (Cryobiology, 2025)

Four-month evaluation of vitrified meniscal allograft transplantation in a pig model - Ge Pan; Haiyang Ma; Kristi Helke; William Michael Pullen; Meenakshi Mukherji; Daniel Eldridge; Peng Chen; Dustin Mueller; Shuchun Sun; Yongren Wua; Tong Ye; Hai Yao; et al. (Cryobiology, 2025)

Hierarchical hollow P-doped ZIF-8/MXene aerogel composites for phase change materials integrating shape stability, thermal energy storage, solar-thermal conversion and flame retardancy - Huiqi Gao; Haiyun Ma; Jinjin Cui; Xusheng Ge; Jiajun Tan; Jianzhong Xu (Chemical Engineering Journal, 2025)

CuFe2O4@T-COF nanosphere-mediated biosensing platform based on DNA walker signal amplification strategy for ultrasensitive HPV detection - Zhen Yu; Yan Zhang; Dongquan Leng; Tingting Wu; Si-Jia Ge; Dawei Fan; Hongmin Ma; Yu Du; Qin Wei (Chemical Engineering Journal, 2025)

Specific microenvironment modulation around Zr clusters via linker engineering in metal-organic frameworks for enhanced catalytic transfer hydrogenation - Mingwei Ma; Xuesong Wu; Xin Wang; Jing Sun; Ge Tian; Hui Liu; Zhongmin Su (Chemical Engineering Journal, 2025)

The interaction between Ir nanocrystallites and Ni2P nanosheets regulates the adsorption energetics of intermediates for boosting ethanol electrolysis - Xiaoyu Zhang; Ruiting Chen; Ge Ma; Xin Wang; Yu Chen; Zhongwei Chen (Chemical Engineering Journal, 2025)

Asymmetric CALF-20/PIM-1 MMMs with anisotropic properties for efficient carbon capture - Yuchao Ma; Wei Zhao; Dacheng Zhang; Kaihua Li; Qian Zhang; Ge Wang; Zhanfeng Zhao; Long Jiao; Leixin Yang; Ningning Gao; Bowen Cheng (Chemical Engineering Journal, 2025)

Cell-supporting cytoskeletons and phagocytic acquisition of compatible solutes emerge as common strategies for high-salt adaptation in different ciliates - Fengchao Li; Wenying Zhang; Shuai Luo; Ning Ma; Jing Zhang; Weiwei Qin; Che Hu; Xinxin Gao; Yuan Xiao; Chuanqi Jiang; Xiaocui Chai; Qiukun Wang; et al. (Science China Life Sciences, 2025)

Retraction Note to: MiR-126 Regulates the ERK Pathway via Targeting KRAS to Inhibit the Glioma Cell Proliferation and Invasion - Yang Li; Yunqian Li; Pengfei Ge; Chengyuan Ma (Molecular Neurobiology, 2025)

Prevalence and molecular spectrum of thalassemia in infertile population among different ethnic groups in Hainan Province, China - Yongle Zhang; Jinyu Kang; Wenye Sun; Fei Sun; Ge Gao; Junhong Chen; Qi Li; Qiuling Jie; Yanlin Ma (Molecular Genetics and Genomics, 2025)

Limitation of the Application of Heat Tracer in Investigating Groundwater and River Interactions under Dynamic Flow Conditions - Mengyan Ge; Rui Ma; Ziyong Sun (Journal of Earth Science, 2025)

Straw-mediated CH4 production via distinct methanogenic pathways in two paddy soils - Wanyu Shen; Yang Ji; Zhongjun Jia; Qiong Huang; Xiaoli Zhu; Jing Ma; Zhenke Zhu; Tida Ge; Guangbin Zhang; Hua Xu (Applied Soil Ecology, 2025)

Isolation and Identification of Metanophrys sinensis from Shrimps (Litopenaeus vannamei) and Screening of Chinese Herbal Medicines for Its Control - Mingfeng Ge; Yifan Xu; Juan Feng; Zheng Liang; Hao Cui; Xinxin Jiang; Jianping Wang; Shengwei Xu; Rongrong Ma (Fishes, 2025)
The parasitic disease scuticociliatosis poses significant economic losses to shrimp culture. In this study, an unidentified species of ciliates was discovered in Litopenaeus vannamei. Morphological and molecular analyses were conducted to identify the parasite species, while a reinfection experiment was performed to assess its virulence towards L. vannamei. Simultaneously, Chinese herbal medicine was assessed for potential prevention and control of this pathogen. The results revealed that the SSU rDNA (93.87%), LSU rDNA (98.20%), and ITS1-5.8S-ITS2 rDNA (87.10%) genes exhibited high homology with Metanophrys sinensis, suggesting its classification within the genus Metanophry sp. The reinfection experiment demonstrated median lethal dosages of 6638 individuals/mL at 24 h and 4658 individuals/mL at 48 h for this ciliate on the host L.vannamei. In terms of drug control, we conducted a screening of 23 Chinese herbal extracts through in vivo injection trials and observed that Mume fructus extract exhibits potent biocidal activity. Specifically, the M. fructus extract solution with a final concentration of 5 mg/mL (0.5% v/v) eliminated all ciliates within 3 h. In conclusion, this study identified the ciliate parasite as Metanophrys sinensis and demonstrated its virulence to Litopenaeus vannamei. Mume fructus extract was found to effectively control the parasite, offering potential for managing scuticociliatosis in shrimp culture.

Selective interaction of BmNPV Bm65 with host proteins before and after ultraviolet radiation - Yutong Liu; Jiayin Huang; Guohui Li; Feifei Zhu; Qian Yu; Lindan Sun; Huiqing Chen; Liang Chen; Qi Ge; Shangshang Ma; Xiaoyong Liu; Keping Chen; et al. (Pesticide Biochemistry and Physiology, 2025)

Downscaling multilayer soil moisture using parameterized depth profiles associated with environmental factors - Mo Zhang; Yong Ge; Yuxin Ma; Yan Jin; Yingying Chen; Shaomin Liu (Journal of Hydrology, 2025)

Efficient degradation of polylactic acid plastics by a novel fungal strain Arthrinium phaeospermum and mechanistic insights - Zhiying Xu; Jie Yang; You Ge; Zeguo Fang; Luyang Ma; Yujie Duan; Zhenglin Xia; Tong Li; Jiali Liu; Xiaorong Qin; Fei Li (Journal of Hazardous Materials, 2025)

Hydrogen and methane production from hydrothermal wastewater via two-stage anaerobic fermentation: Impact of typical toxic components in wastewater - Ruikun Wang; Gaoke Song; Yehong Zhang; Zherui Ma; Junhui Hu; Zhenghui Zhao; Qianqian Yin; Lichao Ge (Journal of Environmental Management, 2025)

Cross-modal 2D-3D feature matching: simultaneous local feature description and detection across images and point clouds - Wei Ma; Yucheng Huang; Shengjun Tang; Xianwei Zheng; Zhen Dong; Liang Ge; Jianping Pan; Qingquan Li; Bing Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Preparation of cinnamon essential oil-micelles/blueberry anthocyanins-loaded PVA bifunctional electrospunning nanofibrous film for maintaining and monitoring shrimp freshness - Siyu Zhang; Yu Ma; Xinyu Wang; Xiaoyu Zhou; Yong Fang; Wen Shen; Xuemei Ge (Food Chemistry, 2025)

Optimizing water management in water-saving and drought-resistant rice cultivation reduces methane emissions with enhanced net economic benefits - Keda Jin; Yuting Yang; Kaifu Song; Jing Ma; Yujiao Dong; Zhenke Zhu; Tida Ge; Shihua Lv; Guangbin Zhang; Hua Xu (Field Crops Research, 2025)

Nitrogen transformation in the crop-soil system determines the exacerbation of yield-scaled N2O emissions from rice paddies under climate change - Yuanyuan Wang; Wei Huang; Ziqi Xu; Zhenghua Hu; Tingwu Liu; Guihua Lu; Kezhi Zheng; Dan Dong; Yonggang Xu; Shuqi He; Gecong Ma; Ting Li; et al. (Field Crops Research, 2025)

Association of ambient fine particulate matter (PM2.5) and its constituents with risk of pulmonary nodules in a lung cancer screening project - Xinyuan Ge; Ci Song; Chen Zhu; Yang Ding; Maojie Liu; Juan Yang; Chan Tian; Jiahao Zhang; Lili Wu; Lingying Zhu; Lei Shi; Xiangdong Cheng; et al. (Environmental Research, 2025)

Agricultural plastic Legacy in river Sediments: Abundance, oxidation, and occurrence characteristics of microplastics across rural China - Ge Ma; Kuangjia Li; Wei Zou; Rui Xin; Xiaohan Zhang; Jiaojiao Feng; Zheng Chen; Yinan Yang; Xiaomeng Lou; Kai Zhang; Fengxia Yang (Environmental Pollution, 2025)

High-performance large-area ITO-free organic photovoltaics under indoor illumination enabled by a dual-interfacial engineering strategy - Jiaxin Gao; Zheng Li; Cuifen Zhang; Fangliang Dong; Zheng Tang; Ming Wang; Dengteng Ge; Zaifei Ma (Chemical Engineering Journal, 2025)

MoO3-MoS2 with abundant oxygen vacancies for real-time seafood quality assessment - Guochen Qi; Shuwei Ren; Jingfang Ji; Hao Gao; Zhichuang Ma; Sufeng Fan; Pan Liu; Jingmin Ge (Chemical Engineering Journal, 2025)

Bimetallic copper-bismuth microtubular electrodes with tunable interfaces for efficient electrochemical reduction of CO2 to formate - Beibei Ma; Hesamoddin Rabiee; Guoliang Chen; Yizhu Kuang; Tianjiu Zhu; Penghui Yan; Lei Ge; Zhonghua Zhu (Chemical Engineering Journal, 2025)

Paraquat induced neuro-immunotoxicity: Dysregulated microglial antigen processing and mitochondrial activated mechanisms - Ge Shi; Kaidong Wang; Qi Liu; Chenyang Wu; Qianrong Zhang; Yuan Ma; Ai Qi; Min Huang (Chemico-Biological Interactions, 2025)

Exploring nonlinear and interaction effects of macro- and micro-environmental factors on age-friendliness of streets through explainable machine learning - Yafei Guo; Yipeng Ge; Yueshan Ma; Qizheng Gan; Shubo Chen; Yang Liu; Yalong Mao (Building and Environment, 2025)

Automatic quantification, grading and five-year prediction of myopic fundus tessellation: a multi-center, longitudinal deep learning study - Wen-Da Zhou; Li Dong; Wen-Xue Li; Li-Jian Fang; Tong Ma; Lie Ju; Zhao-Hui Wang; Yuan Luo; Wanli Miles Zhang; Xian-Gang Chang; Zong-Yuan Ge; Jost. B. Jonas; et al. (Science China Life Sciences, 2025)

Potential effects of fertilization strategies on greenhouse gas emissions from bamboo forest soils - Ziliang Zhao; Dejin Dong; Yujie Zhao; Xuekun Cheng; Zixiang Weng; Qingyu Liu; Zhuonan Lou; Ke Wang; Ailing Ma; Wenting Ge; Hongyan Zhang; Yongjun Shi; et al. (Plant and Soil, 2025)

Mechanisms of thermal, acid, desiccation and osmotic tolerance of Cronobacter spp. - Yanfei Yan; Mengyuan Cao; Jiaqi Ma; Jia Suo; Xiaobao Bai; Wupeng Ge; Xin Lü; Qiang Zhang; Jia Chen; Shenghui Cui; Baowei Yang (Critical Reviews in Food Science and Nutrition, 2025)

Nitrogen-containing pollutant records in rainfall from the north-south boundary area in China: Compositions, variations, and sources - Xinyi He; Jie Zeng; Qixin Wu; Qing Ma; Jie Zhang; Lihong Fu; Xin Ge (Process Safety and Environmental Protection, 2025)

Alternaria radicina xylanase is required for the occurrence of carrot black rot disease - Yingying Wang; Zhimin Wang; Shuo Liu; Jianxin Deng; Ge Wang; Fangfang Ma; Zhilong Bao (Plant Science, 2025)

Morphology and community structure characteristics of aerobic granular sludge: A review - Peixin Liu; Yue Yang; Ma Ge; Qinghui Luo; Bin Cui; Han Cui; Tingting Cao; Dandan Zhou (Journal of Environmental Chemical Engineering, 2025)

Identification of immunomodulatory peptides from crocodile head protein hydrolysates: Targeted screening and immunomodulatory activity by activating NF-κB signaling pathway - Ge Xu; Wenhao Ma; Wenzhu Zhao; Zhipeng Yu (Food Research International, 2025)

Preparation of bacterial cellulose-aloe emodin-vanillin eco-friendly composite film for salmon preservation: Antioxidant, antibacterial, and pH-Responsive color change - Xueqing Zhao; Mingbo Yang; Haolong Zheng; Zhiqing Zhao; Mengyue Duan; Ge Gao; Ting Ma; Guoqiang Li (Food Hydrocolloids, 2025)

Effects of microencapsulated antimicrobial peptides on the growth, immunity, infection resistance, gut microbiota, and gene transcriptome in Manila clam (Ruditapes philippinarum) larvae - Yang Zhang; Kai Liao; Yuxiang Zhu; Yang Liu; Hailong Huang; Haibo Zhou; Deishui Chen; Bin Ma; Hui Ge; Weiwei Zhang; Jilin Xu (Fish & Shellfish Immunology, 2025)

An ingenious structural design of NiCu-MOF bar-like nanosheet array: harnessing synergistic effects to attain exceptional ammonia oxidation performance - Guang-Lan Li; Yu-Hui Shi; Ri-Yang Huang; Tian-Ge Ma; Qian Zhuo; Ling Xu; Fei Jiang; Yu-Kun Zhai; Yong-Hou Xiao; Hong-Jiang Li; Yang Yan; Yun Zhao (Chemical Engineering Journal, 2025)

Sources and potential health indicators in urban aerosols revealed by gas chromatography-mass spectrometry combined with nitrogen chemiluminescence detector: evidence from a megacity (Tianjin) of China - Jingying Ma; Yulin Qi; Yufu Han; Jinfeng Ge; Ling Wen; Xiaoli Fu; Wei Hu; Zongbo Shi; Dietrich A. Volmer; Pingqing Fu (Atmospheric Environment, 2025)

Health impacts and drivers of long-term ozone and nitrogen dioxide exposure in urban China - Zhaoli Yang; Fangliang Li; Rongmin Ye; Huiping Ge; Hongyu Li; Shulian Zhang; Jiaxin Wang; Yuan Zhao; Hong Gao; Tao Huang; Jianmin Ma (Atmospheric Pollution Research, 2025)

A novel method for predicting debris flow hazard: a multi-strategy fusion approach based on the light gradient boosting machine framework - Tianlong Wang; Qi Ge; Tianxing Ma; Hao Chen; Rui Luo; Xu Wang; Keying Zhang; Zhaowei Chu; Xiaohui Ni; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Proteomic analysis reveals novel insights into astaxanthin synthesis in Haematococcus pluvialis - Zhaokun Wang; Haiyan Ma; Jiao Zhan; Li Yuan; Mingkun Yang; Feng Ge (Algal Research, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Promoting the butterfly transformation of residual sludge: Specific adsorption of heavy metals and in-situ cultivation of granular sludge - Tingting Cao; Qinghui Luo; Peixin Liu; Ma Ge; Liang Liu; Xiyang Fei; Yuanhang Zhao; Bin Cui; Han Cui; Dandan Zhou (Journal of Hazardous Materials, 2025)

Aeration-assisted three-dimensional granular boron-doped diamond electrochemical system for high-efficiency organic pollutant degradation: synergistic reactive oxygen species generation and enhanced mass transfer - Hao Wu; Haoqi Liang; Zejun Deng; Luan Jiang; Rongkai Ge; Yijia Wang; Kechao Zhou; Quiping Wei; Li Ma (Journal of Cleaner Production, 2025)

Growth-promoting bacterium Enterobacter sp. CS8-gfp triggers jasmonate signaling pathway for atrazine and thiamethoxam degradation in rice (Oryza sativa L.) - Li Ya Ma; Qun Wan; Jing Ge; Yong Li; Fayun Feng; Mei Li; Jinjin Cheng; Jian Chen; Ya Wang; Yaoyao Cao; Chenye Yang; Xiangyang Yu (Journal of Cleaner Production, 2025)

Evaluation of the degree of blending between virgin and aged asphalt in rejuvenated asphalt mixture based on multilayer inclusion theory - Jinguo Ge; Huanan Yu; Guoping Qian; Taojun Li; Yixiong Zhong; Ruochen Lei; Liang Zhou; Yuetan Ma; Tengfei Nian (Journal of Cleaner Production, 2025)

Preparation of the co-delivery system polymersome for blueberry anthocyanins/lutein and study on its antioxidant and transdermal absorption properties - Yu Ma; Siyu Zhang; Xiaoyu Zhou; Xinyu Wang; Wen Shen; Xuemei Ge (Food Bioscience, 2025)

Alkyl chain engineering in β-linked dimer acceptors: Balancing crystallinity and phase separation for high-performance organic photovoltaics - Yun Li; Jiawei Fu; Hang Jiang; Zhongwei Ge; Haisheng Ma; Yinuo Yang; Xiaobo Sun; Shouchun Yin (Chemical Engineering Journal, 2025)

Engineering covalent surface donor-acceptor interactions via Schiff base reaction for enhanced photocatalytic CO2 reduction - Jingyu Sun; Zhuowen Jiang; Guangying Nie; Lie Ding; Peiyan Wang; Chengsheng Ge; Shuaishuai Ma (Chemical Engineering Journal, 2025)

Magnetic characteristics of sediments in the northern Yangtze River delta since MIS3 and their responses to palaeoenvironmental changes - Guiye Zhang; Longsheng Wang; Xiaohui Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu; Chao Zhan; Qing Wang (CATENA, 2025)

Dissolved organic matter derived from long-term photodegradation of plastics alters microbial methane conversion in mangrove sediments - Minmin Wang; Leiqian Ma; Derong Zhang; Fan Yang; Xing Yang; Bin Wang; Xue Li; Chengjun Ge; Jiwei Luo; Ying Zhang (Bioresource Technology, 2025)

Relative pollen productivity estimates for the dominant plant taxa in the Hoh Xil region of the Qinghai-Tibet Plateau - Ying Wang; Yue Li; Linyuan Ma; Hanfei You; Ruchun Zhang; Changhong Liu; Yutao Zuo; Rongrong Wang; Yawen Ge; Yuecong Li; Qinghai Xu (Vegetation History and Archaeobotany, 2025)

Prolonged nitrate depletion delayed marine ecosystem recovery after the end-Permian mass extinction - Youren Ma; Zhaoxia Ge; Jiaheng Shen (Science China Earth Sciences, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Host genotype-driven assembly of bacterial communities in the rice root microdomains - Yi Wan; Zhi Ma; Jiaping Lang; Xuebin Xu; Caihong Shao; Jianping Chen; Tida Ge; Haoqing Zhang (Soil Ecology Letters, 2025)

Two undescribed compounds from Aspergillus Niger , an endophytic fungus isolated from Camellia flavida - Siyuan Ma; Li Ge; Hongyu Lu; Jianhua Yan; Kedi Yang (Natural Product Research, 2025)

Exploration of thermo-fluid-heat transfer evolution in salt cavern compressed air energy storage system under high-frequency injection and production conditions - Jun Huang; Xinbo Ge; Hongling Ma; Xilin Shi; Yinping Li; Chunhe Yang (Tunnelling and Underground Space Technology, 2025)

Atrazine exposure induces TDP-43 protein translocation: A potential mechanism for prefrontal cortical neurodegeneration induced by environmental pollutants - Yuan Ma; Kaidong Wang; Yuxuan Jiao; Yujing Li; Rong Hu; Yang Li; Ge Shi; Min Huang (Toxicology, 2025)

Long-term manure and mineral fertilisation drive distinct pathways of soil organic nitrogen decomposition: Insights from a 180-year-old study - Wankun Pan; Sheng Tang; Jingjie Zhou; Wolfgang Wanek; Andrew S. Gregory; Tida Ge; Karina A. Marsden; David R. Chadwick; Yongchao Liang; Lianghuan Wu; Qingxu Ma; Davey L. Jones (Soil Biology and Biochemistry, 2025)

Sparingly-soluble CaCO3 promotes plant growth and arsenic accumulation in As-hyperaccumulator Pteris vittata: Oxidative stress and gene expression in As metabolisms - Yu-Fei Yang; Shu-Fen Xiao; Chun-Yan Hu; Qian-Yu Zhou; Chen-Jing Liu; Song-Ge Deng; Lena Q. Ma (Journal of Hazardous Materials, 2025)

A review of microbial degradation of perfluorinated and polyfluoroalkyl substances (PFAS) during waste biotransformation processes: influencing factors and alleviation measures - Yuanming Huang; Jialun Hu; Jia Zheng; Zhihui Bai; Hao Chen; Xiaopeng Ge; Tang Tang; Yao Zhang; Yi Ma; Huibo Luo; Lei Li; Xinqiang Ning (Environmental Research, 2025)

Sealing performance evaluation and analysis of the first salt caverns gas storage facility in the southwest plateau of China - Jun Huang; Xinbo Ge; Hongling Ma; Yinping Li; Xilin Shi; Zhixin Wang (Engineering Geology, 2025)

Accelerated vanadium (IV)/(V) redox cycle and hydroxyl radical generation by hydroxylamine in peroxymonosulfate activation: from synthetic vanadium oxides to natural minerals - Ge Li; Yujie Cheng; Yiqun Chen; Zizheng Liu; Jun Ma; Pengchao Xie (Chemical Engineering Journal, 2025)

Human Health Impact from Nonferrous Metal Mining: Exposure Risk with Hair as Biomarkers and the Associated Influencing Factors - Xueming Zheng; Feng He; Xiaoping Li; He Shen; Danqian Shi; Qishang Zhou; Shuang Zhang; Tunyang Geng; Yueheng Jiang; Pengyuan Jin; Xuelian Kui; Huimin Liu; et al. (Exposure and Health, 2025)

Synergistic genetic module engineering for optimized eicosapentaenoic acid production in Nannochloropsis oceanica - Jie Zheng; Ye Liu; Feng Ge; Cheng-Cai Zhang; Danxiang Han; Haiyan Ma (Algal Research, 2025)

Flower strips increase natural pest control of peanut aphids, thereby enhancing crop yield - Qian Ju; Xiping Wei; Katherine Berthon; Qun Zhang; Wenqian Ma; Mingjing Qu; Feng Ge; Lynn V. Dicks (Agriculture, Ecosystems & Environment, 2025)

A hybrid estimation of distribution algorithm for agile earth observing satellite task scheduling problem - Chunchun Ma; Panxing Huang; Xiaoze Liu; Chu-ge Wu; Rui Xu (Swarm and Evolutionary Computation, 2025)

Experimental study on the hydrodynamic behavior of a floating Fishery–Photovoltaic complementary structure - Sida Xie; Chao Ma; Zhan Zhang; Yun-Peng Zhao; Jia-Qing Shu; Xiao-Feng Ge; Yan-Qian Sun (Ocean Engineering, 2025)

Rutin alleviates heat stress induced hepatic abnormal lipid metabolism of broilers via improving antioxidant capacity to maintain mitochondrial homeostasis - Longfei Ma; Huijuan Liu; Zhongyu Ge; Bing Bai; Jianle Zhao; Shun Chen; Binbin Zhou; Jiaqi Zhang; Tian Wang; Chao Wang (Journal of Thermal Biology, 2025)

Quorum sensing luxI/R genes enhances cadmium detoxification in Aeromonas by up-regulating EPS production and cadmium resistance genes - Jiale Chen; Qingnan Yu; Tao Zhang; Yaonan Ma; Menghan Xiao; Chunhua Zhang; Ying Ge (Journal of Hazardous Materials, 2025)

Potentially toxic elements in sediments of China's Shihe River: Urban-agricultural impact assessment and source apportionment - Kai Zhang; Ge Ma; Zheng Chen; Jilu Wang; Xiaomeng Lou; Yinan Yang; Jiaojiao Feng; Fengxia Yang; Kuangjia Li; Chenxuan Shang; Rui Xin; Xiangmin Zhang (Journal of Contaminant Hydrology, 2025)

Regional disparities in carbon tax effectiveness: A multi-regional CGE analysis of provincial production and freight emissions in China - Xian Wang; Junfeng Liu; Ying Liu; Xiurong Hu; Huihuang Wu; Yuhan Zhou; Wendong Ge; Jianmin Ma; Shu Tao (Environmental Impact Assessment Review, 2025)

Versatile albumin as a booster to optimize the excited state energy redistribution in photosensitizers enabling fluorescence imaging-guided photodynamic therapy - Ting Wang; Lixin Ma; Yingcui Bu; Xinjie Xu; Xuan Zhao; Yingyong Ni; Qitao Zhao; Zhou Lu; Fei Ge; Hongping Zhou (Chemical Engineering Journal, 2025)

High-resolution VOCs measurements and photochemical impact analysis for typical solid waste base in summer - Shuwei Zhang; Song Gao; Pengjie Yuan; Zekai Yang; Yajing Ma; Xiang Ge; Lipeng Liu; Zheng Jiao; Tronganh Nguyen (Air Quality, Atmosphere & Health, 2025)

Restoration-oriented multi-tiered framework for ecosystem degradation diagnosis: a coastal bay case study - Dian Zhang; Weiwei Yu; Bin Chen; Huamei Huang; Jianji Liao; Lingyang Feng; Guangcheng Chen; Zhiyuan Ma; Qinhua Fang; Shunyang Chen; Bin Xie; Zhiyi Kan; et al. (Frontiers in Marine Science, 2025)
Introduction Understanding ecosystem degradation and estimating its extent are essential to enact decision-making policies in biodiversity conservation, ecosystem restoration, and management. Although many approaches have been proposed to identify the degradation status of an ecosystem, the heavy data burden required lacks targeted degradation information to inform such decision-making restoration policies. Methods This study proposes a multi-tiered decision-making framework to diagnose ecosystem degradation based on the most common restoration models that link degradation to restoration. The degradation diagnosis process can be executed step-by-step (i.e., in a physical to chemical to biological order). This study selected a limited number of coastal bay indicators from each layer, and a conceptual ecosystem response profile was applied to guide their degradation criteria settings: stepped for physical indicators, hump-shaped for chemical indicators, and smooth for biological indicators. Daya Bay in China was selected for this case study. Results In total, 62% of the bay has degraded by varying degrees, including completely degraded, heavily degraded, moderately degraded, and slightly degraded percentages were 4.64%, 3.78%, 15.16%, and 38.43%, respectively. Moreover, there has been a gradual but continuous spatial change in its degradation degree from north to south and from west to east. Discussion Results from this study can be used to identify and prioritize restoration processes. Human-assisted restoration efforts should prioritize its moderately degraded western section and its heavily degraded coastal areas along Yaling Bay and Fanhe Harbour. Our framework provides an efficient, science-based, and novel approach to diagnose the degradation status of the coast, particularly in the absence of long-term observational data, which can be effectively applied to any region or ecosystem.

YOLO-CWD: A novel model for crop and weed detection based on improved YOLOv8 - Chaoran Ma; Ge Chi; Xueping Ju; Junqiang Zhang; Changxiang Yan (Crop Protection, 2025)

Two-phase conversion process of ethylene glycol and the mechanism of synergistic extraction of lithium in subcritical water system - Yayun Ma; Bei Wang; Xiaojian Liu; Xiangyang Zhou; Juan Yang; Jingjing Tang; Yaguang Zhang; Junqiang Zhu; Zhongbing Wang; Fanyun Su; Jinyue Ge (Waste Management, 2025)

Increasing importance of regional emission controls for further reduction of PM2.5 in Beijing - Lingkai Dong; Weili Lin; Zhiqiang Ma; Wei Wang; Lei Kong; Xiaobin Xu; Oliver Wild; Yuanlin Wang; Baozhu Ge; Zifa Wang (Urban Climate, 2025)

Bromine radicals and hydroxyl radicals efficiently degrade emerging organic contaminants in the UVA photolysis of bromine process - Tao Yang; Xiujuan Kong; Ge Zeng; Maoju Jiang; Linqian An; Peng Su; Qixiao Lv; Jun Ma; Juan Li (Journal of Environmental Chemical Engineering, 2025)

Catalytic ozonation of coal chemical wastewater using AlOOH-immobilized phosphotungstic acid - Mingzhu Chen; Tengfei Shao; Gangqiang Zhang; Weijun Zhen; Chunmei Ma; Pengtao Sun; Qing Ge; Yusheng Zhou; Buning Chen (Journal of Environmental Chemical Engineering, 2025)

Valorization of crocodile head for anti-inflammatory peptides: In silico screening and cellular validation - Yongyong Hu; Wenhao Ma; Ge Xu; Wenzhu Zhao; Zhipeng Yu (Food Research International, 2025)

Controlled hydrolysis and EGCG conjugation enhance the ADH/ALDH activation activity of chia seed meal protein hydrolysates: Fabrication and structural characterization - Jinghui Chen; Weiben Ge; Yu Wang; Zan Hu; Wenping Lv; Chaoyang Ma; Hongxin Wang (Food Chemistry, 2025)

Edible starch-based films modified by fruit and vegetable juices: Preparation, performance evaluation and seasoning bag design - Xinyu Sun; Guocong Ma; Xiaoling Tian; Dan Hai; Yan Ma; Ge Bai; Lianjun Song; Qinghua Yang; Xianqing Huang (Food Packaging and Shelf Life, 2025)

Construction of a toxicity pathway from activation of the TLR4/NF-κB/NLRP3 axis to Parkinson's disease-like non-motor symptoms in mice - Kaidong Wang; Ge Shi; Yonghang Li; Qi Liu; Qianrong Zhang; Chenyang Wu; Yuxuan Jiao; Yuan Ma; Ai Qi; Min Huang (Environmental Toxicology and Pharmacology, 2025)

Development of Brassica rapa-nigra monosomic alien addition lines: cytology, genetics, and morphology - Pengfei Li; Haiyan Wu; Shizhen Guo; Shunlin Wang; Mimi Zhang; Mengyang Liu; Wei Ma; Jianjun Zhao; Chen Tan; Cheng Cui; Xianhong Ge; Zaiyun Li (Theoretical and Applied Genetics, 2025)

Paleoclimate contributes to soil carbon storage in subtropical shrublands - Jielin Ge; Boyu Ma; Gaoming Xiong; Changming Zhao; Wenting Xu; Yang Wang; Jiaxiang Li; Zongqiang Xie (Agricultural and Forest Meteorology, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Arsenic and metabolic diseases: New insights from mesenchymal stem cells - Yuxin Hu; Jialin He; Yue Ma; Lili Ge; Bin Lou; Xin Fang; Huihui Wang; Yuanyuan Xu (Toxicology and Applied Pharmacology, 2025)

Global prevalence of Porcine Astrovirus: A systematic review and meta-analysis - Xiaoyu Ge; Yize Li; Feipeng Zhao; Xin’ao Ma; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2025)

Lead seasonality: Affect children’s blood lead levels and implication for lead exposure prevention - Jie Dong; Xiaoping Li; Yu Zhang; Xueming Zheng; Shuang Zhang; Qishang Zhou; Feng He; Danqian Shi; Yueheng Jiang; He Shen; Xu Zhang; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

Synergistic surfactant cleaning-bioaugmentation strategy enables deep remediation of heavily petroleum-contaminated soils: Field validation and microbial mechanism - Zhineng Wu; Linhao Kang; Quanli Man; Yaduo Yang; Jiao Wang; Hongjiang Ge; Xiaodong Ma (International Biodeterioration & Biodegradation, 2025)

Effect of LacBS/LacBP on biogenic amines degradation, physicochemical property, and flavor of Huangjiu - Hongpeng He; Yanyan Ge; Xiangyang Ma; Jiahui Wang; Wei Qi; Yihan Liu (Food Chemistry, 2025)

Non-flammable phosphate-ester-based electrolyte with high concentration for high safety potassium-based anode-free dual ion battery - Ge Zhang; Sunfa Wang; Kanghou Ma; Caiyue Sun; Chen Wang; Fangshuo Zhou; Xinyue Zhao; Xiqiang Huang; Zhiguo Liu; Ningning Wu; Yaohui Zhang (Chemical Engineering Journal, 2025)

Construction of site-specific immobilized lipase in bio-inspired “rigid and flexible” composite PVIm/ZIF-8 for long-cycle biodiesel synthesis from waste cooking oil - Qian Wang; Xinyuan Zheng; Meiling Ge; Rong Chen; Fangpei Ma; Jianming Pan; Fu Yang (Chemical Engineering Journal, 2025)

Amplifying population exposure of extreme precipitation across Yellow River Basin, China at 1.5° C, 2.0° C and 3.0° C global warming - Rui Yao; Zice Ma; Peng Sun; Chenhao Ge (Natural Hazards, 2025)

Associations between air pollutants and emergency ambulance dispatches for all-cause and nervous system disease in China Qingdao: a time-stratified case-crossover study - Yang Yu; Bingling Wang; Lu Pan; Nan Ge; Xiaocheng Gu; Yuan Fang; Hua Zhang; Jianjun Zhang; Yan Ma; Haiping Duan (Environmental Monitoring and Assessment, 2025)

Mesua ferrea L. extract inhibits cell invasion and tumor growth in breast cancer in vitro and in vivo - Zhi-Ying Liu; Ge Ge; Shuang-Shuang Ma; Xi-Ya Chen; Yue Cong; Shu-Yun Wang; Ya-Ping Guo (Tissue and Cell, 2025)

Revisiting urban heat island effects in China: Multi-satellite evidence from the ESA-CCI land surface temperature product - Xing Li; Xiao Li; Hedi Ma; Juan Zhou; Fei Ge; Wanxin Zhang; Yan Yan; Yijing Zhou (Sustainable Cities and Society, 2025)

Corrigendum to “Application of Brachypodium genotypes to the analysis of type II resistance to Fusarium head blight (FHB)” [Plant Sci. 272 (2018) 255–266] - Peisen Su; Xiuxiu Guo; Yanhui Fan; Liang Wang; Guanghui Yu; Wenyang Ge; Lanfei Zhao; Xin Ma; Jiajie Wu; Anfei Li; Hongwei Wang; Lingrang Kong (Plant Science, 2025)

Estimation and evaluation of usage, loss and ecological risk of neonicotinoid pesticides in a large catchment - Xian-Kun Ma; Qian-Qian Zhang; Feng-Jiao Peng; Liang-Li Dong; Jin-Ge Zhang; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Puerarin modulates the P62-Keap1-NRF2 pathway and enhances CA7 function to inhibit ferroptosis in ethanol-induced gastric mucosal injury - Xinran Liu; Jiayi Ge; Ximing Yang; Zhihui Chang; Xiaoyu Ma; Shuzhen Cheng; Ming Du (Food Bioscience, 2025)

Hollow and mesoporous nanospheres enable rapid ion migration on the zinc anode surface - Shunshun Jia; Haifeng Bian; Qing Zhou; Biao Wang; Ge Xue; Hao Wu; Fengqi Li; Zhonglu Hu; Yujie Ma; Jian Gu; Shaochun Tang; Xiangkang Meng (Chemical Engineering Journal, 2025)

Confining asymmetric water hydrogen-bond network to boost photoreduction of CO2 to formaldehyde - Minzhi Ma; Shuaikang Zhang; Mengge Jia; Tongqing Li; Jinshuo Chen; Shichu Zhao; Suxiang Ge; Zhi Zheng; Sixin Wu; Wenjun Fa (Chemical Engineering Journal, 2025)

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

Effects of melatonin on the pharmacokinetics and amino acid metabolism profile of vigabatrin in rats - Qiang Zheng; Song-Lin Xu; Xin-Lin Guo; Chuan-Yu Wang; Meng-Die Ma; Jin-Fang Ge (Toxicology and Applied Pharmacology, 2025)

A global soil spectral grid based on space sensing - José A.M. Demattê; Rodnei Rizzo; Nícolas Augusto Rosin; Raul Roberto Poppiel; Jean Jesus Macedo Novais; Merilyn Taynara Accorsi Amorim; Heidy Soledad Rodriguez-Albarracín; Jorge Tadeu Fim Rosas; Bruno dos Anjos Bartsch; Letícia Guadagnin Vogel; Budiman Minasny; Sabine Grunwald; et al. (Science of The Total Environment, 2025)

Widespread resistance of the apple aphid Aphis spiraecola to pyrethroids in China - Kang Wang; Yi You; Yunxiang Liu; Wenrong Xian; Yingying Song; You Ge; Xiaopeng Lu; Zhiqing Ma (Pesticide Biochemistry and Physiology, 2025)

Antitussive drug dextromethorphan induces developmental impairment in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Zhi-Jie Lu; Jin-Ge Zhang; Li-Xin Hu; Zheng Huang; Si-Ying Li; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Interactions between the co-contamination system of oxcarbazepine-polypropylene microplastics and Chlorella sp. FACHB-9: Toxic effects and biodegradation - Hao Zhang; Baoming Liu; Fengjie Sun; Ziqi Zhang; Yifan Kong; Xiang Liu; Yulin Cui; Yuyang Ma; Yuyong Wu; Jianhua Fan; Baosheng Ge; Yan Cheng; et al. (Journal of Environmental Management, 2025)

Quaternary ammonium chitosan-functionalized mesoporous silica nanoparticles: A promising targeted drug delivery system for the treatment of intracellular MRSA infection - Junfeng Liu; Liying Zhang; Haodi Ma; Haoyang Sun; Shu-ai Ge; Jieyi Liu; Shengdi Fan; Chunshan Quan (Carbohydrate Polymers, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

Leakage Risk Analysis of Underground Gas Storage Salt Caverns with Micro-leakage Interlayer in Bedded Rock Salt of Jiangsu, China - Hongwu Yin; Hongling Ma; Xilin Shi; Xinbo Ge (Rock Mechanics and Rock Engineering, 2025)

Investigation on neutronics changes in tungsten granular blockage accident on VENUS-II light water reactor - Liang Chen; Wei Jiang; Zhao-Dong Xia; Fei Ma; Rui Yu; Hai-Yan Meng; Qi Zhou; Hong-Lin Ge; Yan-Bin Zhang; Xue-Ying Zhang (Annals of Nuclear Energy, 2025)

Urinary neonicotinoid exposure and its association with hypertension and dyslipidemia among the elderly: A cross-sectional study in Shenzhen, China - Xinxin Tang; Jiaojiao Ma; Peiyi Liu; Sisi Yu; Xiaohu Ren; Wenchao Zhu; Xiao Chen; Yiming Ge; Haiyan Huang; Jianjun Liu; Shaoyou Lu (Chemosphere, 2025)

Arachidonic acid promotes ovarian development by modulating lipid metabolism and steroid hormone secretion in Chinese mitten crab (Eriocheir sinensis) - Anran Wang; Xuran Liu; Jie Xu; Mengge Li; Dongxu Luo; Xingkong Ma; Yongtao Liu; Jiachun Ge; Qinghui Ai; Shuyan Miao (Aquaculture, 2025)

C-C motif chemokine ligand 5 contributes to radon exposure-induced lung injury by recruiting dendritic cells to activate effector T helper cells - Liping Ma; Yilong Wang; Junwang Guo; Xuewen Zhang; Shuang Xing; Benbo Liu; Guo Chen; Xu Wang; Jiyao Hu; Ge Li; Gencheng Han; Maoxiang Zhu (Toxicology, 2025)

Associations of short-term exposure to air pollution with outpatient visits and treatment costs for chronic obstructive pulmonary disease in Xinxiang, China (2016–2021) - Huijun Li; Fei Zhai; You Ma; Yongbin Wang; Rongrong Gu; Chenlong Cao; Lei Wang; Beilei Ge; Wei Wu; Chengkai Zhai; Weidong Wu (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Liquid-liquid phase separation of TRAF6 promotes anti-TB immunity - Yongjia Duan; Yuanna Cheng; Mingtong Ma; Liru Li; Shanshan Liu; Liru Guan; Jie Wang; Hongjie Liu; Xiaochen Huang; Jianxia Chen; Hua Yang; Baoxue Ge; et al. (Science Bulletin, 2025)

Using machine learning to predict soil lead relative bioavailability - Shuang Zhang; Xiaoping Li; Tunyang Geng; Yu Zhang; Weixi Zhang; Xueming Zheng; He Sheng; Yueheng Jiang; Pengyuan Jin; Xuelian Kui; Huimin Liu; Ge Ma; et al. (Journal of Hazardous Materials, 2025)

Comprehensive assessment of straw returning with organic fertilizer on paddy ecosystems: A study based on greenhouse gas emissions, C/N sequestration, and risk health - Keqi Zhao; Xichen Zhao; Liuqin He; Nanyi Wang; Ma Bai; Xiaobing Zhang; Ge Chen; Anwei Chen; Lin Luo; Jiachao Zhang (Environmental Research, 2025)

Research on building energy-saving based on GA-BP coupled improved multi-objective whale optimization algorithm - Zhimin Liu; Huijun Ge; Tao Song; Shiwei Ma (Energy and Buildings, 2025)

Highly flexible and enhanced catalytic oxidation of Fe-doped Co3O4/SiOC core-shell heterostructured fibrous membranes for flow-through removal of organic contaminants - Haoru Shan; Wenqiang Wang; Zhirong Wang; Mengjiao Zhang; Yuxin Ma; Wenzhe Li; Qixia Liu; Xinglei Zhao; Jianlong Ge; Qiuxia Fu (Chemical Engineering Journal, 2025)

Integrating Ni2P crystalline-NiFeBP amorphous heterojunction nanosheets on hierarchical nickel foam for superior overall water splitting - Guang-Lan Li; Fei Deng; Tian-Ge Ma; Yu-Hui Shi; Junyan Liu; Yang Yan; Qing Mao; Junjiang Bao (Chemical Engineering Journal, 2025)

Drosophila modeling to identify causative genes and reveal the underlying molecular mechanisms for primary ovarian insufficiency - Yanbin Ma; Yuxin Liu; Man Xu; Xinhuan Yin; Chenyu Hu; Xiaohang Yang; Wanzhong Ge (Journal of Molecular Medicine, 2025)

Shear rheological behavior of clay: direct simple shear test and equivalent timeline concept-based model - Ge Chen; Jungao Zhu; Fulong Ma; Qixun Luo; Zhiwen Shen; Tao Wang (Bulletin of Engineering Geology and the Environment, 2025)

Genome-Wide Association Study Identifies Variants in ZmZEP1 Associated with Zeaxanthin Level in Maize Grains - Xiao Zhang; Li Qin; Yufang Ge; Meiyao Wang; Meixu Ma; Chengyang Zhao; Haiyan Li; Xiaoduo Lu (Journal of Plant Biology, 2025)

Oriented ice eddy detection network based on the Sentinel-1 dual-polarization data - Jinqun Wu; Yiqin Zheng; Tingting Wang; Chunyong Ma; Ge Chen (Frontiers in Marine Science, 2025)
The complex convergence of cold and warm ocean currents in the Nordic Seas provides suitable conditions for the formation and development of eddies. In the Marginal Ice Zones (MIZs), ice eddies contribute to the accelerated melting of surface sea ice by facilitating vertical heat transfer, which influences the evolution of the marginal ice zone and plays an indirect role in regulating global climate. In this paper, we employed high-resolution synthetic aperture radar (SAR) satellite imagery and proposed an oriented ice eddy detection network (OIEDNet) framework to conduct automated detection and spatiotemporal analysis of ice eddies in the Nordic Seas. Firstly, a high-quality RGB false-color imaging method was developed based on Sentinel-1 dual-polarization (HH+HV) Extra-Wide Swath (EW) mode products, effectively integrating denoising algorithms and image processing techniques. Secondly, an automatic ice eddy detection method based on oriented bounding boxes (OBB) was constructed to identify the ice eddy and output features such as horizontal scales, eddy centers and rotation angles. Finally, the characteristics of the detected ice eddies in the Nordic Seas during 2022-2023 were systematically analyzed. The results demonstrate that the proposed OIEDNet exhibits significant performance in ice eddy detection.

Using high CO2 concentrations to culture microalgae for lipid and fatty acid production: Synthesis based on a meta-analysis - Yuan Feng; Jingke Ge; Pau Loke Show; Chi Song; Liumiao Wu; Zengling Ma; Guang Gao (Aquaculture, 2025)

Different patterns of bacterioplankton in response to inorganic and organic phosphorus inputs in freshwater lakes - a microcosmic study - Tianhong Tu; Le Li; Wenkai Li; Shan Zhang; Hui Zhong; Gang Ge; Yantian Ma; Lan Wu (Water Research, 2025)

Optimization of low-carbon lightweight foamed concrete using ground circulating fluidized bed fly ash - Hongzhi Zhang; Quping Liang; Mingyang Shao; Nengdong Jiang; Wenqiang Ma; Zhi Ge; Branko Šavija (Journal of Cleaner Production, 2025)

An electrochemical sensor based on 2D Zn-MOFs and 2D C-Ti3C2Tx composite materials for rapid and direct detection of various foodborne pathogens - Liuhong Yang; Yifeng Ding; Yuhang Ma; Jing Wen; Jiafeng Wang; Ge Dai; Fengfeng Mo (Food Chemistry, 2025)

Liquid-solid triboelectric nanogenerator for bubbles real-time detecting - Xianzhang Wang; Yixing He; Jiaqi Shao; Yuan Liu; Liran Ma; Buzhen Su; Ruoling Deng; Mingxin Hou; Ge Chen; Jun Li (Chemical Engineering Journal, 2025)

Co-effect of surface-preferred crystal plane and surface coating for stable zinc metal anodes - Qing Zhou; Haifeng Bian; Biao Wang; Shunshun Jia; Ge Xue; Hao Wu; Fengqi Li; Zhonglu Hu; Haijiao Xie; Yujie Ma; Jian Gu; Shaochun Tang; et al. (Chemical Engineering Journal, 2025)

Zero-strain high entropy spinel oxide (FeNiCuCrMn)3O4@rGO as high-performance anode for sodium ion battery - Bin Xiao; Xiaoyang Liu; Zelin Xie; Duyu Zheng; Juxing Zha; Jiqiu Qi; Fuxiang Wei; Qingkun Meng; Xiaolan Xue; Danyang Zhao; Yongzhi Li; Qing Yin; et al. (Chemical Engineering Journal, 2025)

Enhanced removal of phenolic contaminants with permanganate oxidation mediated by SiO2@TEMPO: Performance, transformation pathway, and selectivity - Xiaoyan Chen; Jiangdong Cui; Xinyu Yang; Taoyue Yuan; Jiacheng Ge; Mengtao Ma; Shunke Ding; Wenhai Chu (Chemical Engineering Journal, 2025)

Deferoxamine-induced neurotoxicity: Role of chaperone-mediated autophagy dysfunction in neuronal apoptosis in the hippocampus - Hong Zhang; Jian Guo; Jiayi Chu; Huanhuan Yu; Jialin Zhang; Siman Ma; Ge Jin; Yingshan Jiang; Jiao Xiao; Yutong Hou; Minyan Li; Shiliang Yin (Chemico-Biological Interactions, 2025)

Characteristics and Functions of Rhizosphere Bacterial Communities of Camelli sinensis cv. Shifocui with Cold Resistance Characteristics in Anhui Province, China - Shuiqin Shi; Enhui He; Junjie Ma; Mengrui Ge; Jiahui Gao; Tianyi Peng; Yu Fu; Jianfen Wang; Li Gong; Duoqi Zhou; Yafang Liu (Current Microbiology, 2025)

An automatic method for extracting sand dunes based on slope cost distance from digital elevation models - Meirui Ge; Fayuan Li; Junfei Ma; Fangyuan Yu; Lingzhou Cui (Advances in Space Research, 2025)

An overview on the legacy and risks of Polychlorinated Biphenyls (PCBs) and Organochlorinated Pesticides (OCPs) in the polar regions - Peng Zhang; Jing Wang; Andrew Sweetman; Linke Ge; Rongguang Xing; Hao Ji; Jingfeng Yan; Qian Xiao; Yaqing Cui; Hongrui Ma; Sisi Xu (Marine Pollution Bulletin, 2024)

Association of ambient ozone exposure with early cardiovascular damage among general urban adults: A repeated-measures cohort study in China - Qiyou Tan; Min Zhou; Xiaojie You; Jixuan Ma; Zi Ye; Wendi Shi; Xiuqing Cui; Ge Mu; Linling Yu; Weihong Chen (Science of The Total Environment, 2024)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Cadmium immobilization by mercapto-palygorskite in alkaline soil: Impacts on soil microbial communities and wheat rhizosphere metabolism - Wenyan Ma; Chenghao Ge; Yuebing Sun; Min Wang; Dongmei Zhou (Science of The Total Environment, 2024)

“Gear-like” process between asymmetric dipole eddies from satellite altimetry - Shuang Long; Fenglin Tian; Ying Ma; Chuanchuan Cao; Ge Chen (Remote Sensing of Environment, 2024)

Optimization of collection efficiency for a dual-row jet mining machine based on CFD-DEM coupling - Wendong Yang; Feng Ge; Xuguang Chen; Ling Wang; Pengcheng Ma; Ziqi Xu (Ocean Engineering, 2024)

A thermodynamics-based coupled model for multi-phase flowback in deformable dual-porosity shale gas reservoirs - Kai Wang; Shangqi Ge; Yue Ma; Wenjie Tan; Yizhe Hou; Yanxiao Si; Aizhong Ding; Xiao-Hui Chen (Journal of Hydrology, 2024)

Novel catalyst-free activation of chlorine by visible light for micropollutant abatement - Ge Zeng; Linqian An; Maoju Jiang; Wenqi Li; Xiangyang Hou; Peng Su; Minchao Liu; Haijun Cheng; Zhiyun Long; Jingxin Yang; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

The accumulation and inhibition mechanism of extracellular polymeric substances of Chlorella vulgaris during cycling cultivation under different light qualities - Yufei Zhang; Sihan Ai; Xue Chen; Yabin Zhao; Yuxuan Zhang; Chenxi Wu; Chen Ma; Zhihong Tang; Daoyong Yu; Chaonan Yao; Baosheng Ge (Journal of Environmental Management, 2024)

Bisulfite enhances p-nitrophenol degradation by zero-valent iron under oxic conditions: Combination of indirect reduction by superoxide radical and direct reduction - Guang-En Yuan; Yan-Ge Ma; Kangning Huangfu; Yunbei Li; Xin Zhang; Fenglin Yang (Journal of Environmental Chemical Engineering, 2024)

Use of proteomics to elucidate characteristics of Cronobacter sakazakii under mild heat stress - Yanfei Yan; Mengyuan Cao; Jiaqi Ma; Jia Suo; Xiaobao Bai; Wupeng Ge; Xin Lv; Qiang Zhang; Jia Chen; Shenghui Cui; Baowei Yang (International Journal of Food Microbiology, 2024)

Quantitative proteomic analysis for characterization of protein components related to dough quality and celiac disease in wheat flour, dough, and heat-treated dough - Jianchao Feng; Yuku Jia; Beiming Xu; Xintong Bi; Zifei Ge; Geng Ma; Yingxin Xie; Chenyang Wang; Dongyun Ma (Food Chemistry, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Rational design of hierarchical defect-rich NiSe2/Se-NiCuOx heterostructures: Modulating electronic structure for exceptional ammonia oxidation performance - Guang-Lan Li; Tian-Ge Ma; Yu-Hui Shi; Fei Deng; Ri-Yang Huang; Yang Yan; Qing Mao; Yushan Li; Yonghou Xiao (Chemical Engineering Journal, 2024)

Mangrove fungi in action: Novel bioremediation strategy for high-chloride wastewater - Zhiping Han; Edward S.X. Moh; Xin Ge; Xingqian Luo; Haizhou Wang; Jie Ma; Sien Shi; Jianzhi Ye (Bioresource Technology, 2024)

An Amino Acids and Dipeptide Injection Inhibits the TNF-α/HMGB1 Inflammatory Signaling Pathway to Reduce Pyroptosis and M1 Microglial Polarization in POCD Mice: the Gut to the Brain - Yelong Ji; Yuanyuan Ma; Yimei Ma; Ying Wang; Xining Zhao; Li Xu; Shengjin Ge (Molecular Neurobiology, 2024)

CMPK2 Promotes CD4+ T Cell Activation and Apoptosis through Modulation of Mitochondrial Dysfunction in Systemic Lupus Erythematosus - Ya-Nan Tan; Ge-Ge Jiang; Xiang-Wen Meng; Zhi-Yuan Lu; Yan-Ma; Jin Li; Nan-Xiang; Xiao-Ge Sun; Qian Wang; Xue Wang; Xiao-Yi Jia; Min Zhang (Cell Biochemistry and Biophysics, 2024)

Effect of copper and temperature on the photosynthetic physiological characteristics of Ulva linza under elevated CO2 concentrations - Wen Wang; Zhouyue Lu; Wenjing Ge; Yuxin Xie; Tianpeng Xu; Jing Ma; Juntian Xu (Marine Pollution Bulletin, 2024)

Short-term sedimentary evidence for increasing diatoms in Arctic fjords in a warming world - Fu-Tao Fang; Zhuo-Yi Zhu; Fred Wenger; Jian-Zhong Ge; Jin-Zhou Du; Bing Deng; Hong-Mei Ma; Rui-Feng Zhang; Yu Zhang (Science of The Total Environment, 2024)

Coupled effects of redox-active substances and microbial communities on reactive oxygen species in rhizosphere sediments of submerged macrophytes - Kexuan Liu; Zuhan Ge; Dan Ai; Zihang Ma; Deying Huang; Jibiao Zhang (Science of The Total Environment, 2024)

Long-term agricultural cultivation decreases microbial nutrient limitation in coastal saline soils - Guanjun Li; Zhi Ma; Liang Wei; Cuiyan Wu; Hao Chen; Bin Guo; Tida Ge; Jianming Wang; Jingwen Li (Science of The Total Environment, 2024)

Sequence stratigraphy driven by tectonic subsidence and astronomical forcing: A case study from the Miocene Pearl River Mouth Basin, South China Sea - Xian Liu; Jiawang Ge; Hongjun Qu; Chang Ma (Marine and Petroleum Geology, 2024)

Fusion property prediction and mineral reaction mechanism of coal/biomass ash blends upon in-situ tests in the gasification process - Zefeng Ge; Yuqing Wu; Zenghui Hou; Lijuan Sun; Mingxun Zeng; Yuna Ma; Zhenting Zha; Qiuxiang Lu; Huiyan Zhang (Fuel, 2024)

Different microbiota modulation and metabolites generation of five dietary glycans during in vitro gut fermentation are determined by their monosaccharide profiles - Yuanyuan Zhao; Yubin Wang; Qiancheng Ma; Dan Wang; Qianqian Jiang; Pan Wang; Zhiwen Ge; Junjuan Wang; Peiyou Qin; Xiaoyan Zhao (Food Research International, 2024)

Characterization of a short-term processing technology of black garlic with low 5-HMF content - Jun Liu; Jing Li; Shihao Ge; Xiaoyu Fu; Jiamin Zhu; Mengnan Wang; Yanrong Wang; Xiaoxiao Huang; Xinzheng Qin; Yixian Tu; Jun Xing; Chao Ma; et al. (Food Control, 2024)

Simultaneous detection of eight dairy-derived components using multiplex PCR combined with gene membrane chip - Yafang Huang; Yingqiu Pan; Huili Xia; Xinyu Ma; Siling Ding; Jian Ge; Junfang Jiang; Feng Guan (Food Control, 2024)

CBS/CSE mediated H2S production induced AMPs expression through Toll pathway in crabs with black gill syndrome - Ziyue Zhu; Xingkong Ma; Xiaohan Liu; Liangmin Zheng; Lihua Zhang; Xiaoling Dai; Hao Li; Zhaoqian Zhang; Bingyan Wang; Xin Huang; Jiachun Ge; Qian Ren (Fish & Shellfish Immunology, 2024)

High-entropy FeCoNiCuRu solid solutions triggered cocktail effect to achieve fine-tuning adsorption energy for boosting nitrate electroreduction to ammonia - Tianfang Yang; Jinrui Huang; Shixiang Hu; Zunjie Zhang; Zhichao Ma; Shizhe Liu; Yang Liu; Bingcheng Ge; Pei Kang Shen; Shuyan Gao (Chemical Engineering Journal, 2024)

A novel macromolecular flame retardant based on sulfonyl diphenol monomer for simultaneous fire safety, transparency and high performance of thin-walled polycarbonate - Zongsheng Liu; Yi Zheng; Bangdong Ge; Meng Ma; Si Chen; Yanqin Shi; Huiwen He; Yulu Zhu; Xu Wang (Chemical Engineering Journal, 2024)

Selenium-doped carbon dots inhibit ferroptosis by multi-hierarchy iron chelation and mitochondrial homeostasis regulation to control inflammation - Kai Zhang; Xueyan Mao; Houming Zhao; Alberto Bianco; Shaohua Ge; Baojin Ma (Chemical Engineering Journal, 2024)

Electrolyte-triggered in-situ polymerization of multi-site organic cathodes for superior-longevity cation-anion co-storage secondary batteries - Xinmei Song; Yang Ge; Xiaolan Xue; Xingkai Ma; Qianchuan Yu; Mengfei Zhu; Yaoda Wang; Junchuan Liang; Zuoxiu Tie; Jing Ma; Zhong Jin (Chemical Engineering Journal, 2024)

Characteristics of soil salinity and water-salt transport in the vadose zone of salt-impacted regions with variable permeability - Zhiyuan Ma; Yanyan Ge; Bo Pang; Wei Liang; Tuerhong Ruze (Environmental Geochemistry and Health, 2024)

Patterns and controls of leaf litter nitrogen and phosphorus of broad-leaved tree species across and within the tropics and the extra-tropics - Boyu Ma; Yang Wang; Jielin Ge; Zongqiang Xie (Agricultural and Forest Meteorology, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Ocean acidification may alleviate the toxicity of zinc to the macroalga, Ulva lactuca - Jing Ma; Yuxin Xie; Zhouyue Lu; Houxu Ding; Wenjing Ge; Jie Jia; Juntian Xu (Marine Pollution Bulletin, 2024)

Iron mineral type controls organic matter stability and priming in paddy soil under anaerobic conditions - Shuang Wang; Wei Gao; Zhi Ma; Zhenke Zhu; Yu Luo; Liang Wei; Hongzhao Yuan; Song Chen; Chaoyun Ying; Kyle Mason-Jones; Yakov Kuzyakov; Tida Ge (Soil Biology and Biochemistry, 2024)

Evaluation and analysis of long-term MODIS MAIAC aerosol products in China - Ge Huang; Xin Su; Lunche Wang; Yi Wang; Mengdan Cao; Lin Wang; Xiaoyu Ma; Yueji Zhao; Leiku Yang (Science of The Total Environment, 2024)

Fast finite-time fault-tolerant trajectory tracking control of unmanned surface vehicles with multiple actuator constraints - Zhenyu Gao; Hengchao Ma; Ge Guo (Ocean Engineering, 2024)

Catalytic combustion of light hydrocarbons over Pd − Pt/Al2O3: The hidden Pt1 active sites - Ziran Ma; Jiali Zhou; Jing Lin; Gongjin Yang; Shuang Liu; Ge Li (Fuel, 2024)

Effects of environmental temperature extremes exposure on sperm quality - Evidence from a prospective cohort study in Anhui Province, China - Xu Zhang; Dongmei Ji; Ying Zhang; Liru Ge; Siwen Xu; Yongzhen Peng; Xuyang Chen; Jianping Ni; Guosheng Wang; Yubo Ma; Faming Pan (Environmental Research, 2024)

Promoting adsorption-diffusion-deposition of Zn2+ via a highly reactive modulator for dendrite-free and kinetics-enhanced Zn metal anode - Yilun Ren; Haifeng Bian; Shaozhong Chang; Yujie Ma; Hao Wu; Qing Zhou; Shunshun Jia; Ge Xue; Jian Gu; Haiming Lu; Xiangkang Meng (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Research on Precise Feeding Strategies for Large-Scale Marine Aquafarms - Yizhi Wang; Yusen Zhang; Fengyuan Ma; Xiaomin Tian; Shanshan Ge; Chaoyuan Man; Maohua Xiao (Journal of Marine Science and Engineering, 2024)
Breeding in large-scale marine aquafarms faces many challenges in terms of precise feeding, including real-time decisions as to the precise feeding amount, along with disturbances caused by the feeding speed and the moving speed of feeding equipment. Involving many spatiotemporal distributed parameters and variables, an effective predictive model for environment and growth stage perception is yet to obtained, further preventing the development of precise feeding strategies and feeding equipment. Therefore, in this paper, a hierarchical type-2 fuzzy system based on a quasi-Gaussian membership function for fast, precise, on-site feeding decisions is proposed and validated. The designed system consists of two layers of decision subsystems, taking in different sources of data and expert experience in feeding but avoiding the rule explosion issue. Meanwhile, the water quality evaluation is considered as the secondary membership function for type-2 fuzzy sets and used to adjust the parameters of the quasi-Gaussian membership function, decreasing the calculation load in type reduction. The proposed system is validated, and the results indicate that the shape of the primary fuzzy sets is altered with the secondary membership, which influences the defuzzification results accordingly. Meanwhile, the hardware of feeding bins for UAVs with variable-speed coupling control systems with disturbance compensation is improved and validated. The results indicate that the feeding speed can follow the disturbance in the level flying speed.

Exploring Siamese network to estimate sea state bias of synthetic aperture radar altimeter - Chunyong Ma; Qianqian Hou; Chen Liu; Yalong Liu; Yingying Duan; Chengfeng Zhang; Ge Chen (Frontiers in Marine Science, 2024)
Sea state bias (SSB) is a crucial error of satellite radar altimetry over the ocean surface. For operational nonparametric SSB (NPSSB) models, such as two-dimensional (2D) or three-dimensional (3D) NPSSB, the solution process becomes increasingly complex and the construction of their regression functions pose challenges as the dimensionality of relevant variables increases. And most current SSB correction models for altimeters still follow those of traditional nadir radar altimeters, which limits their applicability to Synthetic Aperture Radar altimeters. Therefore, to improve this situation, this study has explored the influence of multi-dimensional SSB models on Synthetic Aperture Radar altimeters. This paper proposes a deep learning-based SSB estimation model called SNSSB, which employs a Siamese network framework, takes various multi-dimensional variables related to sea state as inputs, and uses the difference in sea surface height (SSH) at self-crossover points as the label. Experiments were conducted using Sentinel-6 self-crossover data from 2021 to 2023, and the model is evaluated using three main metrics: the variance of the SSH difference, the explained variance, and the SSH difference variance index (SVDI). The experimental results demonstrate that the proposed SNSSB model can further improve the accuracy of SSB estimation. On a global scale, compared to the traditional NPSSB, the multi-dimensional SNSSB not only decreases the variance of the SSH difference by over 11%, but also improves the explained variance by 5-10 cm 2 in mid- and low-latitude regions. And the regional SNSSB also performs well, reducing the variance of the SSH difference by over 10% compared to the NPSSB. Additionally, the SNSSB model improves the computational efficiency by approximately 100 times. The favorable results highlight the potential of the multi-dimensional SNSSB in constructing SSB models, particularly the five-dimensional (5D) SNSSB, representing a breakthrough in overcoming the limitations of traditional NPSSB for constructing high-dimensional models. This study provides a novel approach to exploring the multiple influencing factors of SSB.

Stoichiometry regulates rice straw-induced priming effect: The microbial life strategies - Yuqin Liang; Dan Cao; Zhi Ma; Ruiqiao Wu; Hongrui Zhang; Yunying Fang; Muhammad Shahbaz; Xiao Jun Allen Liu; Yakov Kuzyakov; Jianping Chen; Tida Ge; Zhenke Zhu (Soil Biology and Biochemistry, 2024)

Unraveling the role of Mn(V)/Mn(III) in the enhanced permanganate oxidation under Vis-LED radiation - Jiamin Mai; Ge Zeng; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Xiangyang Hou; Minchao Liu; Jun Ma; Tao Yang (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Electro-oxidation of 5-hydroxymethylfurfural in a low-concentrated alkaline electrolyte by enhancing hydroxyl adsorption over a single-atom supported catalyst - Xiaoxia Xia; Jingyi Xu; Xinru Yu; Jing Yang; An-Zhen Li; Kaiyue Ji; Lei Li; Min Ma; Qian Shao; Ruixiang Ge; Haohong Duan (Science Bulletin, 2024)

Selenium alleviates chromium stress and promotes chromium uptake in As-hyperaccumulator Pteris vittata: Cr reduction and cellar distribution - Qian-Yu Zhou; Wei Li; Si-Xue He; Song-Ge Deng; Shu-Fen Xiao; Chen-Jing Liu; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Multifunctional bacterial cellulose-bentonite@polyethylenimine composite membranes for enhanced water treatment: Sustainable dyes and metal ions adsorption and antibacterial properties - Xueqing Zhao; Mingbo Yang; Yucheng Shi; Liyuan Sun; Haolong Zheng; Mengmeng Wu; Ge Gao; Ting Ma; Guoqiang Li (Journal of Hazardous Materials, 2024)

Foliar-selenium enhances plant growth and arsenic accumulation in As-hyperaccumulator Pteris vittata: Critical roles of GSH-GSSG cycle and arsenite antiporters PvACR3 - Wei Li; Si-Xue He; Qian-Yu Zhou; Zhi-Hua Dai; Chen-Jing Liu; Shu-Fen Xiao; Song-Ge Deng; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Exploring the cationic surfactant adsorption efficiency at concentrations relative to the critical micelle concentration by SA/SiO2 microspheres - Zhiying Li; Lei Zhao; Qing Ao; Ge Zhang; Dongqing Kang; Yingli Li; Jian Liu; Gongtao Ding; Zhongren Ma; Yeit Haan Teow; Mohd Shaiful Sajab; Zhiqiang Li; et al. (Journal of Environmental Management, 2024)

Evolution and distribution of antibiotic resistance genes in submerged macrophytes and biofilm systems: From seasonal monitoring to mesocosm experiments - Zuhan Ge; Dan Ai; Zihang Ma; Yaguang Li; Jibiao Zhang (Journal of Environmental Management, 2024)

One-pot tandem conversion of furfural to γ-valerolactone over a series of modified zirconium-based metal–organic frameworks with variational Lewis and Brønsted acid sites - Wei Xue; Mingwei Ma; Pan Hou; Peng Zhang; Wenzheng Liu; Yongchen Liu; Huijuan Yue; Xiaofeng Wang; Ge Tian; Shouhua Feng (Fuel, 2024)

Lithium-Ion battery silicon Anodes: Surface engineering with novel additives for enhanced ion and electron transport - Kanghou Ma; Yitao He; Xinyue Zhao; Sunfa Wang; Ge Zhang; Chen Wang; Fangshuo Zhou; Wei Shi; Yaohui Zhang (Chemical Engineering Journal, 2024)

Large-scale production of a “skin-like” self-pumping fabric for personal sweat management - Meitong Ge; Fengxiang Chen; Chaoyu Chen; Honglian Cong; Zhijia Dong; Pibo Ma (Chemical Engineering Journal, 2024)

Suppression of pathological neovascularization by anti-Flt1 peptide functionalized DNA tetrahedron - Bicai Tang; Yuting Yang; Yong Li; Yutian He; Yichen Ge; Yangxue Yao; Wenjuan Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Glycine-doped metal–organic frameworks as intelligent nanocarriers to enhance pesticide delivery and provide micronutrient in plants - Tingting Liu; Chunli Xu; Dicheng Ma; Lidong Cao; Shenguang Ge; Yuanbo Li (Chemical Engineering Journal, 2024)

Ultrastructure of the larval rectum of the scorpionfly Panorpa liui (Mecoptera: Panorpidae) - Wan-Ruo Ma; Lu Liu; Ge Wang; Jia-Li Bai; Bao-Zhen Hua (Arthropod Structure & Development, 2024)

Classification of exercise fatigue levels by multi-class SVM from ECG and HRV - Yuru Chen; Huanmin Ge; Xinhua Su; Xinxin Ma (Medical & Biological Engineering & Computing, 2024)

TRIM25-mediated XRCC1 ubiquitination accelerates atherosclerosis by inducing macrophage M1 polarization and programmed death - Hongxian Wu; Wei Gao; Yuanji Ma; Xin Zhong; Juying Qian; Dong Huang; Junbo Ge (Inflammation Research, 2024)

Time-dependent non-uniform corrosion of concrete structures under marine environments considering the vertical variation of exposure conditions - Qifang Liu; Yiquan Chen; Yan Ge; Qingrong Xiong; Jinliang Ma; Yukang Wang; Fengling Zhang (Ocean Engineering, 2024)

Synergistically promoting the catalytic conversion of polysulfides via in-situ construction of Ni-MnO2 heterostructure on N-doped hollow carbon spheres towards high-performance sodium-sulfur batteries - Haoyu Zhao; Zuze Li; Mingzhe Liu; Suyu Ge; Kaixuan Ma; Qingze Jiao; Hansheng Li; Haijiao Xie; Yun Zhao; Caihong Feng (Chemical Engineering Journal, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Labile organic carbon fractions in the rhizosphere contribute to nitrogen and phosphorus uptake in rice under long-term crop rotations and nitrogen application - Mengjia Wang; Xiangqian Feng; Ziyu Zhou; Hengyu Ma; Tida Ge; Caixian Tang; Danying Wang; Song Chen (Applied Soil Ecology, 2024)

Novel sunlight-induced monochloramine activation system for efficient microcontaminant abatement - Haochen Zhang; Maoju Jiang; Peng Su; Qixiao Lv; Ge Zeng; Linqian An; Jun Ma; Tao Yang (Water Research, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Prediction and explanation of debris flow velocity based on multi-strategy fusion Stacking ensemble learning model - Tianlong Wang; Keying Zhang; Zhenghua Liu; Tianxing Ma; Rui Luo; Hao Chen; Xu Wang; Wei Ge; Hongyue Sun (Journal of Hydrology, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Mobile measurement background quantification methods for determining local traffic emissions and background source contributions to ammonia - Weiwei Pu; Yingruo Li; Di He; Fan Dong; Jin Wu; Xiangxue Liu; Yulu Qiu; Shuangshuang Ge; Zhiqiang Ma (Atmospheric Environment, 2024)

Effect of Genotype on Cadmium and Trace Element Accumulation in Wheat from Weakly Alkaline Cadmium-contaminated Soil - Wenyan Ma; Yuliang Li; Chenghao Ge; Min Wang; Dongmei Zhou (Bulletin of Environmental Contamination and Toxicology, 2024)

Seismic effectiveness evaluation and optimized design of tie up method for securing museum collections - Meng Wang; Yi Yan; Weiguo Yang; Pei Liu; Jiaqi Ge; Botao Ma (Earthquake Engineering and Engineering Vibration, 2024)

Significant influence of urban human activities and marine input on rainwater chemistry in a coastal large city, China - Jie Zeng; Guilin Han; Qixin Wu; Rui Qu; Qing Ma; Jingwen Chen; Shijun Mao; Xin Ge; Zhong-Jun Wang; Zhiheng Ma (Water Research, 2024)

An assessment of the carbon emissions of China's ICT system from the demand and supply perspectives - Rong Yuan; Tianhao Ma; Yihan Ge (Sustainable Production and Consumption, 2024)

High efficiency triethylamine gas sensor based on SmVO4 nano octahedron granules - Cheng Yu Xu; Shu Yi Ma; Tian Yuan Dong; Ji Ming Liu; Jin Sha Wei; Hong Tao Jiang; Ping Ni; Ge Ge Fan; Jia Yun Guo (Journal of Environmental Chemical Engineering, 2024)

A review on potential applications of Fe/Ni/Ca in biomass catalytic reforming to produce hydrogen - Qiuxiang Lu; Kai Wu; Zhenting Zha; Yuna Ma; Zefeng Ge; Huiyan Zhang (Fuel, 2024)

Machine learning-based virtual screening of multi-target anti-obesity compounds from medicinal and edible plants: A combined in silico and in vitro study - Xincheng Zhou; Jian Ni; Weiben Ge; Xinyue Wang; Yubing Li; Hongxin Wang; Chaoyang Ma (Food Bioscience, 2024)

Spatial-temporal-controlled NO gas and PARP1 siRNA delivery for alleviating the dilemma of deeper sonodynamic therapy in pancreatic cancer - Qingshuang Tang; Yuan Wang; Ruiqi Wu; Zexing Yu; Xue Shi; Yang Song; Lulu Zhang; Xin Li; Jinxia Zhang; Suhui Sun; Xiaotu Ma; Shuyu Xu; et al. (Chemical Engineering Journal, 2024)

Facet engineering of α-MnO2 for directly electrocatalytic oxygen atom transfer from water toward epoxidation - Yingjun Tian; Baoying Li; Jingrun Wang; Yuyang Ge; Wei Gao; Linyan Yu; Li Ma; Yuehui Li; Ling Wang; Zunqi Liu; Jianbin Chen (Chemical Engineering Journal, 2024)

Hollow fiber gas-diffusion electrodes with tailored crystal facets for tuning syngas production in electrochemical CO2 reduction - Guoliang Chen; Lei Ge; Yizhu Kuang; Hesamoddin Rabiee; Beibei Ma; Fatereh Dorosti; Ashok Kumar Nanjundan; Zhonghua Zhu; Hao Wang (Chemical Engineering Journal, 2024)

The Photocatalytic Ozonation Oxidation Synergistic Degradation on Organic Pollutants In Coal Chemical Phenol-Ammonia Wastewater by Two-Dimensional Nanosheets Bi2WO6 - Fei Li; Qiang Luo; Weijun Zhen; Qing Ge; Yushen Zhou; Chunmei Ma; Pengtao Sun; Jianbo Xu; Buning Chen (Water, Air, & Soil Pollution, 2024)

Developmental pleiotropy of SDP1 from seedling to mature stages in B. napus - Baolong Tao; Yina Ma; Liqin Wang; Chao He; Junlin Chen; Xiaoyu Ge; Lun Zhao; Jing Wen; Bin Yi; Jinxing Tu; Tingdong Fu; Jinxiong Shen (Plant Molecular Biology, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

The potential ability of fungi in preventing cadmium accumulation in wheat seedlings grown in weakly alkaline soils: Evidence from the application of fungicide - Chenghao Ge; Yixuan Wang; Wenyan Ma; Hafiz Adeel Ahmad; Cheng Cheng; Hong-Bo Li; Dongmei Zhou (Applied Soil Ecology, 2024)

Refinement of kinetic model and understanding the role of dichloride radical (Cl2•−) in radical transformation in the UV/NH2Cl process - Haochen Zhang; Maoju Jiang; Peng Su; Qixiao Lv; Ge Zeng; Linqian An; Jiachun Cao; Yang Zhou; Shane Allen Snyder; Jun Ma; Tao Yang (Water Research, 2024)

Evolution and determinants of precipitation chemistry in a plateau city, China: Insight from the pollutants source identification and environmental effect - Jie Zeng; Guilin Han; Qixin Wu; Qing Ma; Shijun Mao; Xin Ge; Zhong-Jun Wang; Chao Yang (Urban Climate, 2024)

The azole biocide climbazole induces oxidative stress, inflammation, and apoptosis in fish gut - Zhi-Jie Lu; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Xiao-Bing Long; Si-Ying Li; Fang-Zhou Gao; Qian-Qian Zhang; Guang-Guo Ying (Science of The Total Environment, 2024)

Role of bipyridyl in enhancing ferrate oxidation toward micropollutants - Juan Li; Jiachun Cao; Maoju Jiang; Linqian An; Ge Zeng; Jiamin Mai; Peng Su; Binghua Jing; Mingbao Feng; Zhimin Ao; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

China's “coal-to-gas” policy had large impact on PM1.0 distribution during 2016–2019 - Tianqi Shi; Yanran Peng; Xin Ma; Ge Han; Haowei Zhang; Zhipeng Pei; Siwei Li; Huiqin Mao; Xingying Zhang; Wei Gong (Journal of Environmental Management, 2024)

Are longer and more intense heatwaves more prone to extreme precipitation? - Peng Sun; Yaojin Bian; Shifang Yu; Rui Yao; Zhongtian Wang; Qiang Zhang; Wenhui Chen; Chenhao Ge; Zice Ma; Wenying Du (Global and Planetary Change, 2024)

Evaluation of styrene butadiene rubber asphalt modification mechanism and adhesion effect based on molecular simulation - Tangxin Xie; Zhongming He; Huanan Yu; Yuetan Ma; Changyun Shi; Chao Zhang; Jinguo Ge; Wan Dai (Fuel, 2024)

Upcycling crab shell waste into biochar for treatment of palm oil mill effluent via microwave pyrolysis and activation - Yan Yang; Shin Ying Foong; Yifeng He; Rock Keey Liew; Nyuk Ling Ma; Peter Nai Yuh Yek; Shengbo Ge; Mu. Naushad; Su Shiung Lam (Environmental Research, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

A five-lump coupled kinetic model for residue hydrodesulfurization in an ebullated bed based on hydrocracking model - Xiaodong Cheng; Hailong Ge; Hexu Ma; Huihong Zhu; Tao Yang; Xiangdong Tan; Shuandi Hou (Fuel, 2024)

Synergy of Mo doping and heterostructures in FeCo2S4@Mo-NiCo LDH/NF as durable and corrosion-resistance bifunctional electrocatalyst towards seawater electrolysis at industrial current density - Suyu Ge; Xueran Shen; Jiaxin Gao; Kaixuan Ma; Haoyu Zhao; Ruru Fu; Caihong Feng; Yun Zhao; Qingze Jiao; Hansheng Li (Chemical Engineering Journal, 2024)

Characteristics of PM2.5 hygroscopicity and the influences of water-soluble ions during haze events in Beijing - Shuangshuang Ge; Jie Su; Pusheng Zhao; Ju Li; Shijie Liu; Yulu Qiu; Weiwei Pu; Zhiqiang Ma (Atmospheric Environment, 2024)

SS-31 inhibits mtDNA–cGAS–STING signaling to improve POCD by activating mitophagy in aged mice - Yelong Ji; Yuanyuan Ma; Yimei Ma; Ying Wang; Xining Zhao; Danfeng Jin; Li Xu; Shengjin Ge (Inflammation Research, 2024)

CDC-like kinase 3 deficiency aggravates hypoxia-induced cardiomyocyte apoptosis through AKT signaling pathway - Xiue Ma; Liming Gao; Rucun Ge; Tianyou Yuan; Bowen Lin; Lixiao Zhen (In Vitro Cellular & Developmental Biology - Animal, 2024)

Effects of New Psychoactive Substance Esketamine on Behaviors and Transcription of Genes in Dopamine and GABA Pathways in Zebrafish Larvae - Si-Ying Li; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Bulletin of Environmental Contamination and Toxicology, 2024)

Acid tolerance response of Salmonella during the squid storage and its amine production capacity analysis - Wei Ge; Qiong Yang; Hui Wang; Chuanyan Pan; Min Lv; Lingyun Liang; Shiya Ya; Xu Luo; Weisheng Wang; Huawei Ma (Archives of Microbiology, 2024)

BDE-47-induced damage prevented by melatonin in grass carp hepatocytes (L8824) - Jianhua Shan; Haoyue Guan; Zhuoqi Zhang; Wenxue Ma; Jingzeng Cai; Ge Gao; Ziwei Zhang (Environmental Science and Pollution Research, 2024)

Combining water-saving and drought-resistant rice with plastic film mulching mitigates CH4 emissions with higher net economic benefits - Guangbin Zhang; Yuting Yang; Xiaoli Zhu; Wanyu Shen; Zhenke Zhu; Tida Ge; Longlong Xia; Jing Ma; Shihua Lv; Hua Xu (Resources, Conservation and Recycling, 2024)

An azole fungicide climbazole damages the gut-brain axis in the grass carp - Zhi-Jie Lu; Wen-Jun Shi; Fang-Zhou Gao; Dong-Dong Ma; Jin-Ge Zhang; Si-Ying Li; Xiao-Bing Long; Qian-Qian Zhang; Guang-Guo Ying (Journal of Hazardous Materials, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Characterization of key flavor substances and their microbial sources in traditional sour bamboo shoots - Hui Tang; Jin-Kui Ma; Lin Chen; Li-Wen Jiang; Lin-Zhi Kang; Ying-Yu Guo; Ge-Yang Men; Dan-Xia Nie; Rui-Min Zhong (Food Chemistry, 2024)

Uncovering Se, P co-doping effect in MnO2 toward high-performance aqueous zinc-ion batteries - Kaixuan Ma; Suyu Ge; Ruru Fu; Caihong Feng; Haoyu Zhao; Xueran Shen; Guangfeng Liang; Yun Zhao; Qingze Jiao (Chemical Engineering Journal, 2024)

Reactivity and kinetics of biomass pyrolysis products for in-situ reduction of NOx in a bubbling fluidized bed - Zhenting Zha; Fangzhou Li; Zefeng Ge; Qiuxiang Lu; Yuna Ma; Mingxun Zeng; Yuqing Wu; Zenghui Hou; Huiyan Zhang (Chemical Engineering Journal, 2024)

Generation of •OH and intermediate manganese species for the efficient removal of micropollutants via photocatalysis of permanganate by indium oxide - Juan Li; Maoju Jiang; Peng Su; Qixiao Lv; Linqian An; Ge Zeng; Xiangyang Hou; Wenqi Li; Chunzhao Chen; Jun Ma; Tao Yang (Chemical Engineering Journal, 2024)

A Study on the Assessment and Integration of Multi-Source Evapotranspiration Products over the Tibetan Plateau - Ming Cheng; Lei Zhong; Yaoming Ma; Han Ma; Yaoxin Chang; Peizhen Li; Meilin Cheng; Xian Wang; Nan Ge (Advances in Atmospheric Sciences, 2024)

Soil nutrient conditions alter viral lifestyle strategy and potential function in phosphorous and nitrogen metabolisms - Xing Huang; Zhichao Zhou; Haiyang Liu; Yiqun Li; Tida Ge; Xianjin Tang; Yan He; Bin Ma; Jianming Xu; Karthik Anantharaman; Yong Li (Soil Biology and Biochemistry, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Chemical evolution of rainfall in China's first eco-civilization demonstration city: Implication for the provenance identification of pollutants and rainwater acid neutralization - Jie Zeng; Guilin Han; Qixin Wu; Meixue Peng; Xin Ge; Shijun Mao; Zhong-Jun Wang; Qing Ma (Science of The Total Environment, 2024)

Retrieving hourly seamless PM2.5 concentration across China with physically informed spatiotemporal connection - Yu Ding; Siwei Li; Jia Xing; Xi Li; Xin Ma; Ge Song; Mengfan Teng; Jie Yang; Jiaxin Dong; Shiyao Meng (Remote Sensing of Environment, 2024)

Research and development of vortex suction dedusting device based on multi-factor horizontal response surface method - Shuaishuai Ren; Deji Jing; Shaocheng Ge; Mingxing Ma; Mohammad Waqar Ali Asad; Ping Chang (Journal of Cleaner Production, 2024)

Experimental and numerical research on the failure pattern and mechanisms of granite disc with a pre-crack after heating and liquid nitrogen cooling - Yuliang Zhang; Guowei Ma; Qiang Sun; Zhenlong Ge; Xindong Wei; Zhe Li; Fuxin Rui (International Journal of Rock Mechanics and Mining Sciences, 2024)

Effect of indigenous Saccharomyces cerevisiae strains on microbial community successions and volatile compounds changes during Longyan wine fermentation - Xiaodi Wang; Chao Dang; Yaqiong Liu; Xiaoxin Ge; Ran Suo; Qianyun Ma; Jie Wang (Food Bioscience, 2024)

Micro- and nanoplastics interact with conventional pollutants on microalgae: Synthesis through meta-analysis - Jingke Ge; Peng Jin; Shuyu Xie; John Beardall; Yuan Feng; Can Guo; Zengling Ma; Guang Gao (Environmental Pollution, 2024)

Char-based Fe-Ni-Ca material for capturing AAEM from biomass pyrolysis volatiles and recyclability in catalytic reforming of volatiles - Qiuxiang Lu; Kai Wu; Zhenting Zha; Yuna Ma; Zefeng Ge; Mingxun Zeng; Shenfu Yuan; Huiyan Zhang (Chemical Engineering Journal, 2024)

The crosstalk between Toll and AMPK signaling pathways mediates growth inhibition of Eriocheir sinensis under deltamethrin stress - Qian Ren; Ximei Nie; Xingkong Ma; Zhengxiao Han; Yanfang Li; Xintong Yang; Lei Ji; Rongqian Su; Jiachun Ge; Xin Huang (Aquatic Toxicology, 2024)

Variability of syn-rift geometry in Pearl River Mouth Basin, China: implications for faulting patterns in two-phase rift basins - G. R. Peng; P. Liu; B. S. Ma; J. W. Ge (Australian Journal of Earth Sciences, 2024)

Multiomics was used to clarify the mechanism by which air pollutants affect chronic obstructive pulmonary disease: A human cohort study - Huijun Li; Yanting Yang; Yanpeiyue Yang; Chengkai Zhai; Juan Yao; Wei Liao; Yongbin Wang; Jing Wang; Chenlong Cao; Hany W. Darwish; Wei Wu; Wenlong Li; et al. (Toxicology, 2024)

Benchmark of plant-based VOCs control effect for indoor air quality: Green wall case in smith campus at Harvard University - Xiwei Shen; Qingqing Sun; Grant Mosey; Junhong Ma; Ling Wang; Mengting Ge (Science of The Total Environment, 2024)

Temporal variations in reactive oxygen species in biofilms of submerged macrophytes: The key role of microbial metabolism mediated by oxygen fluctuations - Zuhan Ge; Zihang Ma; Wenjie Hong; Kexuan Liu; Shuwen Yan; Weihua Song; Jibiao Zhang (Journal of Hazardous Materials, 2024)

Utilizing adsorption of wood and its derivatives as an emerging strategy for the treatment of heavy metal-contaminated wastewater - Jinxuan Jiang; Yang Shi; Nyuk Ling Ma; Haoran Ye; Meenakshi Verma; Hui Suan Ng; Shengbo Ge (Environmental Pollution, 2024)

Longitudinal association of polycyclic aromatic hydrocarbons and genetic risk with lung function - Min Zhou; Shijie Yang; Limin Cao; Wencan Dai; Xiuquan Nie; Ge Mu; Xiaokang Zhang; Bin Wang; Jixuan Ma; Dongming Wang; Tingming Shi; Chaolong Wang; et al. (Environmental Pollution, 2024)

Cellulose nanocrystals-based fluorescent biocarrier binding GAPDH protein with high affinity in cancer-target doxorubicin delivery - Xiaoping Zhao; Qin Wang; Ning Wang; Ge Zhu; Jingzhi Ma; Ning Lin (Carbohydrate Polymers, 2024)

Mapping soil particle-size fractions based on compositional balances - Mo Zhang; Wenjiao Shi; Yuxin Ma; Yong Ge (CATENA, 2024)

Effects of biochar and volcanic rock addition on humification and microbial community during aerobic composting of cow manure - Shuangshuang Ma; Yujun Shen; Jingtao Ding; Hongsheng Cheng; Haibin Zhou; Mianshen Ge; Jian Wang; Qiongyi Cheng; Dongli Zhang; Yun Zhang; Pengxiang Xu; Pengyue Zhang (Bioresource Technology, 2024)

Health risk assessment of trace metal(loid)s in agricultural soils based on Monte Carlo simulation coupled with positive matrix factorization model in Chongqing, southwest China - Jie Ma; Lijuan Chu; Jing Sun; Shenglan Wang; Miao Ge; Li Deng (Journal of Mountain Science, 2024)

Comparative analysis of the effect of nano‑copper and Cu2O treatment on Cryptocaryon irritans tomonts in large yellow croaker (Larimichthys crocea) farming - Ying Zhou; Quanyin Liu; Kun Hu; Mingfeng Ge; Shengwei Xu; Chengyi Huang; Shan Jin; Rongrong Ma; Jianping Wang (Aquaculture, 2023)

Molecular and optical signatures of photochemical transformation of dissolved organic matter: Nonnegligible role of suspended particulate matter in urban river - Jingyi Hou; Ruochun Zhang; Jinfeng Ge; Chao Ma; Yuanbi Yi; Yulin Qi; Si-Liang Li (Science of The Total Environment, 2023)

Improvement of the sediment flux estimation in the Yangtze River Estuary with a GOCI data adjusted numerical model - Guohu Xie; Yang Zhang; Jia Liu; Huijie Xue; Jianzhong Ge; Xianqiang He; Wentao Ma; Fei Chai (Ocean Modelling, 2023)

Nightmare or delight: Taxonomic circumscription meets reticulate evolution in the phylogenomic era - Ze-Tao Jin; Richard G.J. Hodel; Dai-Kun Ma; Hui Wang; Guang-Ning Liu; Chen Ren; Bin-Jie Ge; Qiang Fan; Shui-Hu Jin; Chao Xu; Jun Wu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2023)

Preparation and characterization of polyvinyl alcohol/glutaraldehyde cross-linked chitosan/ε-Polylysine degradable composite film and its antibacterial effect - Shuangfeng Guo; Xiuyun Zhang; Rong Ma; Xiangzhen Ge; Huishan Shen; Wei Liang; Guoquan Zhang; Wenhao Li (Journal of Food Engineering, 2023)

Explosion behaviors of hydrogen-nitrous oxide mixtures with propane addition - Yun Ge; Hong-Hao Ma; Jia-Wei Liu; Yuan Zeng; Jun Pan; Lu-Qing Wang (Fuel, 2023)

Hydrogen-rich syngas production and insight into morphology-kinetics correlation for furfural residue steam gasification in a bubbling fluidized bed - Zhenting Zha; Zefeng Ge; Yuna Ma; Mingxun Zeng; Yuqing Wu; Zenghui Hou; Fangzhou Li; Huiyan Zhang (Chemical Engineering Journal, 2023)

Ephedrine and cocaine cause developmental neurotoxicity and abnormal behavior in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Characteristics and health risk assessment of indoor and outdoor PM2.5 in a rural village, in Northeast of China: impact of coal and biomass burning - Ge Ma; Xiuqun Liu; Jingzhi Wang; Minrui Li; Zhibao Dong; Xiaoping Li; Lijun Wang; Yongming Han; Junji Cao (Environmental Geochemistry and Health, 2023)

Occurrence, Migration, and Transformation of Black Carbon in Environmental Matrix and Its Influence on the Environmental Fate of Coexisting Pollutants: A Review - Yaqian Gao; Yuhui Ge; Yunfeng Ma; Hailun Zhao; Guixing Xiao; Pau Loke Show; Jianqiu Chen; Ruixin Guo; Yanhua Liu (Reviews of Environmental Contamination and Toxicology, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Purification of aquaculture wastewater by macrophytes and biofilm systems: Efficient removal of trace antibiotics and enrichment of antibiotic resistance genes - Zuhan Ge; Zihang Ma; Jianmin Zou; Yunyi Zhang; Yaguang Li; Lieyu Zhang; Jibiao Zhang (Science of The Total Environment, 2023)

Soil moisture dominates the variation of gross primary productivity during hot drought in drylands - Ruonan Qiu; Ge Han; Siwei Li; Feng Tian; Xin Ma; Wei Gong (Science of The Total Environment, 2023)

Foliar application of selenium nanoparticles alleviates cadmium toxicity in maize (Zea mays L.) seedlings: Evidence on antioxidant, gene expression, and metabolomics analysis - Min Wang; Chunyi Mu; Yuliang Li; Yixuan Wang; Wenyan Ma; Chenghao Ge; Cheng Cheng; Gaoling Shi; Hongbo Li; Dongmei Zhou (Science of The Total Environment, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

The hidden indirect environmental effect undercuts the contribution of crop nitrogen fertilizer application to the net ecosystem economic benefit - Quanfeng Yang; Junhua Ma; Fei Yang; Hua Zheng; Zengbin Lu; Fei Qiao; Kening Zhang; Huarui Gong; Xingyuan Men; Jing Li; Fang Ouyang; Feng Ge (Journal of Cleaner Production, 2023)

In vitro starch digestibility of maize flour and maize extruded noodles based on different particle-size effects - Rui Ge; Xiaojie Qian; Binghua Sun; Sen Ma; Xiaoxi Wang (Journal of Cereal Science, 2023)

A new attempt to control volatile organic compounds (VOCs) pollution - Modification technology of biomass for adsorption of VOCs gas - Guiyang Zheng; Kexin Wei; Xuelian Kang; Wei Fan; Nyuk Ling Ma; Meenakshi Verma; Hui Suan Ng; Shengbo Ge (Environmental Pollution, 2023)

Dynamics of Tethyan marine de‑oxygenation and relationship to S-N-P cycles during the Permian-Triassic boundary crisis - Yuzhu Ge; Thomas J. Algeo; Huaguo Wen; Chen Zhang; Yiquan Ma; Chengbo Lian (Earth-Science Reviews, 2023)

Singlet oxygen is also involved in the formation of hypoiodous acid during the transformation of phenolic pollutants by peracetic acid in the presence of iodide - Jiamin Mai; Ge Zeng; Linqian An; Maoju Jiang; Peng Su; Qixiao Lv; Xiangyang Hou; Xiujuan Kong; Jianbo Jia; Tao Yang; Jun Ma (Chemical Engineering Journal, 2023)

The influence of spermidine on the build-up of fucoxanthin in Isochrysis sp. Acclimated to varying light intensities - Yahui Bo; Shanshan Wang; Feifei Ma; Artem Yurevich Manyakhin; Guilin Zhang; Xiaohui Li; Chengxu Zhou; Baosheng Ge; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

Transcriptomic profiling of nuclei from paraformaldehyde-fixed and formalin-fixed paraffin-embedded brain tissues - Yunxia Guo; Junjie Ma; Zhengyue Li; Kaitong Dang; Qinyu Ge; Yan Huang; Guang-zhong Wang; Xiangwei Zhao (Analytica Chimica Acta, 2023)

Paleoproductivity and deep-sea oxygenation in Cosmonaut Sea since the last glacial maximum: impact on atmospheric CO2 - Liangming Hu; Yi Zhang; Yizhuo Wang; Pengyun Ma; Wendong Wu; Qian Ge; Yeping Bian; Xibin Han (Frontiers in Marine Science, 2023)
The paleoproductivity in the Southern Ocean plays a crucial role in controlling the atmospheric CO 2 concentration. Here, we present the sediment record of gravity core ANT37-C5/6-07, which was retrieved from the Cosmonaut Sea (CS), Indian Ocean sector of the Southern Ocean. We found that the change in the oxygen concentration in the CS bottom water is strongly correlated with the atmospheric CO 2 fluctuations since the Last Glacial Maximum (LGM). Based on the change in the export production, we reconstructed the evolution history of the deep-water ventilation/upwelling in the study area. During the LGM, a large amount of respiratory carbon was stored in the deep Southern Ocean due to the effect of the low export productivity and restricted ventilation. The oxygen concentration was also low at this time. Despite the increase in paleoproductivity, the biological pump efficiency remained at a low level during the Last Deglaciation. Vast quantities of CO 2 were released into the atmosphere through enhanced upwelling. The recovery of ventilation during this period facilitated the supply of oxygen-rich surface water to the deep ocean. Moreover, signals were identified during the transitions between the Heinrich Stage 1 (HS1), Antarctic Cold Reverse (ACR), and Younger Drays (YD) periods. During the Holocene, the productivity increased overall, and the oxygen in the bottom water was consumed but still remained at a high level. This may have been caused by the enhanced ventilation and/or the prevalence of East Cosmonaut Polynya (ECP) near Cape Ann.

Analysis of tobacco exposures and high-risk HPV infection in American women: National Health and Nutrition Examination Survey - Liangzi Jiang; Suting Ma; Ge Zhang; Lingling Jiang; Li Yan (Environmental Science and Pollution Research, 2023)
Nicotine is a known toxin, but its relationship with cervicovaginal high-risk human papillomavirus (HR-HPV) infection is uncertain. This study aimed to investigate whether tobacco exposure is associated with elevated cervicovaginal HR-HPV infection in US women, and if the strength of this association varies with the degree of exposure. Cross-sectional data from the 2011–2016 National Health and Nutrition Examination Survey (NHANES), which included a nationally representative sample of US women, were used for the study. Out of 12436 women aged 18–59 who participated in the interview, 3833 were ultimately enrolled in this study. Weighted logistic regression was used to estimate the link between tobacco exposure and cervicovaginal HR-HPV infection. The mean age of participants was 38.6 (SD 12.1) years, and non-Hispanic White individuals accounted for 37.3% of the sample. Those with any tobacco exposure tended to be younger (mean age 37.7 [SD 12.4] years vs 40.3 [11.2] years), non-Hispanic Black (27.8% vs. 15.1%), lower educated (41.8% vs. 29.4%), and have lower family income (39.9% vs. 23.5%). After adjustment, the odds of having HR-HPV infection were 1.32 (95% CI, 1.09–1.59) for those exposed to tobacco, remaining significant in multiple sensitivity analyses and across subgroups. This study, based on a nationally representative sample from the United States, suggests that tobacco exposure is a risk factor for elevated HR-HPV infection in women, highlighting the need for further research into reducing this modifiable risk factor.

Study of filtration, digestion and absorption of Chlorella pyrenoidosa by juvenile Chinese mitten crab (Eriocheir sinensis) - Jiancheng Zeng; Jian Tian; Dongqi Kan; Cui Han; Xiaoqing Fei; Xingkong Ma; Zhihong Wang; Weijian Shen; Jiaxin Yang; Jiachun Ge (Aquaculture, 2023)

Effects of dietary trimetlylamine oxide on the growth performance, feed utilization and appetite regulation of Chinese mitten crab (Eriocheir sinensis) - Mengge Li; Anran Wang; Xue Lin; Hanfeng Miao; Xuran Liu; Jie Xu; Xingkong Ma; Yingke Wu; Xiaojing Dong; Jiachun Ge; Shuyan Miao (Aquaculture, 2023)

Sustainable poverty reduction models for the coordinated development of the social economy and environment in China - Yong Ge; Shan Hu; Yongze Song; Hua Zheng; Yansui Liu; Xinyue Ye; Ting Ma; Mengxiao Liu; Chenghu Zhou (Science Bulletin, 2023)

Multi-omics analysis reveals the mechanism of calcium-reduced quality deterioration in mechanically injured green pepper fruit - Lili Ma; Yanyan Zheng; Zhaoze Sang; Yonghong Ge; Chunmei Bai; Anzhen Fu; Qing Wang; Christopher B. Watkins; Jinhua Zuo (Postharvest Biology and Technology, 2023)

Design and analysis of wire-driven tail fin for bionic underwater glider - Liming Ge; Wenda Ma; Shaoqiong Yang; Xiao Yu; Tongshuai Sun; Xuan Wang; Shuai Fa; Yanhui Wang (Ocean Engineering, 2023)

Copper enhanced arsenic-accumulation in As-hyperaccumulator Pteris vittata by upregulating its gene expression for As uptake, translocation, and sequestration - Chen-Jing Liu; You-Jing Peng; Chun-Yan Hu; Si-Xue He; Shu-Fen Xiao; Wei Li; Song-Ge Deng; Zhi-Hua Dai; Lena Q. Ma (Journal of Hazardous Materials, 2023)

Application of calcium peroxide for efficient treatment of surface water turbidity: Mechanisms and microbial community responses - Zihang Ma; Zuhan Ge; Kexuan Liu; Cong Wang; Tao Wu; Jibiao Zhang (Journal of Environmental Chemical Engineering, 2023)

Effect of different size microplastic particles on the construction of algal-bacterial biofilms and microbial communities - Xinye Gong; Zuhan Ge; Zihang Ma; Yaguang Li; Deying Huang; Jibiao Zhang (Journal of Environmental Management, 2023)

Transport model simulation prediction and environmental risk assessment of pyrethroid insecticides in urban artificial lakes caused by rainfall: A case study of Cloud Mountain Park in subhumid climate zone - Siyao Liu; Xuanying Li; Rui Ding; Yuwen Pan; Xiaoyu Ge; Weifang Ma (Journal of Environmental Management, 2023)

Suitable crop loading: An effective method to improve “Shine Muscat” grape quality - Jianing Li; Tingting Ma; Shihan Bao; Dingze Yin; Qian Ge; Caihong Li; Yulin Fang; Xiangyu Sun (Food Chemistry, 2023)

Toward flame-retardant, transparency, and high mechanical property of polycarbonate based on low addition of linear polyborosiloxane - Zongsheng Liu; Meng Ma; Bangdong Ge; Yi Zheng; Si Chen; Yanqin Shi; Huiwen He; Yulu Zhu; Xu Wang (Chemical Engineering Journal, 2023)

Simple preparation of monolithic N-doped electrode for efficient EF remediation of petrochemical wastewater: Performance, degradation pathways, and mechanism of different N-doped positions - Pei Dong; Zhenzhan Xu; Xiaolin Ma; Yingying Gu; Jinqiang Zhang; Shuaijun Wang; Yang Wang; Baosheng Ge; Chaocheng Zhao (Chemical Engineering Journal, 2023)

Climbazole causes cell apoptosis and lipidosis in the liver of grass carp - Zhi-Jie Lu; Wen-Jun Shi; Fang-Zhou Gao; Dong-Dong Ma; Jin-Ge Zhang; Si-Ying Li; Xiao-Bing Long; Qian-Qian Zhang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Beijing Children’s Hospital guidelines on the design and conduction of the first standardized database for medulloblastoma - Wei Yang; Wenping Ma; Jiansong Huang; Yingjie Cai; Xiaojiao Peng; Fengmao Zhao; Di Zhang; Zhewei Zou; Hailang Sun; Xiang Qi; Ming Ge (Metabolic Brain Disease, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

Silica mitigated calcium mineral scaling in brackish water reverse osmosis - Kai-Ge Lu; Shuanglong Ma; Dangling Hua; Hongen Liu; Chang Li; Jia Song; Haiou Huang; Yuchen Qin (Water Research, 2023)

Enhanced hydroxyl radical generation for micropollutant degradation in the In2O3/Vis-LED process through the addition of periodate - Tao Yang; Linqian An; Ge Zeng; Jiamin Mai; Yuying Li; Jinchuan Lian; Haochen Zhang; Juan Li; Xiaoxiang Cheng; Jianbo Jia; Minchao Liu; Jun Ma (Water Research, 2023)

Improving quantification of methane point source emissions from imaging spectroscopy - Zhipeng Pei; Ge Han; Huiqin Mao; Cuihong Chen; Tianqi Shi; Keyi Yang; Xin Ma; Wei Gong (Remote Sensing of Environment, 2023)

Insight into wavelength-dependent UVA-LED/chlorine process for micropollutant degradation: Performance, mechanism, and effects of water matrix - Ge Zeng; Jiamin Mai; Linqian An; Cui Huang; Juan Li; Haiping Wang; Qiuhua Li; Jingxin Yang; Xiaolong Xu; Changyu Liu; Jianbo Jia; Tao Yang; et al. (Chemical Engineering Journal, 2023)

Elucidating the elevated salinity effect on removal of carbon and nitrogen in coupling aromatic degradation to anaerobic denitrification - Xiao-chen Ma; Ke Wang; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shijie You (Chemical Engineering Journal, 2023)

A XCO Retrieval Algorithm Coupled Spatial Correlation for the Aerosol and Carbon Detection Lidar - Zhipeng Pei; Ge Han; Tianqi Shi; Xin Ma; Wei Gong (Atmospheric Environment, 2023)

Genetic mapping of the wheat leaf rust resistance gene Lr19 and development of translocation lines to break its linkage with yellow pigment - Shoushen Xu; Zhongfan Lyu; Na Zhang; Mingzhu Li; Xinyi Wei; Yuhang Gao; Xinxin Cheng; Wenyang Ge; Xuefeng Li; Yinguang Bao; Zujun Yang; Xin Ma; et al. (Theoretical and Applied Genetics, 2023)

The relative importance of environmental heterogeneity and dispersal limitation on spatial patterns of phytoplankton communities varies across seasons - Feiyang Ge; Bin Chen; Shaopeng Wang; Qianqian Zhou; Zhiyuan Ma; Guangcheng Chen; Weiwei Yu; Wenxuan Han; Senming Tang; Shangke Su; Dian Zhang; Wanting Zhang; et al. (Limnology and Oceanography, 2023)
Environmental heterogeneity and dispersal limitation structure community assembly, but there is limited knowledge on how their effects vary on temporal scale. This study compiled a series of data, including phytoplankton, seawater depth and chemistry from 104 sites, to explore the spatial patterns and their drivers of phytoplankton communities in the Beibu Gulf and adjacent waters, located in the northwestern South China Sea. Our results showed that (1) the beta diversity values ranged from 0.2 to 0.84 (0.5 average), and turnover dominated. (2) The relative contributions of environmental heterogeneity and dispersal limitation to beta diversity varied seasonally, wherein former dominated in summer and winter, latter dominated in spring and autumn. (3) Hydrologic distance, pH, alkalinity, and total nitrogen were the crucial factors shaping the beta diversity pattern. This study detailed the temporal variation of the relative roles of environmental heterogeneity and dispersal limitation in shaping the patterns of phytoplankton communities, which may reflect the dynamical nature of ocean, characterized by seasonal variation in wind and hydrology. It also clarified the intrinsic linkage between these two processes in the ocean, which provides a novel insight to understanding the ocean biogeography and informs decision making for area‐based marine biodiversity conservation.

MiR-425-5p suppression of Crebzf regulates oocyte aging via chromatin modification - Kadiliya Jueraitetibaike; Ting Tang; Rujun Ma; Shanmeizi Zhao; Ronghua Wu; Yang Yang; Xuan Huang; Xi Cheng; Cheng Zhou; Hong Zhang; Lu Zheng; Xie Ge; et al. (GeroScience, 2023)
Female infertility due to declining oocyte quality with age remains a significant challenge for patients and physicians, despite extensive research efforts. Recent studies suggest that microRNAs (miRNAs), which respond to various stressors in the aging process, may provide a promising solution. With the approval of small RNA drugs for clinical use, miRNA-based treatment of oocyte aging appears to be a viable option. Through high-throughput sequencing, miR-425-5p was identified as the only miRNA elevated under natural aging and oxidative stress. Microinjection of inhibitors to inhibit miR-425-5p effectively improved compromised phenotypes of old oocytes in vitro. Further investigation revealed that Crebzf acts as a mediator of miR-425-5p 's age-related functions in old oocytes. In vivo treatment with miR-425-5p antagomirs significantly improved impaired oocyte development in reproductively old females by targeting Crebzf . Single-cell RNA sequencing revealed that Crebzf plays a vital role in regulating mRNAs targeting histone H3, trimethylated lysine 4 (H3K4me3), a crucial marker for transcriptional silencing. Overexpression of miR-425-5p could hinder oocyte maturation by downregulating Crebzf expression and disrupting transcriptional regulation. Our findings provide new insights into the potential of miR-425-5p antagomirs as a treatment for female infertility and highlight an elegant mechanism by which miR-425-5p inhibition of Crebzf inhibits a developmental switch in GV oocytes by regulating a group of histone methyltransferase mRNAs.

Hydrochemical characteristics of groundwater in a plain river network region: Establishing linkages between source and water quality variables - Ning Ma; Li Gao; Zhengkui Ge; Ming Li (Chemosphere, 2023)

The overlooked role of Cr(VI) in micropollutant degradation under solar light irradiation - Tao Yang; Cui Huang; Linqian An; Ge Zeng; Juan Li; Changyu Liu; Xiaolong Xu; Jianbo Jia; Jun Ma (Water Research, 2023)

Efficient removal of p-arsanilic acid and arsenite by Fe(II)/peracetic acid (Fe(II)/PAA) and PAA processes - Tao Yang; Linqian An; Ge Zeng; Maoju Jiang; Juan Li; Changyu Liu; Jianbo Jia; Jun Ma (Water Research, 2023)

In-situ pyrolysis kinetic analysis and fixed-bed pyrolysis behavior of ex-service wind turbine blades - Yuqing Wu; Zefeng Ge; Chen Huang; Zhenting Zha; Mingxun Zeng; Yuna Ma; Lijuan Sun; Zenghui Hou; Sheng Chu; Huiyan Zhang (Waste Management, 2023)

Gasification characteristics and synergistic effects of typical organic solid wastes under CO2/steam atmospheres - Yuna Ma; Zhenting Zha; Chen Huang; Zefeng Ge; Mingxun Zeng; Huiyan Zhang (Waste Management, 2023)

Comparative analysis of the molecular response characteristics in Platycodon grandiflorus irradiated with heavy ion beams and X-rays - Xiao Liu; Yan Du; Chaoli Xu; Fusheng Wang; Xuehu Li; Luxiang Liu; Xiaohui Ma; Yuanmeng Wang; Linghui Ge; Weibin Ren; Ling Jin; Libin Zhou (Life Sciences in Space Research, 2023)

Constructing branch architectures on fly ash surfaces to immobilize iron tetracarboxy phthalocyanine for synergistic degradation of dye contaminants - Peng Zhang; Na Wei; Jinqiang Wu; Qingyuan Liu; Lianfeng Yang; Shixun Zu; Chunhui Liu; Yun Li; Dapeng Li; Suxiang Ge; Juntao Ma (Journal of Cleaner Production, 2023)

Eating with peel or not: Investigation of the peel consumption situation and its nutrition, risk analysis, and dietary advice in China - Qinyu Zhao; Qian Ge; Yi Shang; Mingyuan Zheng; Xiangyu Sun; Shihan Bao; Yulin Fang; Zhenwen Zhang; Tingting Ma (Food Research International, 2023)

Hepatotoxicity screening and ranking of structurally different pyrrolizidine alkaloids in zebrafish - Yueyang Pan; Jiang Ma; Hui Zhao; Peter P. Fu; Ge Lin (Food and Chemical Toxicology, 2023)

Creation of surface frustrated Lewis pairs on high-entropy spinel nanocrystals that boosts catalytic transfer hydrogenation reaction - Mingwei Ma; Liping Li; Ge Tian; Zhibin Geng; Xin Zhang; Xu Zhao; Guangshe Li (Chemical Engineering Journal, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Spatial organization and connectivity of wood rays in Pinus massoniana xylem based on high-resolution μCT-assisted network analysis - Lingyu Ma; Qiulu Meng; Xiaomei Jiang; Zhedong Ge; Zixiong Cao; Yupei Wei; Lichao Jiao; Yafang Yin; Juan Guo (Planta, 2023)

Role of Bmal1 in Type 2 Diabetes Mellitus-Related Glycolipid Metabolic Disorder and Neuropsychiatric Injury: Involved in the Regulation of Synaptic Plasticity and Circadian Rhythms - Xinran Gao; Yadong Wei; Huaizhi Sun; Shengwei Hao; Mengdie Ma; Huimin Sun; Dandan Zang; Congcong Qi; Jinfang Ge (Molecular Neurobiology, 2023)

Geographical Information Visualization on a Panoramic Sphere in an Immersive Environment - Ying Ma; Fenglin Tian; Wen Liu; Moran Tang; Jinyu Li; Ge Chen (Journal of Ocean University of China, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Kuo-Jian Ma; Yong-Lian Ye; Yun-Han Fu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota , Pseudomonadota , Bacillota , and Actinomycetota . It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota . Three Bacteroidota strains, M17 T , M82 T , and M415 T , isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17 T and Mangrovivirga cuniculi KCTC 72349 T was 99.28%, and less than 90.09% with other species; strain M82 T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252 T , and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17 T and M82 T represent novel species within the genus Mangrovivirga and Pontibacter , respectively, and strain M415 T represents a novel species of a novel genus within the family Flavobacteriaceae . The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17 T and M82 T were found to be higher than those in Flavobacteriales sp. M415 T . Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.

Properties and Model of a Lacustrine Shale Oil Reservoir: A Case Study of the Upper Fourth Member and Lower Third Member of the Shahejie Formation in Dongying Sag and Zhanhua Sag, Jiyang Depression - Cunfei Ma; Xianxu Fang; Xiaonan Ma; Xiantai Liu; Bingkun Xu; Xinmin Ge (Journal of Marine Science and Engineering, 2023)
By combining thermal simulation experiments with core data, thin sections, scanning electron microscopy (SEM), source rock, and high-pressure mercury and gas adsorption analysis, this paper evaluates the properties and models of shale reservoirs in the upper fourth member and the lower third member of the Shahejie Formation in Dongying Sag and Zhanhua Sag. The results show that the oil shale is a high-quality source rock with petroleum generation potential. Inorganic mineral pores, organic pores, and fractures have developed with petroleum storage capacity. Clay and organic-rich soft shale lithofacies are interbedded with carbonate-rich hard shale lithofacies to form sandwich-type source–reservoir–caprock assemblages with internal sealing properties. Bitumen occurs mostly in the free state, and to a lesser extent is adsorbed, and shows flow characteristics. The migration resistance of the bitumen is displacement pressure, including capillary force and adsorption resistance, and the main force is pore fluid pressure. The migration modes of the bitumen include both subcritical flow and instantaneous flow, which are controlled by pore fluid pressure, displacement pressure, and the rock’s fracture strength. Owing to the multi-scale characteristics of the shale reservoir space, a vein-type model of a multi-scale progressive transport network is developed that obeys Murray’s law with a dominant migration pathway in the shale reservoir. The shale oil reservoir is a special lithologic reservoir controlled by the sedimentary environment and has self-generation, self-storage, and self-sealing characteristics with developed pore fluid overpressure and a multi-scale transport network.

Spatiotemporal dynamics of near-surface ozone concentration and potential source areas in northern China during 2015—2020 - Kang Ma; Yuesheng Lin; Fengman Fang; Huarong Tan; Jingwen Li; Lei Ge; Fei Wang; Youru Yao (Environmental Science and Pollution Research, 2023)

Inhibited expression of amylases and cellulases in crabs with hepatopancreatic necrosis disease and their regulation by EcR and HR38 - Qian Ren; Yuqi Zhao; Xingkong Ma; Jiachun Ge; Xin Huang (Frontiers in Marine Science, 2023)
Hepatopancreatic necrosis disease (HPND) is a serious threat to the stable and sustainable development of the Chinese mitten crab farming industry. Studies have found that the hepatopancreas is the main lesion organ in HPND crabs, capable of causing metabolic abnormalities and non-feeding (starvation state). Here, four amylases (named as EsAmy1-4 ) and four cellulases (endo-beta-1, 4-glucanase, named as EsGlu1-4 ) that relate to carbohydrate metabolism were cloned from Eriocheir sinensis . Our studies found that the expressions of EsAmy1-4 and EsGlu1-4 were significantly decreased in the hepatopancreas of crabs with HPND. Moreover, the expressions of two important regulatory factors of carbohydrate metabolism, hormone receptor 38 ( EsHR38 ) and ecdysone receptor ( EsEcR ), were remarkably decreased in the hepatopancreas of crabs with HPND. Further studies found that knockdown of EsHR38 and EsEcR could down-regulated the expressions of EsAmy1-4 and EsGlu1-4 . In addition, downregulation of EsEcR could decrease the expression of EsHR38 . Hence, HPND causes down-regulation of EsEcR expression, inhibits the transcription of EsHR38 , further inhibits the expression of EsAmy1-4 and EsGlu1-4 , and then leads to the abnormal carbohydrate metabolism. The abnormalities of carbohydrate metabolism may result in the abnormal food intake in crabs. This study provides new evidence for further understanding the mechanism of HPND.

Revisiting effective Lewis number of combustible mixtures - Lu-Qing Wang; Yun Ge; Hong-Hao Ma (Fuel, 2023)

Pt@TiO /TiO2 as a highly effective and stable recipe for C3H8 and C3H6 combustion - Jiali Zhou; Ge Li; Hongfei Li; Ziran Ma; Shuang Liu; Xiaolong Tang (Fuel, 2023)

Constructing dendrite suppressing mixed sulfide solid electrolyte for high-rate lithium metal batteries - Zeyu Ge; Nanshan Chen; Rui Wang; Rui Ma; Bo Fan; David Le coq; Xianghua Zhang; Hongli Ma; Bai Xue (Chemical Engineering Journal, 2023)

Southwestern Atlantic ocean fronts detected from the fusion of multi-source remote sensing data by a deep learning model - Zhi Wang; Ge Chen; Chunyong Ma; Yalong Liu (Frontiers in Marine Science, 2023)
In the Southwestern Atlantic, the Falkland Current intrudes onto the South American shelf, resulting in the meeting of two water masses which are completely different in temperature and dynamic characteristics, thus generating the Southwestern Atlantic Front (SAF). Therefore, the SAF has prominent characteristics of thermal and dynamics. The current ocean front detection is mainly by performing gradient operations on sea surface temperature (SST) data, where regions with large temperature gradients are considered as ocean fronts. The thermal gradient method largely ignores the dynamical features, leading to inaccurate manifestation of SAF. This study develops a deep learning model, SAFNet, to detect the SAF through the synergy of 10-year (2010-2019) satellite-derived SST and sea surface height (SSH) observations to achieve high accuracy detection of SAF with fused thermal and dynamic characteristics. The comparative experimental results show that the detection accuracy of SAFNet reaches 99.45%, which is significantly better than other models. By comparing the frontal probability (FP) obtained by SST, SSH and SST-SSH fusion data respectively, it is proved that the necessity of fusion multi-source remote sensing data for SAF detection. The detection results of fusion data can reflect the spatial distribution of SAF more comprehensively and accurately. According to the meridional variation of FP, the main reason for the seasonal variation of the SAF is the change in its thermal characteristics, and the SAF has stable dynamic characteristics.

Organophosphate esters in the seawater of the Bohai Sea: Environmental occurrence, sources and ecological risks - Rongguang Xing; Peng Zhang; Nan Zheng; Hao Ji; Ren Shi; Linke Ge; Hongrui Ma (Marine Pollution Bulletin, 2023)

Compound and successive events of extreme precipitation and extreme runoff under heatwaves based on CMIP6 models - Peng Sun; Yifan Zou; Rui Yao; Zice Ma; Yaojin Bian; Chenhao Ge; Yinfeng Lv (Science of The Total Environment, 2023)

Chemical conversions of free phytosterols during the bleaching of corn oil - Ge Bai; Chuan-Guo Ma; Yu-Yuan Hu; Shu-Jing Guo; Tong Wang (Food Chemistry, 2023)

A study of long-term toxicity of multiple mixtures with hormetic effects by the characteristic parameter σ() and stepwise method - Na Wang; Jiajing Sun; Xiaoyan Ma; Xinyue Yang; Xiaochang Wang; Yujiao Zhang; Jinhong Zhou; Jiaxuan Wang; Chengmin Ge (Environmental Toxicology and Pharmacology, 2023)

MCSTNet: a memory-contextual spatiotemporal transfer network for prediction of SST sequences and fronts with remote sensing data - Ying Ma; Wen Liu; Ge Chen; Guoqiang Zhong; Fenglin Tian (Frontiers in Marine Science, 2023)
Ocean fronts are a response to the variabilities of marine hydrographic elements and are an important mesoscale ocean phenomenon, playing a significant role in fish farming and fishing, sea-air exchange, marine environmental protection, etc. The horizontal gradients of sea surface temperature (SST) are frequently applied to reveal ocean fronts. Up to now, existing spatiotemporal prediction approaches have suffered from low prediction precision and poor prediction quality for non-stationary data, particularly for long-term prediction. It is a challenging task for medium- and long-term fine-grained prediction for SST sequences and fronts in oceanographic research. In this study, SST sequences and fronts are predicted for future variation trends based on continuous mean daily remote sensing satellite of SST data. To enhance the precision of the predicted SST sequences and fronts, this paper proposes a novel memory-contextual spatiotemporal transfer network (MCSTNet) for SST sequence and front predictions. MCSTNet involves three components: the encoder-decoder structure, a time transfer module, and a memory-contextual module. The encoder-decoder structure is used to extract the rich contextual and semantic information in SST sequences and frontal structures from the SST data. The time transfer module is applied to transfer temporal information and fuse low-level, fine-grained temporal information with high-level semantic information to improve medium- and long-term prediction precision. And the memory-contextual module is employed to fuse low-level, spatiotemporal information with high-level semantic information to enhance short-term prediction precision. In the training process, mean squared error (MSE) loss and contextual loss are combined to jointly guide the training of MCSTNet. Extensive experiments demonstrate that MCSTNet predicts more authentic and reasonable SST sequences and fronts than the state-of-the-art (SOTA) models on the SST data.

Lipidomic analysis revealed dynamic changes of lipidic compounds of postharvest strawberry in response to gray mold - Quan Ma; Xinwei Wu; Zisheng Luo; Zhiwei Ge; Dong Li; Di Wu; Xiaochen Zhang; Yanpei Chen; Li Li; Yanqun Xu (Postharvest Biology and Technology, 2023)

Photolysis of chlorite by solar light: An overlooked mitigation pathway for chlorite and micropollutants - Tao Yang; Mengyang Zhu; Linqian An; Ge Zeng; Chengqian Fan; Juan Li; Jin Jiang; Jun Ma (Water Research, 2023)

Associations of selenium exposure with blood lipids: Exploring mediating DNA methylation sites in general Chinese urban non-smokers - Xiuquan Nie; Ge Mu; Yanjun Guo; Shijie Yang; Xing Wang; Zi Ye; Qiyou Tan; Mengyi Wang; Min Zhou; Jixuan Ma; Weihong Chen (Science of The Total Environment, 2023)

GhMYB102 promotes drought resistance by regulating drought-responsive genes and ABA biosynthesis in cotton (Gossypium hirsutum L.) - Ruida Liu; Yanhui Shen; Minxuan Wang; Ruihua Liu; Ziqian Cui; Pengzhen Li; Qidi Wu; Qian Shen; Jing Chen; Siping Zhang; Shaodong Liu; Huijuan Ma; et al. (Plant Science, 2023)

Using environmentally friendly technology for fabricating special plywood with ultra-high strength - Shida Zuo; Yunyi Liang; Yingji Wu; Shengbo Ge; Jiangtao Shi; Xinxin Ma; Liping Cai; Jianzhang Li; Su Shiung Lam; Changlei Xia (Journal of Cleaner Production, 2023)

Deciphering the fate of osmotic stress priming on enhanced microorganism acclimation for purified terephthalic acid wastewater treatment with high salinity and organic load - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Bioresource Technology, 2023)

Optical Coherence Tomography in Cerebrovascular Disease: Open up New Horizons - Ran Xu; Qing Zhao; Tao Wang; Yutong Yang; Jichang Luo; Xiao Zhang; Yao Feng; Yan Ma; Adam A. Dmytriw; Ge Yang; Shengpan Chen; Bin Yang; et al. (Translational Stroke Research, 2023)

GWAS across multiple environments and WGCNA suggest the involvement of ZmARF23 in embryonic callus induction from immature maize embryos - Tianhu Liang; Yu Hu; Na Xi; Minyan Zhang; Chaoying Zou; Fei Ge; Guangsheng Yuan; Shibin Gao; Suzhi Zhang; Guangtang Pan; Langlang Ma; Thomas Lübberstedt; et al. (Theoretical and Applied Genetics, 2023)

Transcriptomics, metabolomics, antioxidant enzymes activities and respiration rate analysis reveal the molecular responses of rice to Cd stress and/or elevated CO2 concentration - Lanlan Wang; Ge Wang; Jinghui Cui; Xuhao Wang; Meng Li; Xiufen Qi; Xuemei Li; Yueying Li; Lianju Ma (Plant and Soil, 2023)

Study on the dust migration law and a spray dust suppression scheme in transportation roadway - Deji Jing; Mingxing Ma; Shaocheng Ge; Tian Zhang; Xiangxi Meng; Shuaishuai Ren (Environmental Science and Pollution Research, 2023)

Full genome sequence of a novel iflavirus from the aster leafhopper Macrosteles fascifrons - Jiajing Xiao; Kai Zhu; Rui Ma; Chunmin Zhang; Keliang Lv; Danfeng Ge; Renyi Liu (Virus Genes, 2023)

Applications of bioremediation and phytoremediation in contaminated soils and waters: CREST publications during 2018–2022 - Chen-Jing Liu; Song-Ge Deng; Chun-Yan Hu; Peng Gao; Eakalak Khan; Chang-Ping Yu; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2023)

Chronic oral exposure to short chain chlorinated paraffins induced testicular toxicity by promoting NRF2-mediated oxidative stress - Zhang Qian; Chuwei Li; Wei Zhao; Zhaowanyue He; Mengqi Xue; Shuxian Wang; Xi Cheng; Rujun Ma; Xie Ge (Toxicology Letters, 2023)

Adaptive reinforcement learning fault-tolerant control for AUVs With thruster faults based on the integral extended state observer - Zhifu Li; Ming Wang; Ge Ma; Tao Zou (Ocean Engineering, 2023)

Short-term impacts of air pollution on the platelet-lymphocyte ratio and neutrophil-lymphocyte ratio among urban adults in China - Weihong Qiu; Heng He; Bin Wang; Dongming Wang; Ge Mu; Tao Xu; Min Zhou; Zi Ye; Jixuan Ma; Weihong Chen (Journal of Environmental Sciences, 2023)

Morphology evolution regulation of dual-doped S, Fe-NiMoO4 microrods based on precipitation-dissolution equilibrium for oxygen evolution - Meng-Xuan Li; Bo Xiao; Zi-Yi Zhao; Yu Ma; Ya-Nan Zhou; Xin-Yu Zhang; Feng-Ge Wang; Yong-Ming Chai; Bin Dong (Fuel, 2023)

A novel sulfated mannan-carboxymethyl-5-fluorouracil-folic acid conjugates for targeted anticancer drug delivery - Nan Ma; Mi-Hye Kwon; Subramanian Palanisamy; Yunfei Ge; Yutong Zhang; Fang Kou; Lee Dae-Hee; Dong-Jin Lee; Il-Shik Shin; SangGuan You (Carbohydrate Polymers, 2023)

The growth toxicity and neurotoxicity mechanism of waterborne TBOEP to nematodes: Insights from transcriptomic and metabolomic profiles - Jingjuan Ju; Xinyue Wu; Weiya Mao; Chenran Zhang; Wenjie Ge; Yiran Wang; Siyang Ma; Ya Zhu (Aquatic Toxicology, 2023)

Extreme wind speed prediction in mountainous area with mixed wind climates - Teng Ma; Wei Cui; Lin Zhao; Ding Yejun; Fang Genshen; Yaojun Ge (Stochastic Environmental Research and Risk Assessment, 2023)

Trace elements in outdoor and indoor PM2.5 in urban schools in Xi’an, Western China: characteristics, sources identification and health risk assessment - Runyu Wang; Xinxin Ding; Jingzhi Wang; Zhibao Dong; Hongmei Xu; Ge Ma; Bo Gao; Han Song; Menghan Yang; Junji Cao (Environmental Geochemistry and Health, 2023)

Imbalanced phytoplankton C, N, P and its relationship with seawater nutrients in Xiamen Bay, China - Xiaoqian Lu; Weiwei Yu; Bin Chen; Zhiyuan Ma; Guangcheng Chen; Feiyang Ge; Shenqun An; Wenxuan Han (Marine Pollution Bulletin, 2023)

A systematic review, meta-analysis and meta-regression of the global prevalence of foodborne Vibrio spp. infection in fishes: A persistent public health concern - Jun-Yang Ma; Xin-Kun Zhu; Ren-Ge Hu; Ze-Zheng Qi; Wen-Chao Sun; Zhi-Peng Hao; Wei Cong; Yuan-Huan Kang (Marine Pollution Bulletin, 2023)

Mixed bromine/chlorine transformation products of tetrabromobisphenol A formed in the combustion of printed circuit boards: Emission characteristics and transformation pathways - Xiang Ge; Yanpeng Gao; Yan Yang; Guanhui Chen; Shengtao Ma; Beibei Hu; Yingxin Yu; Taicheng An (Science of The Total Environment, 2023)

Decreasing summer monsoon precipitation during the Mid-Pleistocene transition revealed by a pollen record from lacustrine deposits of the Northeast Plain of China - Tao Zhan; Ye Yang; Yanxia Liang; Xiaoyan Liu; Fangming Zeng; Junyi Ge; Yongfa Ma; Keliang Zhao; Xinying Zhou; Xia Jiang; Rongfu Huang; Xun Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Photodegradation of hydroxyfluorenes in ice and water: A comparison of kinetics, effects of water constituents, and phototransformation by-products - Linke Ge; Shengkai Cao; Crispin Halsall; Junfeng Niu; Dongxiao Bai; Guangkai He; Peng Zhang; Hongrui Ma (Journal of Environmental Sciences, 2023)

Flexible quasi-3D zinc ion microcapacitor based on V2O5-PANI cathode and MXene anode - Ao Li; Zhichao Wei; Yongxin Wang; Yuhang Zhang; Mengjie Wang; Hongyun Zhang; Yanan Ma; Chenxu Liu; Junjie Zou; Binghui Ge; Feng Cheng; Yang Yue (Chemical Engineering Journal, 2023)

Genome-wide association study identifies GhSAL1 affects cold tolerance at the seedling emergence stage in upland cotton (Gossypium hirsutum L.) - Qian Shen; Siping Zhang; Changwei Ge; Shaodong Liu; Jing Chen; Ruihua Liu; Huijuan Ma; Meizhen Song; Chaoyou Pang (Theoretical and Applied Genetics, 2023)

The home-field advantage of litter decomposition in lake wetlands and the community characteristics of bacterial and eukaryotic decomposers - Yantian Ma; Runfa Cai; Hui Zhong; Lan Wu; Gang Ge (Plant and Soil, 2023)

Bi/Te control on gold mineralizing processes in the North China Craton: Insights from the Wulong gold deposit - Haoxuan Feng; Ping Shen; Rixiang Zhu; Andrew G. Tomkins; Joël Brugger; Ge Ma; Changhao Li; Yang Wu (Mineralium Deposita, 2023)

Deep blue artificial intelligence for knowledge discovery of the intermediate ocean - Ge Chen; Baoxiang Huang; Jie Yang; Milena Radenkovic; Linyao Ge; Chuanchuan Cao; Xiaoyan Chen; Linghui Xia; Guiyan Han; Ying Ma (Frontiers in Marine Science, 2023)
Oceans at a depth ranging from ~100 to ~1000-m (defined as the intermediate water here), though poorly understood compared to the sea surface, is a critical layer of the Earth system where many important oceanographic processes take place. Advances in ocean observation and computer technology have allowed ocean science to enter the era of big data (to be precise, big data for the surface layer, small data for the bottom layer, and the intermediate layer sits in between) and greatly promoted our understanding of near-surface ocean phenomena. During the past few decades, however, the intermediate ocean is also undergoing profound changes because of global warming, the research and prediction of which are of intensive concern. Due to the lack of three-dimensional ocean theories and field observations, how to remotely sense the intermediate ocean from space becomes a very attractive but challenging scientific issue. With the rapid development of the next generation of information technology, artificial intelligence (AI) has built a new bridge from data science to marine science (called Deep Blue AI, DBAI), which acts as a powerful weapon to extend the paradigm of modern oceanography in the era of the metaverse. This review first introduces the basic prior knowledge of water movement in the ~100 m ocean and vertical stratification within the ~1000-m depths as well as the data resources provided by satellite remote sensing, field observation, and model reanalysis for DBAI. Then, three universal DBAI methodologies, namely, associative statistical, physically informed, and mathematically driven neural networks, are elucidated in the context of intermediate ocean remote sensing. Finally, the unique advantages and potentials of DBAI in data mining and knowledge discovery are demonstrated in a top-down way of “surface-to-interior” via several typical examples in physical and biological oceanography.

Temperature-regulated and starvation-induced refractory para-toluic acid anaerobic biotransformation - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Chemosphere, 2023)

Insights into the accumulation, distribution and toxicity of pyrene associated with microplastics in rice (Oryza sativa L.) seedlings - Lili Tian; Li Ya Ma; Xiaolong Chen; Jing Ge; Yini Ma; Rong Ji; Xiangyang Yu (Chemosphere, 2023)

Cytotoxic shornephines and asterresins from the hydrothermal vent associated fungus Aspergillus terreus CXX-158-20 - Jihua Wei; Xuexia Chen; Yichao Ge; Qizhao Yin; Yihan Ma; Zunjing Zhang; Xiaodan Wu; Kui Hong; Bin Wu (Phytochemistry, 2023)

A clarification of concepts related to the digestion and absorption of carotenoids and a new standardized carotenoids bioavailability evaluation system - Tonghui Geng; Shihan Bao; Xiangyu Sun; Dexue Ma; Hexin Zhang; Qian Ge; Xuebo Liu; Tingting Ma (Food Chemistry, 2023)

Ultralight carbon aerogel composites derived from MOFs and cross-linked chitosan: Synthesis, characterization, and U(VI) adsorption - Yanbing Sun; Jianfa Chen; Yixiao Kang; Haoyan Zhang; Yulin Ge; Nan Yuan; Yubo Xing; Wei Ma; Zhen Yang; Liping Zou; Liang Lu (Chemical Engineering Journal, 2023)

Engineered anti-cancer nanomedicine for synergistic ferroptosis-immunotherapy - Xinyu Zhang; Haiyan Ge; Yanling Ma; Linlin Song; Yansong Ma; Guanglong Tian; Lei Wang; Qingwei Meng; Xiao Sun (Chemical Engineering Journal, 2023)

The direct modification of metal Cu interface for high-performing solid-state anode via KCu7S4/Cu7S4 interconversion mechanism - Tianyi Gao; Tianyu xiao; Yunshuang Ge; Shuai Zhang; Zimeng Wang; Zhongyu Wang; Zhipeng Ma; Wenfeng Guo; Yuqian Fan (Chemical Engineering Journal, 2023)

Temporal change of plankton size structure preserved by Lugol’s solution: a FlowCAM study - Zijia Liu; Yuan Dong; Qian P. Li; Zhengchao Wu; Zaiming Ge; Mengzhen Ma (Journal of Oceanology and Limnology, 2023)

A Time-course Transcriptional Kinetics of Genes in Behavior, Cortisol Synthesis and Neurodevelopment in Zebrafish Larvae Exposed to Imidacloprid and Thiamethoxam - Jin-Ge Zhang; Dong-Dong Ma; Si-Ying Li; Xiao-Bing Long; Fang Liu; Zhi-Jie Lu; Wen-Jun Shi (Bulletin of Environmental Contamination and Toxicology, 2023)

The signal-to-cutoff ratios to predict HCV infection among people who inject drugs - Bing Chen; Ling-yu Gao; Zhong-hui Ma; Hao Chang; Li-jian Pei; Qiang Zhou; Wen-ge Xing (VirusDisease, 2022)

Isoflurane Preconditioning May Attenuate Cardiomyocyte Injury Induced by Hypoxia/Reoxygenation Possibly by Regulating miR-363-3p - Yanhu Ge; Chengbin Wang; Boqun Cui; Yaguang Liu; Duomao Lin; Liang Zhang; Liyun Zhao; Jun Ma (Neurotoxicity Research, 2022)

Overlapping-calibration of wide-swath altimeter baseline errors using two satellites formation flying design - Chunyong Ma; Xuan Wang; Zhanwen Gao; Zheng Li; Chaofang Zhao; Ge Chen (Frontiers in Marine Science, 2022)
The sea surface height (SSH) measured by future wide-swath altimetry satellites contains observation error due to baseline measurement, which is called SSH_Error_Baseline. It is a huge challenge for satellite engineering to maintain such high accuracies of the baseline roll and length in orbit to ensure that the SSH_Error_Baseline can be maintained below 1 cm. Therefore, how to effectively reduce the SSH_Error_Baseline is extremely important. In order to solve the existing problem, an innovative overlapping-calibration method is proposed based on two-satellite formation flight design with overlapping swath. In this study, the differences of SSH data observed by these two satellites in the overlapping area is so small that it can be ignored, and the SSH_Error_Baseline dominates the difference. Then, the baseline parameters of the two satellites can be well estimated by adopting an optimal inverse method. A total of 9 groups of observing system simulation experiments (OSSEs) have been carried out, and they respectively indicate different pessimistic theoretical scenarios of baseline measurement systems. According to the results, this design can effectively reduce the SSH_Error_Baseline in most scenarios. Regarding the advantage of this method, it can be applied to all along-track observation data without requiring the application of additional auxiliary data (i.e. model data, SSH derived from nadir altimetry). Therefore, when two wide-swath altimetry satellites are simultaneously designed, the formation flight scheme proposed in this paper is recommended, especially when the measurements of the baseline cannot meet the expected accuracies.

Source and composition analysis of petroleum hydrocarbons in the refinery circulating water - Ge Ma; Han Xiao; Xinming Wei; Anshan Xiao; Xiaoying Sun; Xiang Gao (Environmental Science and Pollution Research, 2022)

Intercropping improves soil ecosystem multifunctionality through enhanced available nutrients but depends on regional factors - Huaiying Ma; Jie Zhou; Junyong Ge; Jiangwen Nie; Jie Zhao; Zhiqiang Xue; Yuegao Hu; Yadong Yang; Leanne Peixoto; Huadong Zang; Zhaohai Zeng (Plant and Soil, 2022)

Obesity aggravated hippocampal-dependent cognitive impairment after sleeve gastrectomy in C57/BL6J mice via SIRT1/CREB/BDNF pathway - Yuanyuan Ma; Yelong Ji; Li Xu; Zheng Li; Shengjin Ge (Experimental Brain Research, 2022)

Combination of bicarbonate and low temperature stress induces the biosynthesis of both arachidonic and docosahexaenoic acids in alkaliphilic microalgae Dunaliella salina HTBS - Zhile Guo; Yuyong Hou; Zhiyong Liu; Yanbo Ma; Tong Han; Nahui Hao; Yuanjiang Yao; Chunxuan Lan; Tongling Ge; Maliheh Safavi; Weijie Wang; Lei Zhao; et al. (Frontiers in Marine Science, 2022)
High bicarbonate levels and low temperature may have an impact on microalgae cultivation. However, changes in cellular composition in response to the combination of the above stresses are still poorly understood. In this study, the combined effects of bicarbonate and low temperature on biochemical changes in alkaliphilic microalgae Dunaliella salina HTBS were investigated. Comparing to the control condition of 25°C without bicarbonate, the cell density was increased from 0.69 to 1.18 in the treatment condition of 0.15 M bicarbonate and low temperature (16 °C) while the lipid\protein\carbohydrate contents were increased from 34.71% to 43.94%, 22.44% to 26.03%, 22.62% to 29.18%, respectively. Meanwhile, the PUFAs, arachidonic acid (AA) and docosahexaenoic acid (DHA) contents reached to 3.52% and 4.73% with the combination of low temperature and bicarbonate, respectively, whereas they were not detected when the cells were treated with single condition. Moreover, both the chlorophyll and carotenoid contents were also detected with increased profiles in the combined treatments. As a result, the maximum photochemical efficiency but not reduced non-photochemical quenching was strengthened, which enhanced the photosynthetic performance. Additionally, our results indicated that D. salina HTBS could acclimate to the combined stress by up-regulating the activity of SOD\CAT and reducing MDA content. These findings demonstrated that the addition of a certain bicarbonate under low temperature could effectively enhance the biomass production and accumulation of AA and DHA, which would benefit the development of the microalgae industry in value-added products.

Assessment of the inhalation exposure and incremental lifetime cancer risk of PM2.5 bounded polycyclic aromatic hydrocarbons (PAHs) by different toxic equivalent factors and occupancy probability, in the case of Xi’an - Yumeng Wang; Zedong Wang; Jingzhi Wang; Runyu Wang; Xinxin Ding; Neil McPherson Donahue; Zhibao Dong; Ge Ma; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2022)

Genome-wide association study reveals that GhTRL1 and GhPIN8 affect cotton root development - Ziqian Cui; Shaodong Liu; Changwei Ge; Qian Shen; Siping Zhang; Huijuan Ma; Ruihua Liu; Xinhua Zhao; Ruida Liu; Pengzhen Li; Hongchen Wang; Qidi Wu; et al. (Theoretical and Applied Genetics, 2022)

An Efficient Approach to Determine the Shear Damage Zones of Rock Joints Using Photogrammetry - Ding Xia; Cheng He; Huiming Tang; Yunfeng Ge; Junwei Ma; Junrong Zhang (Rock Mechanics and Rock Engineering, 2022)

Spatial variation in bacterial community and dissolved organic matter composition in groundwater near a eutrophic lake - Ning Ma; Li Gao; Yan Zhang; Zhengkui Ge; En Hu; Baozhu Pan; Jian Wang; Ming Li (Aquatic Ecology, 2022)

Real wine or not? Protecting wine with traceability and authenticity for consumers: chemical and technical basis, technique applications, challenge, and perspectives - Xiangyu Sun; Fan Zhang; Gastón Gutiérrez-Gamboa; Qian Ge; Pingkang Xu; Qianwen Zhang; Yulin Fang; Tingting Ma (Critical Reviews in Food Science and Nutrition, 2022)

Temporal shifts in the relative importance of climate and leaf litter traits in driving litter decomposition dynamics in a Chinese transitional mixed forest - Jielin Ge; Boyu Ma; Wenting Xu; Changming Zhao; Zongqiang Xie (Plant and Soil, 2022)

Precise ages of gold mineralization and pre-gold hydrothermal activity in the Baiyun gold deposit, northeastern China: in situ U–Pb dating of hydrothermal xenotime and rutile - Haoxuan Feng; Ping Shen; Rixiang Zhu; Jian-Wei Zi; David I. Groves; Changhao Li; Yang Wu; Ge Ma; Taiyang Li (Mineralium Deposita, 2022)

Production and Evaluation of a Novel Multi-Epitope Bivalent Vaccine Against Echinococcus multilocaularis Metacestode - Runle Li; Mingyuan Xin; Kunmei Liu; Bingwen Hu; Jingwei Ma; Pei Zhou; Lin Feng; Mingquan Pang; Ri-li Ge; Haining Fan; Le Guo; Feng Tang (International Journal of Peptide Research and Therapeutics, 2022)

Conditions of Mainland China’s Island Ecosystems and Associated Influencing Factors: Integrated Assessment of 42 Typical Island Ecosystems - Zhiyuan Ma; Weiwei Yu; Wanting Zhang; Feiyang Ge; Bin Chen; Wenjia Hu; Dian Zhang; Jianji Liao; Hao Huang; Yuanmin Sun; Haiping Huang (Frontiers in Marine Science, 2022)
Although China possesses a large number of islands, knowledge of their overall ecological condition is limited on a national scale. Accordingly, this study developed a comprehensive and quantitative island ecosystem assessment framework that incorporates environmental quality, biological structure, and landscape patterns. The framework was applied to 42 typical, representative islands within China’s coastal regions, including different climatic zones, area sizes, populations, and substratum lithologies. Results showed that the value range of the comprehensive index of island ecosystem condition ( CI island ) was significant (from 52.33 to 89.53, 71.72 average), and 85.4% of islands scored either “high” or “good,” indicative of their exceptional condition. However, conditions varied among different island components, indicating different challenges. Environmental quality index ( I env ) values ranged from 60.70 to 94.80 (79.72 average), where primary threats were seawater nutrient pollution, petroleum, and marine organism metal contamination. Biological structure index ( I bio ) values ranged from 43.50 to 89.40 (66.10 average), where primary threats were vegetation destruction and a reduction in marine biodiversity within intertidal and subtidal zones. Landscape pattern index ( I land ) values varied significantly (from 6 to 100, 72.36 average), where a key characteristic of highly developed islands was low natural landscape (vegetation) coverage. Conditions also varied among island climate zones, lithologies, area sizes, and levels of human habitation. Additionally, island ecosystem conditions were influenced by both natural and anthropogenic factors as well as area size, population, and GDP. Although distance to the mainland significantly correlated to ( I bio ), and ( CI island ), these parameters did not significantly correlate to ( I env ), which might be explained by that environmental quality was generally conditional on large-scale environments. This assessment is intended to provide a holistic perspective on island conditions in China while identifying key challenges and associated driving factors, which will greatly aid in establishing island-specific sustainable management practices.

Homo-harringtonine, highly effective against coronaviruses, is safe in treating COVID-19 by nebulization - Huajuan Ma; Haijun Wen; Yaoxu Qin; Shijie Wu; Ge Zhang; Chung-I Wu; Qichun Cai (Science China Life Sciences, 2022)

Climate change and ecological engineering jointly induced vegetation greening in global karst regions from 2001 to 2020 - Jing Huang; Zhongxi Ge; Yuqing Huang; Xuguang Tang; Zhan Shi; Peiyu Lai; Zengjing Song; Binfei Hao; Hong Yang; Mingguo Ma (Plant and Soil, 2022)

Nutritional Profile and Bioremediation of Tropical Marine Aquaculture with an Integrated Microalgae and Bacteria Symbiosis - Ruiyang Ma; Shiyu Xie; Huiting Jia; Linhai Pu; Licheng Peng; Chengjun Ge (Water, Air, & Soil Pollution, 2022)

Occurrence and dietary exposure risks of phthalate esters in food in the typical valley city Xi’an, Northwest China - Ge Ma; Bianbian Ma; Lijun Wang; Wendong Tao (Environmental Science and Pollution Research, 2022)

Satellite observed shape-based overall rotation—A new aspect in eddy kinematics - Xueqing Yang; Guiyan Han; Chunyong Ma; Chuanchuan Cao; Jie Yang; Ge Chen (Acta Oceanologica Sinica, 2022)

Changes in the waterbird community of the Yangtze River in the Three Gorges Reservoir Region, China, 2003–2013 - Xiuming Li; Wenfa Xiao; Ge Sun; Tian Ma; Fuguo Liu; Xiaoyun Liu; Hualong Su; Kaijun Pan; Ruimei Cheng; Fawen Qian (Biologia, 2022)

Adaptive Network Design for Multiple Gliders Observation of Mesoscale Eddy - Zhanwen Gao; Ge Chen; Yang Song; Jie Zheng; Chunyong Ma (Frontiers in Marine Science, 2022)
With its excellent endurance, good maneuverability and track controllability, glider has become one of the important equipment to obtain ocean field data. The network observation of multiple gliders will be the main approach of ocean observation in the future. However, how to plan the glider path in a reasonable way and how to design the optimal observation network consisting of multiple gliders in an eddy have not been well solved. As an effort to tackle this problem, an adaptive network design algorithm for multiple gliders in mesoscale eddies observation which referred as “Optimal Sampling” is proposed in this paper. Simulation experiments of tracking a target eddy in the South China Sea (SCS) show that the proposed algorithm cannot only realize the adaptive network design for multiple gliders, but also ensure the uniform sampling inside the eddy. Compared with the traditional method which samples eddy along a fixed path, the observation data obtained by the solution proposed in this paper are more valuable to describe the essential temperature characteristics of eddies. The residual errors computed from the interpolation of the sampled field is also smaller.

Phytoplankton Species Diversity Patterns and Associated Driving Factors in China’s Jiulong River Estuary: Roles That Nutrients and Nutrient Ratios Play - Feiyang Ge; Zhiyuan Ma; Bin Chen; Yu Wang; Xiaoqian Lu; Shenqun An; Dian Zhang; Wanting Zhang; Weiwei Yu; Wenxuan Han; Xingguang Yu; Zhenghua Liu; et al. (Frontiers in Marine Science, 2022)
Understanding diversity patterns and associated driving factors are the critical topics in macroecology and conservation biology. Phytoplankton are highly susceptible to environmental changes in estuaries, particularly eutrophication. This study examined phytoplankton alpha and beta diversity using investigation data in May (springtime), August (summer) and November (autumn) 2009 in China’s Jiulong River estuary, where it was easily polluted because of considerable discharge from a highly dense human population and low self-purification capacity with its limited river basin area, potentially resulting in eutrophication and then influencing phytoplankton diversity. Potential influencing factors were also explored, including dissolved oxygen, salinity, nutrients, nutrient ratios, geographic and hydrologic distance, and so on. The results indicated that Shannon’s index ( H’ ) and Pielou’s index ( J ) decreased from the estuary’s upper to middle and then increased from middle to lower reaches, Simpson’s ( D ) observed the opposite trend and species number ( S ) gradually increased from the estuary’s upper to lower reaches. For beta diversity, all the indices showed a gradual decrease trend from the estuary’s upper to lower reaches, where also, turnover dominated beta diversity for all seasons. It is noteworthy that the significant roles that nutrients and nutrient ratios played in shaping phytoplankton diversity patterns and the nutrient balance were characterized by excess nitrogen (N) and silicon (Si) and limited phosphorus (P), which could potentially cause diatom blooms. Findings also showed that decreasing Si concentrations can help to reduce overall pollution levels as well as the restoration of the estuary’s ecosystem better than just reducing N alone. Accordingly, this study advocates for the protection of the entire estuary system with particular emphasis on its upper reaches. Moreover, greater attention should also be paid to impacts associated with N input and nutrient ratio trade-offs to the prospective watershed management of this estuary. This study provides a practical approach to explore estuarine diversity in a comprehensive way, which can inform effective biodiversity conservation and also be applied to other marine ecosystems to better guide sustainable management and conservation practices.

Association between air pollution and emergency room visits for eye diseases and effect modification by temperature in Beijing, China - Wanzhou Wang; Wenlou Zhang; Hongxia Ge; Baiqi Chen; Jingjing Zhao; Jun Wu; Zefeng Kang; Xinbiao Guo; Furong Deng; Qingbian Ma (Environmental Science and Pollution Research, 2022)

Evaluation of Allicin Against Alveolar Echinococcosis In Vitro and in a Mouse Model - Chuanchuan Liu; Haining Fan; Lu Guan; Lan Ma; Ri-li Ge (Acta Parasitologica, 2022)
Purpose At present, the chemotherapy for alveolar echinococcosis (AE) is mainly based on albendazole (ABZ). However, more than 20% of patients fail chemotherapy. Therefore, new and more effective treatments are urgently needed. Allicin has been reported to have antibacterial and antiparasitic effects. The objectives of the present study were to investigate the in vivo and in vitro efficacy of allicin against Echinococcus multilocularis ( E. multilocularis ). Methods The effects of allicin on protoscolex survival and structural changes were evaluated in vitro . The 4-week-old BALB/c male mice used for in vivo modelling underwent inoculation of E. multilocularis protoscoleces by intraperitoneal injection, followed by intragastric administration of allicin for 6 weeks. Then, the effects of allicin on lymphocyte subsets, metacestode growth and host tissue matrix metalloproteinase 2 (MMP2)/MMP9 expression around metacestodes in mice were evaluated. The toxicity of allicin was further evaluated in vivo and in vitro . Results Att 40 μg/mL, allicin showed a killing effect on protoscoleces in vitro and treatment resulted in the destruction of protoscolex structure. Molecular docking showed that allicin could form hydrogen bonds with E. multilocularis cysteine enzymes. After 6 weeks of in vivo allicin treatment, the spleen index of mice was increased and the weight of metacestodes was reduced. Allicin increased the proportion of CD4 + T cells and decreased the proportion of CD8 + T cells in the peripheral blood and spleen. Pathological analysis of the metacestodes showed structural disruption of the germinal and laminated layers after allicin treatment. In addition, allicin inhibited the expression of MMP2 and MMP9 in metacestode-surrounding host tissues. At 160 μg/mL, allicin had no significant toxicity to normal hepatocytes but could inhibit hepatoma cell proliferation. At 30 mg/kg, allicin had no significant hepatorenal toxicity in vivo . Conclusion These results suggest that allicin exerts anti- E. multilocularis effects in vitro and in vivo and can enhance immune function in mice, with the potential to be developed as a lead compound against echinococcosis.

The premature decay of rifting processes in the northern South China Sea (38–33.9 Ma): insight from 3D seismic and its interpretation of the Lufeng Sag of the Pearl River Mouth Basin - B. S. Ma; J. W. Ge; G. H. Wu; J. F. Qi; F. Yu; S. Chen; W. G. He (Australian Journal of Earth Sciences, 2022)

miR-361-3p mitigates hypoxia-induced cardiomyocyte injury via targeting apoptosis initiators caspase-2/-8/-9 - Jinwei Zhang; Xiankun Zhou; Jing Sun; Mingzhou Li; Jideng Ma; Liangpeng Ge (In Vitro Cellular & Developmental Biology - Animal, 2022)

Fasting augments pyrrolizidine alkaloid-induced hepatotoxicity - Jiang Ma; Chunyuan Zhang; Yisheng He; Xinmeng Chen; Ge Lin (Archives of Toxicology, 2022)

G1-like PB2 gene improves virus replication and competitive advantage of H9N2 virus - Xiuli Li; Shumiao Qiao; Ying Zhao; Min Gu; Ruyi Gao; Kaituo Liu; Zhichuang Ge; Jing Ma; Xiaoquan Wang; Jiao Hu; Shunlin Hu; Xiaowen Liu; et al. (Virus Genes, 2021)

Future study for the urinary histidine adduct derived from pyrrolizidine alkaloids is warranted - Lin Zhu; Chunyuan Zhang; Jiang Ma; Yisheng He; Ge Lin (Archives of Toxicology, 2021)

Simulation and Prediction of the Spatial Dynamics of Land Use Changes Modelling Through CLUE-S in the Southeastern Region of Bangladesh - Shahidul Islam; Yuechen Li; Mingguo Ma; Anxu Chen; Zhongxi Ge (Journal of the Indian Society of Remote Sensing, 2021)

Impacts of ecological restoration on public perceptions of cultural ecosystem services - Qingyue Tan; Chen Gong; Shujie Li; Ning Ma; Fengchi Ge; Mingxiang Xu (Environmental Science and Pollution Research, 2021)

Seasonal variation of oxidative potential of water-soluble components in PM2.5 and PM1 in the Yangtze River Delta, China - Zhirao Li; Dongyang Nie; Mindong Chen; Pengxiang Ge; Zhengjiang Liu; Xiaoyun Ma; Xinlei Ge; Rui Gu (Air Quality, Atmosphere & Health, 2021)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Parallel-Dynamic Interpolation Algorithm of Sea Surface Height for Future 2D Altimetry Mapping of Sea Surface Height - Jiankai Di; Chunyong Ma; Ge Chen (Journal of Ocean University of China, 2021)

Developing urinary pyrrole–amino acid adducts as non-invasive biomarkers for identifying pyrrolizidine alkaloids-induced liver injury in human - Lin Zhu; Chunyuan Zhang; Wei Zhang; Qingsu Xia; Jiang Ma; Xin He; Yisheng He; Peter P. Fu; Wei Jia; Yuzheng Zhuge; Ge Lin (Archives of Toxicology, 2021)

Data-Driven Mapping With Prediction Neural Network for the Future Wide-Swath Satellite Altimetry - Jiankai Di; Chunyong Ma; Ge Chen (Frontiers in Marine Science, 2021)
Two-dimensional mapping of sea surface height (SSH) for future wide-swath satellite altimetry (WSA) is a challenge at present. So far, considering the utilization of data-driven methods is a new researching direction for SSH mapping. In general, the data-driven mapping methods rely on the spatial-temporal relationship of the observations. These methods require training in large volumes, and the time cost is high, especially for the WSA observations. This paper proposed the prediction neural networks for mapping (Mapping-PNN) method to improve the training efficiency and maintain stable data and mapping capabilities. By 10-year wide-swath satellite along track observing system simulation experiments (OSSEs) on the HYCOM data, the experiment results indicate that the method introduced in this paper can improve the training efficiency and meet the grid mapping expectations. Compared with other methods, the root mean squared error (RMSE) of the mapping-PNN method can be limited within the range of ~1.8 cm, and the new method can promote the observation of the ocean phenomena scale with < ~40 km, which reaches state of the art.

Variational Quality Control of Non-Gaussian Innovations in the GRAPES m3DVAR System: Mass Field Evaluation of Assimilation Experiments - Jie He; Xulin Ma; Xuyang Ge; Juanjuan Liu; Wei Cheng; Man-Yau Chan; Ziniu Xiao (Advances in Atmospheric Sciences, 2021)

Establishment of a visualized isothermal nucleic acid amplification method for on‐site diagnosis of acute hepatopancreatic necrosis disease in shrimp farm - Xiaohan Yang; Yu Dong; Chao Ma; Yi Qiao; Ge Jiang; Shiqi Chen; Jingquan Dong; Hui Shen; Song Gao (Journal of Fish Diseases, 2021)
Acute hepatopancreatic necrosis disease (AHPND) is a significant deadly infectious disease in the shrimp farming industry, causing serious economic losses globally every year. Because of the rapid progress speed, lack of effective treatment and high mortality rate of AHPND, monitoring with frequent diagnostic tests is vital for a successful prevention. The conventional histopathological diagnosis fell far short of the requirement for efficient monitoring, and the polymerase chain reaction (PCR)‐based molecular diagnostic methods that rely on sophisticated thermocycler and trained personnel are hardly applicable in the field. Combining the recombinase polymerase amplification (RPA) and the lateral flow strips (LFSs), a diagnostic method suitable for on‐site everyday monitoring of AHPND has been established in this study. This RPA‐LFS method targeted the binary toxic photorhabdus insect‐related genes PirA and PirB on a virulence plasmid of the AHPND‐causative Vibrio parahaemolyticus strains. The diagnostic test was completed within 30 min at 37°C and showed good specificity and good sensitivity of 20 fg DNA of the AHPND shrimp or one colony‐forming unit of the causative bacterium per reaction, which was better than the administration‐approved standard AP4 assay. Crude templates from sample boiling could be directly used. Tests of clinical samples showed 100% consistency of this method with the standard AP4 assay. This RPA‐LFS method can be a good choice for on‐site diagnosis of AHPND with quick response time, easy procedure and low demand for resources, and should have significant value for the control of spreading of this dangerous disease in farmed shrimp.

Ras subfamily GTPases regulate development, aflatoxin biosynthesis and pathogenicity in the fungus Aspergillus flavus - Zhuo Zhu; Gengli Ma; Mingkun Yang; Can Tan; Guang Yang; Sen Wang; Na Li; Feng Ge; Shihua Wang (Environmental Microbiology, 2021)
Summary Ras subfamily proteins are molecular switches in signal transduction pathways of many eukaryotes that regulate a variety of cellular processes. Here, the Ras subfamily, encoded by six genes, was identified in Aspergillus flavus : rasA , rasB , rasC , rab‐33 , rheb and rsr1 . The rsr1 deletion mutant (∆ rsr1 ), rheb deletion mutant (∆ rheb ) and double deletion mutant (∆ rheb/rsr1 ) displayed significantly decreased growth and sporulation. Sclerotia formation was significantly decreased for ∆ rheb or ∆ rheb/rsr1 but increased for ∆ rsr1 . Aflatoxin production was significantly increased in ∆ rheb but decreased in ∆ rsr1 and ∆ rheb/rsr1 . We found that rsr1 and rheb are crucial for the pathogenicity of A . flavus . Quantitative proteomics identified 520 differentially expressed proteins (DEPs) for the ∆ rsr1 mutant and 133 DEPs for the ∆ rheb mutant. These DEPs were annotated in multiple biological processes and KEGG pathways in A . flavus . Importantly, we identified the cytokinesis protein SepA in the protein–protein interaction network of rsr1 , and deletion mutants showed that SepA has pleiotropic effects on growth and AF biosynthesis, which may depend on Rsr1 for regulation in A . flavus . Our results indicated that these Ras subfamily proteins exhibited functional redundancy with each other but there were also differences in A . flavus .

Proteomic and Transcriptomic Analyses Reveal Pathological Changes in the Entorhinal Cortex Region that Correlate Well with Dysregulation of Ion Transport in Patients with Alzheimer’s Disease - Yangjie Jia; Xia Wang; Yanyu Chen; Wenying Qiu; Wei Ge; Chao Ma (Molecular Neurobiology, 2021)

Refractory organic compounds in coal chemical wastewater treatment by catalytic ozonation using Mn-Cu-Ce/Al2O3 - Kang-He Zhao; Yu-Long Ma; Feng Lin; Shao-Ying Ge; Li Zhu (Environmental Science and Pollution Research, 2021)

Estimations of Land Surface Characteristic Parameters and Turbulent Heat Fluxes over the Tibetan Plateau Based on FY-4A/AGRI Data - Nan Ge; Lei Zhong; Yaoming Ma; Yunfei Fu; Mijun Zou; Meilin Cheng; Xian Wang; Ziyu Huang (Advances in Atmospheric Sciences, 2021)

Effects of Dual Fronts on the Spatial Pattern of Chlorophyll-a Concentrations in and off the Changjiang River Estuary - Weiqi Li; Jianzhong Ge; Pingxing Ding; Jianfei Ma; Patricia M. Glibert; Dongyan Liu (Estuaries and Coasts, 2021)

Study on the Effect and Mechanism of Water Immersion on the Characteristic Temperature during Coal Low-Temperature Oxidation - Xiaowei Zhai; Bobo Song; Bo Wang; Teng Ma; Hui Ge (Natural Resources Research, 2021)

Biosynthesis and preparation of phycoerythrobilin in recombinant Escherichia coli - Wenjun Li; Chengbo Ma; Baosheng Ge; Fan Zang; Song Qin; Jian Lin (Journal of Applied Phycology, 2021)

Metabolism-mediated cytotoxicity and genotoxicity of pyrrolizidine alkaloids - Yisheng He; Lin Zhu; Jiang Ma; Ge Lin (Archives of Toxicology, 2021)

Contrasting pathways of carbon sequestration in paddy and upland soils - Xiangbi Chen; Yajun Hu; Yinhang Xia; Shengmeng Zheng; Chong Ma; Yichao Rui; Hongbo He; Daoyou Huang; Zhenhua Zhang; Tida Ge; Jinshui Wu; Georg Guggenberger; et al. (Global Change Biology, 2021)
Paddy soils make up the largest anthropogenic wetlands on earth, and are characterized by a prominent potential for organic carbon (C) sequestration. By quantifying the plant‐ and microbial‐derived C in soils across four climate zones, we identified that organic C accrual is achieved via contrasting pathways in paddy and upland soils. Paddies are 39%–127% more efficient in soil organic C (SOC) sequestration than their adjacent upland counterparts, with greater differences in warmer than cooler climates. Upland soils are more replenished by microbial‐derived C, whereas paddy soils are enriched with a greater proportion of plant‐derived C, because of the retarded microbial decomposition under anaerobic conditions induced by the flooding of paddies. Under both land‐use types, the maximal contribution of plant residues to SOC is at intermediate mean annual temperature (15–20°C), neutral soil (pH~7.3), and low clay/sand ratio. By contrast, high temperature (~24°C), low soil pH (~5), and large clay/sand ratio are favorable for strengthening the contribution of microbial necromass. The greater contribution of microbial necromass to SOC in waterlogged paddies in warmer climates is likely due to the fast anabolism from bacteria, whereas fungi are unlikely to be involved as they are aerobic. In the scenario of land‐use conversion from paddy to upland, a total of 504 Tg C may be lost as CO 2 from paddy soils (0–15 cm) solely in eastern China, with 90% released from the less protected plant‐derived C. Hence, preserving paddy systems and other anthropogenic wetlands and increasing their C storage through sustainable management are critical for maintaining global soil C stock and mitigating climate change.

Influences of pika and simulated grazing disturbances on bare patches of alpine meadow in the Yellow River Source Zone - Jie-xia Li; Xi-lai Li; Jay Gao; Yan Shi; Ge-liang Ma; Ka-zhao-cai-rang (Journal of Mountain Science, 2021)

Correction to: MiR-126 Regulates the ERK Pathway via Targeting KRAS to Inhibit the Glioma Cell Proliferation and Invasion - Yang Li; Yunqian Li; Pengfei Ge; Chengyuan Ma (Molecular Neurobiology, 2021)

Variations of Concentration Characteristics of Rainfall Runoff Pollutants in Typical Urban Living Areas - Jie Xu; Xiaodong Wu; Xuguang Ge; Ying Tian; Xiaochan Ma; Yunmei Li; Xiaoguang Xu; Zhichun Li (Bulletin of Environmental Contamination and Toxicology, 2021)

Clinical application of pyrrole–hemoglobin adducts as a biomarker of pyrrolizidine alkaloid exposure in humans - Jiang Ma; Wei Zhang; Yisheng He; Lin Zhu; Chunyuan Zhang; Jia Liu; Yang Ye; Yuzheng Zhuge; Ge Lin (Archives of Toxicology, 2021)

Genomic and phylodynamic analysis of sapoviruses isolated in Henan Province, China - Jinjin Liu; Na Ren; Shanlei Hu; Lijun Zheng; Lili Ge; Shuhuan Ma; Yuqi Huo (Archives of Virology, 2021)

Lung injury induced by pyrrolizidine alkaloids depends on metabolism by hepatic cytochrome P450s and blood transport of reactive metabolites - Yisheng He; Wei Lian; Liang Ding; Xiaoyu Fan; Jiang Ma; Qing-Yu Zhang; Xinxin Ding; Ge Lin (Archives of Toxicology, 2021)

Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Hanting Liu; Jingjing Gu; Yu Jin; Qi Yuan; Gaoxiang Ma; Mulong Du; Yuqiu Ge; Chao Qin; Qiang Lv; Guangbo Fu; Meilin Wang; Haiyan Chu; et al. (Archives of Toxicology, 2021)

A combination of linkage mapping and GWAS brings new elements on the genetic basis of yield-related traits in maize across multiple environments - Xiaoxiang Zhang; Zhongrong Guan; Zhaoling Li; Peng Liu; Langlang Ma; Yinchao Zhang; Lang Pan; Shijiang He; Yanling Zhang; Peng Li; Fei Ge; Chaoying Zou; et al. (Theoretical and Applied Genetics, 2020)

An eddy-borne Argo float measurement experiment in the South China Sea - Chunyong Ma; Zhanwen Gao; Siqing Li; Shuo Li; Ge Chen (Ocean Dynamics, 2020)

Concentrations, Speciation, and Bioavailability of Heavy Metals in Street Dust as well as Relationships with Physiochemcal Properties: A Case Study of Jinan City in East China - Shuzhen Dong; Shengwei Zhang; Lijun Wang; Ge Ma; Xinwei Lu; Xiaoping Li (Environmental Science and Pollution Research, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

Biosynthesis of phycocyanobilin in recombinant Escherichia coli - Chengbo Ma; Wenjun Li; Baosheng Ge; Jian Lin; Song Qin (Journal of Oceanology and Limnology, 2020)

Sequence characteristics of Medicago truncatula cyclophilin family members and function analysis of MsCYP20-3B involved in axillary shoot development - Lingqiao Ge; Kun Zhang; Xiaohui Cao; Yinyin Weng; Bei Liu; Peisheng Mao; Xiqing Ma (Molecular Biology Reports, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Treatment and recurrence on re-treatment tuberculosis patients: a randomized clinical trial and 7-year perspective cohort study in China - Jian Du; Le Zhang; Yan Ma; X.-Y. Chen; Q.-P. Ge; X.-Z. Tian; Weiwei Gao; Zhongwei Jia (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Atmospheric mercury accumulation rate in northeastern China during the past 800 years as recorded by the sediments of Tianchi Crater Lake - Tao Zhan; Xin Zhou; Wenhan Cheng; Xiaoqing He; Luyao Tu; Xiaoyan Liu; Junyi Ge; Yuanyun Xie; Jun Zhang; Yongfa Ma; E Li; Yansong Qiao (Environmental Science and Pollution Research, 2020)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

Combination of multi-locus genome-wide association study and QTL mapping reveals genetic basis of tassel architecture in maize - Yanli Wang; Jie Chen; Zhongrong Guan; Xiaoxiang Zhang; Yinchao Zhang; Langlang Ma; Yiming Yao; Huanwei Peng; Qian Zhang; Biao Zhang; Peng Liu; Chaoying Zou; et al. (Molecular Genetics and Genomics, 2019)

Pore size distribution and reservoir characterization: evaluation for the Eocene beach-bar sequence, Dongying Depression, China - Muhammad Aleem Zahid; Dong Chunmei; Alexandra N. Golab; Chengyan Lin; Xianguo Zhang; Xinmin Ge; Wu Songtao; Muhammad Jawad Munawar; Cunfei Ma; Lydia Knuefing (Arabian Journal of Geosciences, 2019)

Neuroprotective effect of green tea extractives against oxidative stress by enhancing the survival and proliferation of PC12 cells - Zhenlu Cai; Xiaoxuan Hu; Ruolan Tan; Yunran Feng; Meiqi Sun; Ning Ma; Xingxing Li; Li Huang; Jing An; Qian Ge; Haixia Lu (Molecular & Cellular Toxicology, 2019)

Long-term stacking coal promoted soil bacterial richness associated with increased soil organic matter in coal yards of power plants - Congcong Shen; Dawei Ma; Ruibo Sun; Benyao Zhang; Delin Li; Yuan Ge (Journal of Soils and Sediments, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

Hydrochemical characteristics and irrigation suitability of surface water in the Syr Darya River, Kazakhstan - Weiyan Zhang; Long Ma; Jilili Abuduwaili; Yongxiao Ge; Gulnura Issanova; Galymzhan Saparov (Environmental Monitoring and Assessment, 2019)

Intestinal and hepatic biotransformation of pyrrolizidine alkaloid N-oxides to toxic pyrrolizidine alkaloids - Mengbi Yang; Jiang Ma; Jianqing Ruan; Yang Ye; Peter Pi-Cheng Fu; Ge Lin (Archives of Toxicology, 2019)

Identification and characterization of Populus microRNAs in response to plant growth-promoting endophytic Streptomyces sp. SSD49 - Wenjia Tian; Youyou Ge; Xiaoyu Liu; Guiming Dou; Yuchao Ma (World Journal of Microbiology and Biotechnology, 2019)

Concept Design of the “Guanlan” Science Mission: China’s Novel Contribution to Space Oceanography - Ge Chen; Junwu Tang; Chaofang Zhao; Songhua Wu; Fangjie Yu; Chunyong Ma; Yongsheng Xu; Weibiao Chen; Yunhua Zhang; Jie Liu; Lixin Wu (Frontiers in Marine Science, 2019)

Study on Damage and Repair Mechanical Characteristics of Rock Salt Under Uniaxial Compression - Hongwu Yin; Chunhe Yang; Hongling Ma; Xilin Shi; Xiangsheng Chen; Nan Zhang; Xinbo Ge; Wei Liu (Rock Mechanics and Rock Engineering, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Agricultural labor changes and agricultural economic development in China and their implications for rural vitalization - Li Ma; Hualou Long; Yingnan Zhang; Shuangshuang Tu; Dazhuan Ge; Xiaosong Tu (Journal of Geographical Sciences, 2019)

Chimeric GII.3/GII.6 norovirus capsid (VP1) proteins: characterization by electron microscopy, trypsin sensitivity and binding to histo-blood group antigens - Shuhuan Ma; Lijun Zheng; Jinjin Liu; Wenhui Wang; Jie Ma; Xuhui Cheng; Lili Ge; Mingchen Wang; Yuqi Huo; Shuo Shen (Archives of Virology, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

The role of formation of pyrrole–ATP synthase subunit beta adduct in pyrrolizidine alkaloid-induced hepatotoxicity - Yao Lu; Jiang Ma; Zijing Song; Yang Ye; Peter P. Fu; Ge Lin (Archives of Toxicology, 2018)

Genomic characterization of circoviruses associated with acute gastroenteritis in minks in northeastern China - Junwei Ge; Shanshan Gu; Xingyang Cui; Lili Zhao; Dexing Ma; Yunjia Shi; Yuanzhi Wang; Taofeng Lu; Hongyan Chen (Archives of Virology, 2018)

The relative abundance of alkane‐degrading bacteria oscillated similarly to a sinusoidal curve in an artificial ecosystem model from oil‐well products - Guoqiang Li; Peike Gao; Bo Zhi; Bing Fu; Ge Gao; Zhaohui Chen; Mengli Gao; Mengmeng Wu; Ting Ma (Environmental Microbiology, 2018)
Summary Microbial phylogenetic diversity and species interactions in natural ecosystems have been investigated extensively, but our knowledge about their ecological roles, community dynamics and succession patterns is far from complete. This knowledge is essential to understand the complicated interactions of microorganisms in natural ecosystems. Here, an artificial ecosystem model of microorganisms was constructed from oil‐well products and cultivated in a chemostat to investigate the succession pattern of alkane‐degrading bacteria, a functional population in oil reservoirs. Their abundance was quantified by an improved qPCR technique. Our results showed that the phylogenetic structure of this artificial ecosystem model is stable during most of the chemostat cultivation process, while the genotype structure of alkane‐degrading bacteria containing alk B genes shifted and their relative abundance oscillated similarly to a sinusoidal curve, like the succession pattern of producers in the Lotka–Volterra model. These results suggest that some theoretical frameworks of macroecology may work well in microbial ecosystems and be an efficient tool to understand them.

OsERF101, an ERF family transcription factor, regulates drought stress response in reproductive tissues - Yue Jin; Weiyang Pan; Xiufang Zheng; Xuan Cheng; Mengmeng Liu; Hong Ma; Xiaochun Ge (Plant Molecular Biology, 2018)

Did carbon dioxide emission regulations inhibit investments? A provincial panel analysis of China - Jianping Ge; Yalin Lei; Qun Xu; Xiangrong Ma (Environmental Science and Pollution Research, 2018)

Arsenic removal from water by metal-organic framework MIL-88A microrods - Hao Wu; Meng-Dan Ma; Wei-Zhuo Gai; Hongxun Yang; Jian-Ge Zhou; Zhenxiang Cheng; Pingguang Xu; Zhen-Yan Deng (Environmental Science and Pollution Research, 2018)

Metformin reduces the relapse rate of tuberculosis patients with diabetes mellitus: experiences from 3-year follow-up - Y. Ma; Y. Pang; W. Shu; Y.-H. Liu; Q.-P. Ge; J. Du; L. Li; W.-W. Gao (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Agaricus blazei Murill Polysaccharides Protect Against Cadmium-Induced Oxidative Stress and Inflammatory Damage in Chicken Spleens - Wanqiu Xie; Ai Lv; Ruyue Li; Zequn Tang; Dexing Ma; Xiaodan Huang; Ruili Zhang; Ming Ge (Biological Trace Element Research, 2018)

Electron acceptors for anaerobic oxidation of methane drive microbial community structure and diversity in mud volcanoes - Ge Ren; Anzhou Ma; Yanfen Zhang; Ye Deng; Guodong Zheng; Xuliang Zhuang; Guoqiang Zhuang; Danielle Fortin (Environmental Microbiology, 2018)
Summary Mud volcanoes (MVs) emit globally significant quantities of methane into the atmosphere, however, methane cycling in such environments is not yet fully understood, as the roles of microbes and their associated biogeochemical processes have been largely overlooked. Here, we used data from high‐throughput sequencing of microbial 16S rRNA gene amplicons from six MVs in the Junggar Basin in northwest China to quantify patterns of diversity and characterize the community structure of archaea and bacteria. We found anaerobic methanotrophs and diverse sulfate‐ and iron‐reducing microbes in all of the samples, and the diversity of both archaeal and bacterial communities was strongly linked to the concentrations of sulfate, iron and nitrate, which could act as electron acceptors in anaerobic oxidation of methane (AOM). The impacts of sulfate/iron/nitrate on AOM in the MVs were verified by microcosm experiments. Further, two representative MVs were selected to explore the microbial interactions based on phylogenetic molecular ecological networks. The sites showed distinct network structures, key species and microbial interactions, with more complex and numerous linkages between methane‐cycling microbes and their partners being observed in the iron/sulfate‐rich MV. These findings suggest that electron acceptors are important factors driving the structure of microbial communities in these methane‐rich environments.

Farmland function evolution in the Huang-Huai-Hai Plain: Processes, patterns and mechanisms - Yingnan Zhang; Hualou Long; Li Ma; Dazhuan Ge; Shuangshuang Tu; Yi Qu (Journal of Geographical Sciences, 2018)

Cloning and characterization of a specific UDP-glycosyltransferase gene induced by DON and Fusarium graminearum - Lanfei Zhao; Xin Ma; Peisen Su; Wenyang Ge; Hongyan Wu; Xiuxiu Guo; Anfei Li; Hongwei Wang; Lingrang Kong (Plant Cell Reports, 2018)

Evaluation of vulnerable PM2.5-exposure individuals: a repeated-measure study in an elderly population - Haiyan Chu; Junyi Xin; Qi Yuan; Xu Zhang; Wang Pan; Xinying Zeng; Yaoyao Chen; Gaoxiang Ma; Yuqiu Ge; Mulong Du; Na Tong; Xiaobo Li; et al. (Environmental Science and Pollution Research, 2018)

Factors Influencing Morphological Characteristics of Keratella cochlearis in Lake Tingtang - Yali Ge; Yilong Xi; Jie Ma; Dandan Xu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Climatology and seasonality of upper ocean salinity: a three-dimensional view from argo floats - Ge Chen; Lin Peng; Chunyong Ma (Climate Dynamics, 2018)

Different behavioral, neural and neuropeptide responses of fathers to their own and to alien pups in mandarin voles - Wei Yuan; Xiang-Ping Yang; Peng Yu; Rui Jia; Fa-Dao Tai; Bin Wei; Xiao Liu; Lei-Ge Ma (Journal of Comparative Physiology A, 2018)

Functional analysis of spinach CONSTITUTIVE EXPRESSOR OF PATHOGENESIS-RELATED GENES5 (SoCPR5) in plant immunity - Teng Song; Yuxia Lou; Chenxi Xu; Xiaofeng Cai; Xiaoli Wang; Huimin Ma; Tianhua Wang; Jianjian Zhou; Chenhui Ge; Quanhua Wang; Shui Wang (European Journal of Plant Pathology, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

A WTLS-based rational function model for orthorectification of remote-sensing imagery - Yong Ge; Yongzhao Wei; Yongze Song; Tianjun Wu; Alfred Stein; Xian Guo; Chenghu Zhou; Jianghong Ma (International Journal of Remote Sensing, 2017)

Hypsodonty of Dipodidae (Rodentia) in Correlation with Diet Preferences and Habitats - Haidan Ma; Deyan Ge; Georgy Shenbrot; Julie Pisano; Qisen Yang; Zhaoqun Zhang (Journal of Mammalian Evolution, 2017)

Microsatellite records for volume 9, issue 4 - Zhaosheng Cai; Wenxuan Cao; Jie Chen; Jiayin Dai; Ge Ding; Samantha Gray; Jiasheng Hao; Xiayun Jiang; B. B. Li; Yao Li; Z. B. Li; Gang Liu; et al. (Conservation Genetics Resources, 2017)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

The Effects of Agaricus blazei Murill Polysaccharides on Cadmium-Induced Apoptosis and the TLR4 Signaling Pathway of Peripheral Blood Lymphocytes in Chicken - Wenjing Liu; Ming Ge; Xuequan Hu; Ai Lv; Dexing Ma; Xiaodan Huang; Ruili Zhang (Biological Trace Element Research, 2017)

Comparative study on magnetic minerals of tidal flat deposits from different sediment sources in Jiangsu coast, Eastern China - Longsheng Wang; Shouyun Hu; Ge Yu; Mingming Ma; Mengna Liao (Studia Geophysica et Geodaetica, 2017)

Simulated sensitivity of the tropical cyclone eyewall replacement cycle to the ambient temperature profile - Xulin Ma; Jie He; Xuyang Ge (Advances in Atmospheric Sciences, 2017)

Characteristics of temperature change in China over the last 2000 years and spatial patterns of dryness/wetness during cold and warm periods - Quansheng Ge; Haolong Liu; Xiang Ma; Jingyun Zheng; Zhixin Hao (Advances in Atmospheric Sciences, 2017)

JNK Activation Contributes to Oxidative Stress-Induced Parthanatos in Glioma Cells via Increase of Intracellular ROS Production - Linjie Zheng; Chen Wang; Tianfei Luo; Bin Lu; Hongxi Ma; Zijian Zhou; Dong Zhu; Guangfan Chi; Pengfei Ge; Yinan Luo (Molecular Neurobiology, 2017)

The relationship between urbanization, income growth and carbon dioxide emissions and the policy implications for China: a cointegrated vector error correction (VEC) analysis - Xiangrong Ma; Jianping Ge; Wei Wang (Natural Hazards, 2017)

On the coupling between precipitation and potential evapotranspiration: contributions to decadal drought anomalies in the Southwest China - Shanlei Sun; Haishan Chen; Weimin Ju; Guojie Wang; Ge Sun; Jin Huang; Hedi Ma; Chujie Gao; Wenjian Hua; Guixia Yan (Climate Dynamics, 2017)

Near-Infrared Spectroscopy Assay of Key Quality-Indicative Ingredients of Tongkang Tablets - Wenjie Pan; Jinfang Ma; Xue Xiao; Zhengwei Huang; Huanbin Zhou; Fahuan Ge; Xin Pan (AAPS PharmSciTech, 2017)

Spatial distribution and bioaccumulation of polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) in snails (Bellamya aeruginosa) and sediments from Taihu Lake area, China - Ge Yin; Yihui Zhou; Anna Strid; Ziye Zheng; Anders Bignert; Taowu Ma; Ioannis Athanassiadis; Yanling Qiu (Environmental Science and Pollution Research, 2017)

Physiological and anatomical responses of Phyllostachys vivax and Arundinaria fortunei (Gramineae) under salt stress - Wei Ge; Ying Zhang; Zhongyuan Sun; Juan Li; Guohua Liu; Yanjun Ma; Jian Gao (Brazilian Journal of Botany, 2017)

RETRACTED ARTICLE: MiR-126 Regulates the ERK Pathway via Targeting KRAS to Inhibit the Glioma Cell Proliferation and Invasion - Yang Li; Yunqian Li; Pengfei Ge; Chengyuan Ma (Molecular Neurobiology, 2017)

Spatial pattern of grassland aboveground biomass and its environmental controls in the Eurasian steppe - Cuicui Jiao; Guirui Yu; Nianpeng He; Anna Ma; Jianping Ge; Zhongmin Hu (Journal of Geographical Sciences, 2017)

A real-time photo-realistic rendering algorithm of ocean color based on bio-optical model - Chunyong Ma; Shu Xu; Hongsong Wang; Fenglin Tian; Ge Chen (Journal of Ocean University of China, 2016)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

Impacts of the diurnal cycle of solar radiation on spiral rainbands - Shunwu Zhou; Yue Ma; Xuyang Ge (Advances in Atmospheric Sciences, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Temporal Variability and Potential Diffusion Characteristics of Dust Aerosol Originating from the Aral Sea Basin, Central Asia - Yongxiao Ge; Jilili Abuduwaili; Long Ma; Dongwei Liu (Water, Air, & Soil Pollution, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

New norditerpenoid alkaloids from Aconitum vilmorinianum Komarov - Cui-Ling Chen; Wen-Hong Tan; Yan Wang; Zhi-Ge Xue; Chun-Ping Wan; Zhu-Ya Yang; Zhi-Hong Zhou; Xiao-Xia Ma (Journal of Natural Medicines, 2015)

Development polymorphic microsatellite primers for the giant panda’s staple food bamboo Bashania fargesii and B. aristata (Poaceae: Bambusoideae) - Ge Yu; Jian-Jun Liu; Qing-Qing Ma; Yi-Sheng Ma (Conservation Genetics Resources, 2015)

Molecular phylogeny and the underestimated species diversity of the endemic white‐bellied rat (Rodentia: Muridae: Niviventer ) in Southeast Asia and China - Liang Lu; Deyan Ge; Douglas Chesters; Simon Y. W. Ho; Ying Ma; Guichang Li; Zhixin Wen; Yongjie Wu; Jun Wang; Lin Xia; Jingli Liu; Tianyu Guo; et al. (Zoologica Scripta, 2015)
The white‐bellied rat, Niviventer , is a genus endemic to Southeast Asia and China. However, the interspecific phylogenetic relationships and species diversity of this genus remain poorly understood. In the present study, single and multi‐locus analyses were performed. Phylogenetic reconstruction on Cytochrome b (512 individuals, including data from Genbank) revealed five major clades with approximately 35 operational taxonomic units ( OTU s), a number twice the existing taxonomy. The first clade ( N . langbianis species group) was the earliest diverged. The second clade ( N. fulvescens species group) diverged in Southeast Asia, the south and lower altitude regions of the Hengduan Mountains, and Southeast China. The third clade (the N. eha species group) is endemic to high altitudes in Northwest Yunnan and the central region of Himalaya. The fourth clade (the N. andersoni species group), is mainly confined to alpine regions of the Hengduan Mountains. The fifth clade ( N . confucianus species group) is mainly distributed in the north and higher altitude regions of eastern Himalaya, the Hengduan Mountains and Taiwan, with the complex also invading central and northern China. Results from the combined dataset of four genes (Cytochrome b, Cytochrome oxidase subunit I, the D‐loop sequence of the mitochondrial genome and the first exon of the nuclear interphotoreceptor retinoid binding protein) for 82 representative individuals from China generally coincide with the result of the single gene, with 12 OTU s identified. These results provide a preliminary framework for the existing classification of this highly diversified genus. The divergence time of Niviventer based on the four gene topology was dated to the late Miocene ~6.41 Ma. Significant differences were detected in the general body form changes among these units based on voucher specimens. Moreover, geometric morphometric analysis of the cranium shape of voucher specimens indicated significant differences among five major species groups. Shape divergence of the cranium among several OTU s within the N. confucinaus complex is also significant. Our results provide further evidence for rapid and highly underestimated diversification of Niviventer both in genetics and morphology.

Sensitivity of the warm core of tropical cyclones to solar radiation - Xuyang Ge; Yue Ma; Shunwu Zhou; Tim Li (Advances in Atmospheric Sciences, 2015)

Erratum to: Regioselective Glucuronidation of Andrographolide and Its Major Derivatives: Metabolite Identification, Isozyme Contribution, and Species Differences - Xiangge Tian; Sicheng Liang; Chao Wang; Baojian Wu; Guangbo Ge; Sa Deng; Kexin Liu; Ling Yang; Xiaochi Ma (The AAPS Journal, 2015)

Regioselective Glucuronidation of Andrographolide and Its Major Derivatives: Metabolite Identification, Isozyme Contribution, and Species Differences - Xiangge Tian; Sicheng Liang; Chao Wang; Baojian Wu; Guangbo Ge; Sa Deng; Kexin Liu; Ling Yang; Xiaochi Ma (The AAPS Journal, 2015)

Impacts of the diurnal cycle of radiation on tropical cyclone intensification and structure - Xuyang Ge; Yue Ma; Shunwu Zhou; Tim Li (Advances in Atmospheric Sciences, 2014)

Combined bioremediation of atrazine-contaminated soil by Pennisetum and Arthrobacter sp. strain DNS10 - Ying Zhang; Shijie Ge; Mingyue Jiang; Zhao Jiang; Zhigang Wang; Bingbing Ma (Environmental Science and Pollution Research, 2014)

A tripeptide (NSK) inhibits Japanese encephalitis virus infection in vitro and in vivo - Chen Li; Ling-ling Ge; Ya-ling Yu; Li Huang; Yue Wang; Ming-xia Sun; Hassan Ishag; Liang-xiao Ma; Xue-hua Li; Zhi-qiang Shen; Xiang Mao (Archives of Virology, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

Analysis of the microphysical properties of a stratiform rain event using an L-Band profiler radar - Zheng Ruan; Hu Ming; Jianli Ma; Runsheng Ge; Lingen Bian (Journal of Meteorological Research, 2014)

Ginkgo biloba extract reducing myocardium cells apoptosis by regulating apoptotic related proteins expression in myocardium tissues - Zeng Yong Qiao; Jian Hua Huang; Jiang Wei Ma; Ya Wei Xu; Jun Xie; Hua Jin Liu; San Jun Xiong; Guang Hao Ge (Molecular Biology Reports, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Interactions between soybean ABA receptors and type 2C protein phosphatases - Ge Bai; Da-Hai Yang; Yang Zhao; Si Ha; Fen Yang; Jun Ma; Xiao-Shu Gao; Zhi-Min Wang; Jian-Kang Zhu (Plant Molecular Biology, 2013)

Fine mapping TaFLW1, a major QTL controlling flag leaf width in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Guoqiang Li; Yan Zhou; Musen Lin; Zhongxia Gao; Xiuhong Su; Xiaowu Xu; Ge Jiang; Shuang Zhang; Haiyan Jia; Zhongxin Kong; et al. (Theoretical and Applied Genetics, 2013)

Decreased expression of the DBC2 gene and its clinicopathological significance in breast cancer: correlation with aberrant DNA methylation - Linlin Han; Lin Hou; Jinlian Song; Dongliang Lin; Li Wu; Yinlin Ge; Zhongliang Ma (Biotechnology Letters, 2013)

The rice OsDIL gene plays a role in drought tolerance at vegetative and reproductive stages - Changkui Guo; Xiaochun Ge; Hong Ma (Plant Molecular Biology, 2013)

Changes of spring phenodates for the past 150 years over the Yangtze River Delta - Jingyun Zheng; Shuying Zhong; Quansheng Ge; Zhixin Hao; Xuezhen Zhang; Xiang Ma (Journal of Geographical Sciences, 2013)

Pathways and Organisms Involved in Ammonia Oxidation and Nitrous Oxide Emission - Jianhua Guo; Yongzhen Peng; Shuying Wang; Bin Ma; Shijian Ge; Zhongwei Wang; Huijun Huang; Jingrong Zhang; Liang Zhang (Critical Reviews in Environmental Science and Technology, 2013)

High density lipoprotein cholesterol promotes the proliferation of bone-derived mesenchymal stem cells via binding scavenger receptor-B type I and activation of PI3K/Akt, MAPK/ERK1/2 pathways - Jianfeng Xu; Juying Qian; Xinxing Xie; Li Lin; Jianying Ma; Zheyong Huang; Mingqiang Fu; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Scaled total-least-squares-based registration for optical remote sensing imagery - Yong Ge; Tianjun Wu; Jianghao Wang; Jianghong Ma; Yunyan Du (Earth Science Informatics, 2012)

Bone Mineral Density and Elemental Composition of Bone Tissues in “Red-Boned” Guishan Goats - Chenchen Wu; Jianguo Wang; Peng Li; Guowen Liu; Xiaobing Li; Huarong Ma; Weizhong Wang; Zhe Wang; Changrong Ge; Shizheng Gao (Biological Trace Element Research, 2012)

Iodine-125 Seed Implantation in the Treatment of Sacrococcygeal Chordoma: A Case Report - Rong-hui Ni; Ge Wang; Zhi-min Zhang; Jun-gang Ma (Cell Biochemistry and Biophysics, 2012)

Cryptotanshinone induces cell cycle arrest and apoptosis of multidrug resistant human chronic myeloid leukemia cells by inhibiting the activity of eukaryotic initiation factor 4E - Yuqing Ge; Rubin Cheng; Yuhong Zhou; Jianping Shen; Laijun Peng; Xiaofeng Xu; Qun Dai; Pei Liu; Haibing Wang; Xiaoqiong Ma; Jia Jia; Zhe Chen (Molecular and Cellular Biochemistry, 2012)

Phylogenetic and functional alpha and beta diversity in temperate and tropical tree communities - Nathan G. Swenson; David L. Erickson; Xiangcheng Mi; Norman A. Bourg; Jimena Forero-Montaña; Xuejun Ge; Robert Howe; Jeffrey K. Lake; Xiaojuan Liu; Keping Ma; Nancai Pei; Jill Thompson; et al. (Ecology, 2012)
The study of biodiversity has tended to focus primarily on relatively information‐poor measures of species diversity. Recently, many studies of local diversity (alpha diversity) have begun to use measures of functional and phylogenetic alpha diversity. Investigations into the phylogenetic and functional dissimilarity (beta diversity) of communities have been far less numerous, but these dissimilarity measures have the potential to infer the mechanisms underlying community assembly and dynamics. Here, we relate levels of phylogenetic and functional alpha diversity to levels of phylogenetic and functional beta diversity to infer the mechanism or mechanisms responsible for the assembly of tree communities in six forests located in tropical and temperate latitudes. The results show that abiotic filtering plays a role in structuring local assemblages and governing spatial turnover in community composition and that phylogenetic measures of alpha and beta diversity are not strong predictors of functional alpha and beta diversity in the forests studied.

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

TEE monitoring for RA-horizontal paradoxical arterial air embolism during sitting-position surgery - Xin Ye; Ting Ma; TianLong Wang; MingFei Ge; CaiRong Wang; Jing Gao; XiaoHui Li (Science China Life Sciences, 2010)

A mutant of infectious Asia 1 serotype foot-and-mouth disease virus with the deletion of 10-amino-acid in the 3A protein - Shuang Li; Mingchun Gao; Runxiang Zhang; Ge Song; Jun Song; Dandan Liu; Yongsheng Cao; Tingting Li; Bo Ma; Xiangtao Liu; Junwei Wang (Virus Genes, 2010)

Isolation and characterization of polymorphic microsatellite loci from a dinucleotide-enriched genomic library of obscure puffer (Takifugu obscurus) and cross-species amplification - Hongyu Ma; Songlin Chen; Xiaolin Liao; Tianjun Xu; Jiachun Ge (Conservation Genetics, 2009)

Comparative analysis of distinct non-coding characteristics potentially contributing to the divergence of human tissue-specific genes - Qianli Huang; Jiaming Guo; Qq Ge; Jesse Li-Ling; Xueping Chen; Fei Ma (Genetica, 2009)

Distribution, sources, and potential risk of polycyclic aromatic hydrocarbons (PAHs) in drinking water resources from Henan Province in middle of China - Ying-ge Ma; Jin-ping Cheng; Fei Jiao; Ke-xin Duo; Zheng Rong; Ming Li; Wen-hua Wang (Environmental Monitoring and Assessment, 2008)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)

Role of withdrawal in reinstatement of morphine-conditioned place preference - Lin Lu; Hai Chen; Wenjuan Su; Xin Ge; Wen Yue; Fen Su; Lan Ma (Psychopharmacology, 2005)

Spatial-temporal dynamics of regional convergence at County level in Jiangsu - Ying-xia Pu; Rong-hua Ma; Ying Ge; Xing-yuan Huang (Chinese Geographical Science, 2005)

Identification of 27 Porphyra lines (Rhodophyta) by DNA fingerprinting and molecular markers - Manli Weng; Bo Liu; Demin Jin; Qingkai Yang; Ge Zhao; Jiahai Ma; Pu Xu; Delin Duan; Bin Wang (Journal of Applied Phycology, 2005)

Reactivation of morphine conditioned place preference by drug priming: role of environmental cues and sensitization - Lin Lu; Nan-Jie Xu; Xin Ge; Wen Yue; Wen-Juan Su; Gang Pei; Lan Ma (Psychopharmacology, 2002)